Microfibrous cellulose, dispersion, sheet, laminated sheet, laminated body, and method for producing microfibrous cellulose
By controlling the amount of substituents and fiber width of microfibrous cellulose, combining anionic groups and specific manufacturing methods, the problem of reducing transparency and coloring after substituent removal is solved, and a dispersion with high transparency and low coloring is achieved and the preparation of laminated sheets, suitable for applications such as optical components.
Patent Information
- Application Number
- CN202180036590.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-18
- Filing Date
- 2021-05-19
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-05-19
AI Technical Summary
The prior art has easily caused the reduction of transparency or coloring after removing substituents in fine fibrous cellulose. Especially when removing functional groups in the slurry state, it is difficult to simultaneously improve transparency and suppress coloring.
By controlling the amount of substituent introduction in microfibrous cellulose, the fiber width is 1 to 10 nm, and anionic groups such as phosphorus oxyacid or sulfo groups are used, combined with specific manufacturing methods such as heating treatment With uniform dispersion treatment, a high transparency dispersion liquid and laminated sheet were prepared.
It is realized that the transparency and coloring are improved when the dispersion liquid and sheet are prepared, and the laminated sheet with high transparency and coloring is suppressed is obtained, which is suitable for applications such as optical components.
Smart Images

Figure BDA0003952492690000111 
Figure BDA0003952492690000131 
Figure BDA0003952492690000161
Abstract
Description
Technical Field
[0001] The present invention relates to fine fibrous cellulose, a dispersion, a sheet, a laminated sheet, a laminate, and a method for producing fine fibrous cellulose. Background Art
[0002] In recent years, due to the replacement of petroleum resources and the improvement of environmental awareness, attention has been paid to materials obtained from renewable natural fibers. Among natural fibers, fibrous cellulose with a fiber diameter of 10 μm or more and 50 μm or less, especially fibrous cellulose (pulp) derived from wood, has been widely used mainly as paper products.
[0003] As fibrous cellulose, microfibrous cellulose having a fiber diameter of 1 μm or less is also known. Microfibrous cellulose has attracted much attention as a new raw material, and its uses are diverse. For example, sheets, resin composites, and thickeners containing microfibrous cellulose have been developed.
[0004] Microfibrous cellulose can be produced by defibration of cellulose fibers. However, since cellulose fibers are strongly bonded to each other by hydrogen bonds, a large amount of energy is required to obtain microfibrous cellulose when simply defibration is performed. Therefore, it is known that in order to produce microfibrous cellulose with less fibrillation energy, it is effective to perform a pretreatment such as a chemical treatment or a biological treatment together with the fibrillation.
[0005] For example, it is known that if ionic functional groups are introduced into cellulose fibers by chemical treatment of cellulose fibers, the cellulose fibers are easily micronized, and the dispersion stability after micronization is also improved. On the other hand, sometimes the system containing cellulose fibers changes in ionic strength and pH or reactions originating from functional groups occur. Therefore, sometimes problems such as deterioration and yellowing of cellulose fibers occur.
[0006] Therefore, research has been conducted to remove ionic functional groups at any time after micronization. For example, Patent Document 1 discloses a method for producing microfibers, which has the following steps: (a) a step of introducing substituents having electrostatic functionality and / or stereo functionality into a microfiber raw material to obtain substituent-introduced fibers; (b) a step of mechanically treating the substituent-introduced fibers; (c) a step of partially or completely removing the introduced substituents from the substituent-introduced microfibers obtained in step (b) to obtain substituent-removed microfibers. In addition, Patent Document 2 discloses a method for producing a deesterified compound, which includes the step of heating a compound having an ester derived from phosphoric acid and / or an ester derived from carboxylic acid in the presence of an alkaline nitrogen-containing compound. These documents study the removal of substituents introduced into microfibers.
[0007] Patent Document 3 discloses a method for producing a sheet containing fine fibers, wherein the method for producing a sheet containing fine fibers comprises at least the following steps: (a) a step of introducing a substituent having electrostatic functionality and / or stereofunctionality into a fiber raw material to obtain a substituent-introduced fiber; (b) a step of mechanically treating the substituent-introduced fiber obtained in step (a) to obtain a substituent-introduced fine fiber; (c) a step of preparing a sheet from the substituent-introduced fine fiber obtained in step (b); and (d) a step of removing at least a part of the introduced substituent from the sheet obtained in step (c). Here, a method of removing the substituent after forming a sheet from fine fibers having substituents is studied.
[0008] Furthermore, Patent Documents 4 and 5 disclose a method for producing xanthate cellulose nanofibers, wherein xanthate cellulose or a cationic substituted product of xanthate cellulose is subjected to a defibration treatment. Patent Document 4 also studies a method for restoring xanthate cellulose nanofibers to unmodified cellulose by regenerating the xanthate cellulose nanofibers as needed. In addition, Patent Document 5 discloses a sheet containing derivative functional group-detached cellulose microfibers, which is obtained by detaching functional groups from microfibers of a cellulose derivative, and has an average fiber diameter of 3 nm or more and 300 nm or less.
[0009] In addition, in recent years, the development of a composite body including a resin layer and a sheet containing fine fibrous cellulose has also been carried out. For this composite body, for example, research has been conducted to improve the adhesion between a sheet (fiber layer) containing fine fibrous cellulose and a resin layer. For example, Patent Document 6 discloses a laminate having: a fiber layer containing fine fibrous cellulose, and a resin layer in contact with one surface of the fiber layer. In addition, Patent Document 7 discloses a laminate having: a fiber layer formed of fine fibrous cellulose, a resin layer, and an adhesive layer disposed between the fiber layer and the resin layer, and Patent Document 8 discloses a laminate having a substrate, an anchoring layer, and a cellulose nanofiber layer disposed in sequence.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: International Publication No. 2013 / 176049
[0013] Patent Document 2: Japanese Patent Application Publication No. 2015-098526
[0014] Patent Document 3: International Publication No. 2015 / 182438
[0015] Patent Document 4: International Publication No. 2017 / 111103
[0016] Patent Document 5: Japanese Patent Application Publication No. 2019-7101
[0017] Patent Document 6: International Publication No. 2017 / 126432
[0018] Patent Document 7: Japanese Patent Application Publication No. 2017-056715
[0019] Patent Document 8: Japanese Patent Application Publication No. 2014-079938 Summary of the invention
[0020] Problem that the invention aims to solve
[0021] The present inventors have studied microfibrous cellulose after the substituents have been removed and have found that if the functional groups are removed in a microfibrous slurry state, the transparency is reduced, and if the functional groups are removed in a sheet state, coloring occurs.
[0022] Therefore, in order to solve the problems of the prior art, the present inventors have conducted research for the purpose of providing a microfibrous cellulose after the substituent is removed, which can improve transparency and suppress coloration when it is made into a dispersion liquid or a sheet. In addition, an object of the present invention is to provide a laminated sheet having a resin layer and a fiber layer containing microfibrous cellulose, the laminated sheet having high transparency and suppressed coloration.
[0023] Solutions for solving problems
[0024] Specifically, the present invention has the following configurations.
[0025] [1] A microfibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm.
[0026] [2] The fine fibrous cellulose according to [1], wherein the nanofiber yield calculated by the following formula is 95% by mass or more;
[0027] Nanofiber yield [mass %] = C / 0.1×100
[0028] Here, C is the concentration of fine fibrous cellulose contained in the supernatant obtained when an aqueous dispersion having a fine fibrous cellulose concentration of 0.1% by mass is centrifuged under the conditions of 12000 G for 10 minutes.
[0029] [3] The fine fibrous cellulose according to [1] or [2], wherein when the fine fibrous cellulose is prepared as an aqueous dispersion having a concentration of 0.2% by mass, the haze of the aqueous dispersion is 5.0% or less.
[0030] [4] The fine fibrous cellulose according to any one of [1] to [3], wherein the substituent is an anionic group.
[0031] [5] The fine fibrous cellulose according to [4], wherein the anionic group is a phosphorus oxyacid group or a substituent derived from a phosphorus oxyacid group.
[0032] [6] The fine fibrous cellulose according to any one of [1] to [5], which has a urea group.
[0033] [7] A dispersion containing the fine fibrous cellulose according to any one of [1] to [6].
[0034] [8] A sheet comprising the fine fibrous cellulose according to any one of [1] to [6].
[0035] [9] A laminated sheet comprising the sheet according to [8] and a resin layer.
[0036]
[10] A sheet comprising fine fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm,
[0037] The sheet has a YI value of 1.5 or less when the sheet has a thickness of 50 μm.
[0038]
[11] The sheet according to
[10] , wherein when the sheet is heated at 160° C. for 6 hours, the YI increase rate calculated by the following formula is 1500% or less;
[0039] YI increase rate (%) = (yellowness index of the sheet after heating - yellowness index of the sheet before heating) / yellowness index of the sheet before heating × 100
[0040] In the above formula, the yellowness index of the sheet is a yellowness index measured in accordance with JIS K 7373:2006.
[0041]
[12] The sheet according to
[10] or
[11] , which has a total light transmittance of 90.0% or more.
[0042]
[13] The sheet according to any one of
[10] to
[12] , which has a haze of 5.0% or less.
[0043]
[14] The sheet according to any one of
[10] to
[13] , wherein the surface roughness of at least one surface is 10 nm or less.
[0044]
[15] A laminated sheet comprising a fiber layer and a resin layer disposed on at least one surface of the fiber layer,
[0045] The fiber layer comprises fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm.
[0046]
[16] The laminated sheet according to
[15] , wherein the thickness of the fiber layer is 20 μm or more.
[0047]
[17] The laminated sheet according to
[15] or
[16] , wherein the density of the fiber layer is 1.0 g / cm 3 above.
[0048]
[18] The laminate sheet according to any one of
[15] to
[17] , wherein the resin layer is directly laminated on the fiber layer.
[0049]
[19] The laminated sheet according to any one of
[15] to
[18] , wherein the resin layer comprises at least one selected from a polycarbonate resin and an acrylic resin.
[0050]
[20] The laminated sheet according to any one of
[15] to
[19] , wherein the resin layer further contains an adhesion aid.
[0051]
[21] The laminated sheet according to
[20] , wherein the adhesion aid is at least one selected from the group consisting of isocyanate compounds and organosilicon compounds.
[0052]
[22] The laminated sheet according to
[20] or
[21] , wherein the adhesion aid is an isocyanate compound, and the content of the isocyanate compound is 10 parts by mass or more and 40 parts by mass or less relative to 100 parts by mass of the resin contained in the resin layer.
[0053]
[23] The laminated sheet according to any one of
[15] to
[22] , wherein the YI value is 2.0 or less.
[0054]
[24] The laminated sheet according to any one of
[15] to
[23] , which has a haze of 2.0% or less.
[0055]
[25] The laminated sheet according to any one of
[15] to
[24] , which is used for an optical member.
[0056]
[26] A laminate comprising the laminate sheet according to any one of
[15] to
[25] and an adherend.
[0057]
[27] A method for producing microfibrous cellulose, comprising:
[0058] A step (A) of removing at least a part of the substituent from the fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less; and
[0059] After the step (A), a step (B) of performing a uniform dispersion treatment is performed.
[0060]
[28] The method for producing fine fibrous cellulose according to
[27] , wherein the amount of substituents introduced into the fine fibrous cellulose subjected to step (A) is 0.60 mmol / g or more.
[0061]
[29] The method for producing fine fibrous cellulose according to
[27] or
[28] , wherein the substituent is an anionic group.
[0062]
[30] The method for producing fine fibrous cellulose according to
[29] , wherein the anionic group is a phosphorus oxyacid group or a substituent derived from a phosphorus oxyacid group.
[0063]
[31] The method for producing fine fibrous cellulose according to any one of
[27] to
[30] , wherein the fine fibrous cellulose used in step (A) has a urea group.
[0064]
[32] The method for producing fine fibrous cellulose according to any one of
[27] to
[31] , further comprising a step of reducing the nitrogen content.
[0065]
[33] The method for producing fine fibrous cellulose according to any one of
[27] to
[32] , wherein step (A) is performed in a slurry state.
[0066]
[34] The method for producing fibrous cellulose according to
[33] , further comprising, before step (A), a step of adjusting the pH of the slurry containing fine fibrous cellulose to 3 to 8.
[0067]
[35] The fine fibrous cellulose according to any one of [1] to [6], which is used for a concrete pump primer.
[0068]
[36] The fine fibrous cellulose according to any one of [1] to [6], which is used as a lubricant.
[0069]
[37] The fine fibrous cellulose according to any one of [1] to [6], which is used in a casting molding composition.
[0070]
[38] The fine fibrous cellulose according to any one of [1] to [6], which is used for a dental material.
[0071]
[39] The fine fibrous cellulose according to any one of [1] to [6], which is used in a polishing agent.
[0072]
[40] The fine fibrous cellulose according to any one of [1] to [6], which is used in a release agent.
[0073]
[41] The fine fibrous cellulose according to any one of [1] to [6], which is used as an additive for papermaking.
[0074]
[42] A concrete pump pipe lubricant comprising the fine fibrous cellulose according to any one of [1] to [6].
[0075]
[43] A lubricant comprising the fine fibrous cellulose according to any one of [1] to [6].
[0076]
[44] A casting composition comprising the fine fibrous cellulose according to any one of [1] to [6].
[0077]
[45] A dental material comprising the fine fibrous cellulose according to any one of [1] to [6].
[0078]
[46] An abrasive comprising the fine fibrous cellulose according to any one of [1] to [6].
[0079]
[47] A release agent comprising the fine fibrous cellulose according to any one of [1] to [6].
[0080]
[48] A papermaking additive comprising the fine fibrous cellulose according to any one of [1] to [6].
[0081] Effects of the Invention
[0082] According to the present invention, it is possible to obtain fine fibrous cellulose which can improve transparency and suppress coloration when it is made into a dispersion or a sheet. In addition, according to the present invention, it is possible to obtain a laminated sheet which has high transparency and suppresses coloration. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 This is a graph showing the relationship between the amount of NaOH added dropwise to a slurry containing fibrous cellulose having a phosphorus oxyacid group and the pH.
[0084] Figure 2 It is a cross-sectional view for explaining the structure of the laminated sheet of this embodiment. DETAILED DESCRIPTION
[0085] The present invention is described in detail below. The description of the technical features described below is sometimes based on representative embodiments and specific examples, and the present invention is not limited to such embodiments. It should be noted that in this specification, the numerical range represented by "to" refers to the range containing the numerical values recorded before and after "to" as the lower limit and upper limit.
[0086] (Microfibrous cellulose)
[0087] The present invention relates to a microfibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm. In the present invention, the substituent introduction amount after removing the substituent in the microfibrous cellulose is set to less than 0.5 mmol / g, and the fiber width is set to 1 to 10 nm, so that the transparency can be improved and the coloring can be suppressed when the dispersion liquid or sheet is prepared. The transparency and coloring degree when the dispersion liquid or sheet is prepared can be evaluated based on the haze and YI value of the dispersion liquid or sheet as described below.
[0088] In the present embodiment, the amount of substituents introduced into the fine fibrous cellulose may be less than 0.5 mmol / g, preferably 0.4 mmol / g or less, more preferably 0.3 mmol / g or less, further preferably 0.25 mmol / g or less, and particularly preferably 0.15 mmol / g or less. It should be noted that the amount of substituents introduced into the fine fibrous cellulose may be 0.0 mmol / g, preferably 0.03 mmol / g or more, more preferably 0.04 mmol / g or more, further preferably 0.05 mmol / g or more, and particularly preferably 0.07 mmol / g or more.
[0089] The fiber width of the microfibrous cellulose can be 1 to 10 nm, preferably 1 to 9 nm, more preferably 1 to 8 nm, and further preferably 1 to 7 nm. Here, the fiber width of the microfibrous cellulose is measured by, for example, electron microscopy observation and the following operation. First, the microfibrous cellulose is dispersed in water in a manner such that the concentration of cellulose is 0.01% by mass or more and 0.1% by mass or less, and is cast on a hydrophilic carbon film-covered grid. After drying, it is stained with uranyl acetate and observed using a transmission electron microscope (TEM, manufactured by JEOL, JEOL-2000EX). At this time, an axis of arbitrary image width in the vertical and horizontal directions is assumed in the obtained image, and the magnification is adjusted in such a way that more than 20 fibers intersect the axis. After obtaining an observed image that meets this condition, for each image, two random axes in the vertical and horizontal directions are drawn, and the fiber width of the fiber intersecting the axis is read visually. In this manner, three non-overlapping observation images are captured, and the fiber width values of the fibers intersecting the two axes are read (20 or more fibers×2×3=120 or more fibers).
[0090] (1) Draw a straight line X at any position in the observation image, and 20 or more fibers intersect the straight line X.
[0091] (2) A straight line Y is drawn in the same image to intersect the straight line at right angles, and 20 or more fibers intersect the straight line Y.
[0092] It should be noted that, for a group of fine fibrous cellulose contained in a dispersion or the like, the number average fiber width can be calculated based on the fiber width obtained by the above method. In addition, when the sheet contains fine fibrous cellulose, the fiber width of the fine fibrous cellulose in the sheet is measured using, for example, atomic force microscopy as follows. First, an atomic force microscope (NanoScope IIIa, manufactured by Veeco) is used to observe the sheet containing fine fibrous cellulose. At this time, the image is set to a field of view of 500 nm square. For the obtained image, two random vertical and horizontal axes are drawn for each image, and 20 or more fibers that intersect the axes are randomly selected to read the fiber width by visual inspection. In this way, three non-repetitive observation images are taken, and the fiber width values of the fibers that intersect the respective two axes are read (20 or more × 2 × 3 = 120 or more)
[0093] (1) Draw a straight line X at any position in the observation image, and randomly select 20 or more fibers that intersect the straight line X.
[0094] (2) Draw a straight line Y perpendicular to the straight line in the same image, and randomly select 20 or more fibers that intersect the straight line Y.
[0095] The fiber length of the microfibrous cellulose is not particularly limited, and is, for example, preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and further preferably 0.1 μm or more and 600 μm or less. By setting the fiber length within the above range, the destruction of the crystalline region of the microfibrous cellulose can be suppressed. In addition, the slurry viscosity of the microfibrous cellulose can also be set to an appropriate range. It should be noted that the fiber length of the microfibrous cellulose can be obtained by, for example, image analysis based on TEM, SEM, or AFM.
[0096] The fine fibrous cellulose preferably has a type I crystal structure. Here, the fine fibrous cellulose having the type I crystal structure can be obtained by using CuKα monochromatized by graphite. The identification can be made by using the diffraction curve obtained from the wide-angle X-ray diffraction photograph. Specifically, it can be identified based on the presence of typical peaks at two locations, near 2θ=14° to 17° and near 2θ=22° to 23°. The proportion of type I crystal structure in fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and further preferably 50% or more. Regarding the crystallinity, an X-ray diffraction curve is measured and obtained from its pattern by conventional methods (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0097] The axial ratio (fiber length / fiber width) of the fine fibrous cellulose is not particularly limited, and is, for example, preferably 50 or more and 10,000 or less, and more preferably 100 or more and 1,000 or less. By setting the axial ratio to be above the lower limit, it is easy to form a sheet containing fine fibrous cellulose. By setting the axial ratio to be below the upper limit, it is preferred from the viewpoint of facilitating operations such as dilution when, for example, fibrous cellulose is treated in the form of a dispersion.
[0098] The fine fibrous cellulose in the present embodiment has, for example, both crystalline regions and amorphous regions. The fine fibrous cellulose having both crystalline regions and amorphous regions and having an axial ratio within the above range is achieved by a method for producing fine fibrous cellulose described below.
[0099] The cellulose component in the fine fibrous cellulose can be classified into an α-cellulose component and a hemicellulose component. When the ratio of hemicellulose is low, the effect of suppressing yellowing over time and yellowing due to heating is easily obtained, so it is preferred. The ratio of hemicellulose in the fine fibrous cellulose of the present embodiment is preferably less than 30%, more preferably less than 25%, and further preferably less than 20%.
[0100] The total amount of nitrogen contained in the microfibrous cellulose and the free nitrogen contained in the microfibrous cellulose dispersion (hereinafter sometimes referred to as "nitrogen amount", "nitrogen amount contained in microfibrous cellulose" or "nitrogen amount in microfibrous cellulose") is preferably 0.08 mmol / g or less, more preferably 0.04 mmol / g or less, and further preferably 0.02 mmol / g or less. In addition, the amount of nitrogen contained in the microfibrous cellulose is preferably 0.001 mmol / g or more. It should be noted that the amount of nitrogen in the microfibrous cellulose is a value measured by the following method. First, the solid content concentration of the dispersion containing microfibrous cellulose is adjusted to 1% by mass, and decomposed by the Kjeldahl method (JIS K 0102:2016 44.1). After decomposition, the amount of ammonium ions (mmol) is measured by cation chromatography, and the nitrogen content (mmol / g) is calculated by dividing it by the amount of cellulose (g) used in the measurement. The nitrogen amount refers to the total amount of nitrogen bonded to the microfibrous cellulose via ionic bonds and / or covalent bonds and free nitrogen dissolved in the dispersion liquid that is not bonded to the microfibrous cellulose via ionic bonds and / or covalent bonds.
[0101] In this embodiment, the amount of substituent introduced into the microfibrous cellulose is less than 0.5 mmol / g, and the substituent mentioned here is preferably an anionic group. That is, the microfibrous cellulose of this embodiment is obtained by subjecting microfibrous cellulose having anionic groups to a substituent removal treatment, and the microfibrous cellulose of this embodiment is microfibrous cellulose after the substituent is removed.
[0102] Examples of the anionic group include a phosphorus oxyacid group or a substituent derived from a phosphorus oxyacid group (sometimes simply referred to as a phosphorus oxyacid group), a carboxyl group or a substituent derived from a carboxyl group (sometimes simply referred to as a carboxyl group), a sulfo group or a substituent derived from a sulfo group (sometimes simply referred to as a sulfo group), and a xanthate group or a substituent derived from a xanthate group (sometimes simply referred to as a xanthate group). When a sulfo group or a substituent derived from a sulfo group is introduced by means of an ester bond, the substituent is sometimes referred to as a sulfur oxyacid group or a substituent derived from a sulfur oxyacid group (sometimes simply referred to as a sulfur oxyacid group). Among them, the anionic group is preferably at least one selected from a phosphorus oxyacid group or a substituent derived from a phosphorus oxyacid group, and a sulfo group or a substituent derived from a sulfo group, and more preferably a phosphorus oxyacid group or a substituent derived from a phosphorus oxyacid group.
[0103] The phosphorus oxyacid group or the substituent derived from the phosphorus oxyacid group is, for example, a substituent represented by the following formula (1). Each fine fibrous cellulose may be introduced with a plurality of substituents represented by the following formula (1). In this case, the introduced plurality of substituents represented by the following formula (1) may be the same or different.
[0104]
[0105] In formula (1), a, b and n are natural numbers, and m is an arbitrary number (where a=b×m). At least one of the n existing α and α′ is O - , the remainder is R or OR. It should be noted that each α and α' can all be O - The n αs that exist can be all the same or different from each other. b+ It is a cation with a valence of one or more formed by organic or inorganic substances.
[0106] R is a hydrogen atom, a saturated straight-chain hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated straight-chain hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group or a derivative thereof. In formula (1), n is preferably 1.
[0107] As saturated-straight-chain hydrocarbon groups, methyl, ethyl, n-propyl or n-butyl groups may be listed without particular limitation. As saturated-branched hydrocarbon groups, isopropyl or tert-butyl groups may be listed without particular limitation. As saturated-cyclic hydrocarbon groups, cyclopentyl or cyclohexyl groups may be listed without particular limitation. As unsaturated-straight-chain hydrocarbon groups, vinyl or allyl groups may be listed without particular limitation. As unsaturated-branched hydrocarbon groups, isopropenyl or 3-butenyl groups may be listed without particular limitation. As unsaturated-cyclic hydrocarbon groups, cyclopentenyl, cyclohexenyl groups may be listed without particular limitation. As aromatic groups, phenyl or naphthyl groups may be listed without particular limitation.
[0108] In addition, examples of the derivative groups in R include a carboxyl group, a carboxylate group (-COO - ), at least one of the functional groups such as hydroxyl, amino and ammonium groups, is not particularly limited. In addition, the number of carbon atoms constituting the main chain of R is not particularly limited, and is preferably 20 or less, and more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R to the above range, the molecular weight of the phosphorus oxyacid group can be set to an appropriate range, which makes it easy to penetrate into the fiber raw material and can also increase the yield of fine cellulose fibers. It should be noted that when there are multiple Rs in formula (1) and when multiple substituents shown in the above formula (1) are introduced into the fine fibrous cellulose, the multiple Rs present can be optionally the same or different.
[0109] β b+It is a cation with a valence of 1 or more formed by an organic or inorganic substance. Examples of cations with a valence of 1 or more formed by an organic substance include organic onium ions. Examples of organic onium ions include organic ammonium ions and organic onium ions. Examples of organic ammonium ions include aliphatic ammonium ions and aromatic ammonium ions. Examples of organic onium ions include aliphatic phosphonium ions and aromatic phosphonium ions. Examples of cations with a valence of 1 or more formed by an inorganic substance include ions of alkali metals such as sodium, potassium or lithium; ions of divalent metals such as calcium or magnesium, hydrogen ions, ammonium ions, etc. It should be noted that in formula (1), there are multiple β b+ In the case of introducing multiple substituents represented by the above formula (1) into the microfibrous cellulose, the presence of multiple β b+ As a cation having a valence of more than 1, which is formed by an organic or inorganic substance, it is preferred that the cation containing β b+ The sodium or potassium ions are not particularly limited and are those which are easy to industrially utilize and do not easily turn yellow when the fiber raw material is heated.
[0110] More specifically, phosphoric acid groups (-PO3H2), salts of phosphoric acid groups, phosphite groups (phosphonic acid groups) (-PO2H2), and salts of phosphite groups (phosphonic acid groups) can be cited as the substituents derived from phosphorus oxyacid groups or phosphorus oxyacid groups. In addition, phosphorus oxyacid groups or substituents derived from phosphorus oxyacid groups can be groups condensed with phosphoric acid groups (e.g., pyrophosphate groups), groups condensed with phosphonic acid (e.g., polyphosphonic acid groups), phosphate groups (e.g., monomethyl phosphate groups, polyoxyethylene alkyl phosphate groups), phosphonic acid alkyl ester groups (e.g., methyl phosphonate groups), and the like.
[0111] In addition, the sulfonic group (sulfonic group or a substituent derived from the sulfonic group) is preferably a sulfur-containing oxyacid group (sulfur-containing oxyacid group or a substituent derived from the sulfur-containing oxyacid group), and is preferably, for example, a substituent represented by the following formula (2). Each fine fibrous cellulose may optionally have a plurality of substituents represented by the following formula (2) introduced therein. In this case, the plurality of substituents represented by the following formula (2) introduced therein may be the same or different.
[0112]
[0113] In the above structural formula, b and n are natural numbers, p is 0 or 1, and m is an arbitrary number (where 1=b×m). It should be noted that when n is 2 or more, the multiple ps present may be the same number or different numbers. b+It is a cation with a valency of one or more formed by an organic or inorganic substance. Examples of cations with a valency of one or more formed by an organic substance include organic onium ions. Examples of organic onium ions include organic ammonium ions and organic onium ions. Examples of organic ammonium ions include aliphatic ammonium ions and aromatic ammonium ions. Examples of organic onium ions include aliphatic phosphonium ions and aromatic phosphonium ions. Examples of cations with a valency of one or more formed by an inorganic substance include ions of alkali metals such as sodium, potassium or lithium; ions of divalent metals such as calcium or magnesium; hydrogen ions, ammonium ions, etc. It should be noted that when a plurality of substituents represented by the above formula (2) are introduced into the microfibrous cellulose, the presence of a plurality of β b+ As a cation having a valence of more than 1, which is formed by an organic or inorganic substance, it is preferred that the cation containing β b+ The sodium or potassium ions are not particularly limited and are those which are easy to industrially utilize and do not easily turn yellow when the fiber raw material is heated.
[0114] The amount of anionic groups introduced into the fine fibrous cellulose can be measured, for example, by neutralization titration. In the measurement by neutralization titration, the amount introduced is measured by adding a base such as an aqueous sodium hydroxide solution to the obtained fine fibrous cellulose slurry and determining the change in pH.
[0115] Figure 1 This is a graph showing the relationship between the amount of NaOH added dropwise to a slurry containing fine fibrous cellulose having phosphorus oxyacid groups and pH. The amount of phosphorus oxyacid groups introduced into the fine fibrous cellulose is measured, for example, as follows.
[0116] First, a slurry containing fine fibrous cellulose is treated with a strongly acidic ion exchange resin. It should be noted that, if necessary, the object to be measured may be subjected to a defibration treatment similar to the defibration treatment step described below before the treatment with the strongly acidic ion exchange resin.
[0117] Next, while adding sodium hydroxide aqueous solution, the pH change was observed to obtain Figure 1 The titration curve is as shown in the upper part of Figure 1 In the titration curve shown in the upper part of the graph, the measured pH is plotted against the amount of base added. Figure 1In the titration curve shown in the lower part of , the increment (differential value) of pH is plotted for the amount of alkali added (1 / mmol). In this neutralization titration, in the curve obtained by plotting the measured pH for the amount of alkali added, two points where the increment (differential value of pH relative to the amount of alkali added) reaches a maximum are confirmed. The maximum point of the increment obtained first by adding alkali among them is called the first end point, and the maximum point of the increment obtained subsequently is called the second end point. The amount of alkali required from the start of titration to the first end point is equal to the first dissociated acid amount of microfibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the second dissociated acid amount of microfibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total dissociated acid amount of microfibrous cellulose contained in the slurry used for titration. In addition, the value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the titration object slurry becomes the phosphorus oxygen acid group introduction amount (mmol / g). It should be noted that when simply referred to as the amount of phosphorus oxyacid groups introduced (or the amount of phosphorus oxyacid groups), this refers to the amount of the first dissociated acid.
[0118] It should be noted that in Figure 1 In, the region from the start of titration to the first terminal is called the first region, and the region from the first terminal to the second terminal is called the second region. For example, when the phosphorus oxyacid group is a phosphate group and the phosphate group is condensed, the weakly acidic group amount (also referred to as the second dissociated acid amount in this manual) in the phosphorus oxyacid group is reduced, and the amount of alkali required in the second region decreases compared to the amount of alkali required in the first region. On the other hand, the strongly acidic group amount (also referred to as the first dissociated acid amount in this manual) in the phosphorus oxyacid group is consistent with the amount of phosphorus atoms regardless of whether it is condensed. In addition, when the phosphorus oxyacid group is a phosphite group, there is no weakly acidic group in the phosphorus oxyacid group, therefore, there is also a situation where the amount of alkali required in the second region decreases or the amount of alkali required in the second region becomes zero. In this case, in the titration curve, the point where the increment of pH becomes extremely large becomes one.
[0119] It should be noted that, since the denominator represents the mass of the acid-type microfibrous cellulose, the above-mentioned phosphorus oxyacid group introduction amount (mmol / g) represents the amount of phosphorus oxyacid groups possessed by the acid-type microfibrous cellulose (hereinafter referred to as the phosphorus oxyacid group amount (acid-type)). On the other hand, when the counter ion of the phosphorus oxyacid group is replaced by an arbitrary cation C in a manner that becomes charge equivalent, the amount of phosphorus oxyacid groups possessed by the microfibrous cellulose with the cation C as the counter ion (hereinafter referred to as the phosphorus oxyacid group amount (C-type)) can be obtained by converting the denominator into the mass of the microfibrous cellulose with the cation C as the counter ion.
[0120] That is, calculation is performed by the following calculation formula.
[0121] Phosphorus oxyacid group content (C type) = Phosphorus oxyacid group content (acid type) / {1 + (W-1) × A / 1000}
[0122] A [mmol / g]: Total anion amount derived from phosphorus oxyacid groups possessed by fine fibrous cellulose (total dissociated acid amount of phosphorus oxyacid groups)
[0123] W: The formula weight per valence of the cation C (e.g., 23 for Na, 9 for Al)
[0124] In the determination of the amount of anionic groups based on titration, when the amount of one drop of sodium hydroxide aqueous solution is too much or the titration interval is too short, the amount of anionic groups sometimes becomes lower than the original amount, and the correct numerical value cannot be obtained. As appropriate amount of addition and titration interval, it is expected that, for example, 10 to 50 μL of 0.1N sodium hydroxide aqueous solution are titrated in 5 to 30 seconds. In addition, in order to eliminate the influence of carbon dioxide dissolved in the slurry containing fine fibrous cellulose, it is expected that, for example, from 15 minutes before the start of titration until the end of titration, inert gas such as nitrogen is blown into the slurry for measurement.
[0125] In addition, the amount of sulfonic groups introduced into the microfibrous cellulose can be calculated by measuring the amount of sulfur in a sample obtained by freeze-drying and pulverizing a slurry containing microfibrous cellulose. Specifically, the slurry containing microfibrous cellulose is freeze-dried and pulverized, and the sample obtained is decomposed by pressurized heating using nitric acid in a sealed container, and then appropriately diluted and the amount of sulfur is measured by ICP-OES. The value calculated by dividing by the absolute dry mass of the tested microfibrous cellulose is taken as the amount of sulfonic groups in the microfibrous cellulose (unit: mmol / g).
[0126] The amount of xanthate groups introduced into fine fibrous cellulose can be measured by the Bredee method using the following method. First, add 40 mL of saturated ammonium chloride solution to 1.5 parts by mass (absolute dry mass) of fine fibrous cellulose, mix thoroughly while crushing the sample with a glass rod, and filter with GFP filter paper (GS-25 manufactured by ADVANTEC) after standing for about 15 minutes, and wash thoroughly with saturated ammonium chloride solution. Next, put the sample together with the GFP filter paper into a 500 mL high volume cup, add 50 mL of 0.5 M sodium hydroxide solution (5°C) and stir, and stand for 15 minutes. Add phenolphthalein solution until the solution turns pink, then add 1.5 M acetic acid, and the point where the solution turns from pink to colorless is used as the neutralization point. After neutralization, add 250 mL of distilled water and stir thoroughly, and use a full-capacity pipette to add 10 mL of 1.5 M acetic acid and 10 mL of 0.05 mol / L iodine solution. Then, the solution was titrated with a 0.05 mol / L sodium thiosulfate solution, and the xanthate base amount was calculated from the titration amount of sodium thiosulfate and the absolute dry mass of the fine fibrous cellulose by the following formula.
[0127] Xanthate base amount (mmol / g) = (0.05×10×2-0.05×sodium thiosulfate titration (mL)) / 1000 / absolute dry mass of microfibrous cellulose (g)
[0128] In the present embodiment, the fine fibrous cellulose preferably has a urea group. In the present specification, the urea group is preferably a group represented by the following structural formula.
[0129]
[0130] In the above structural formula, R is a hydrogen atom, a saturated straight-chain hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated straight-chain hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group or a derivative thereof. Among them, R is particularly preferably a hydrogen atom.
[0131] The amount of urea groups introduced into the microfibrous cellulose is preferably 0.001 mmol / g or more. In addition, the amount of urea groups introduced into the microfibrous cellulose is preferably 0.08 mmol / g or less, more preferably 0.04 mmol / g or less, and further preferably 0.02 mmol / g or less. Here, the amount of urea groups introduced into the microfibrous cellulose can be calculated by performing a trace nitrogen analysis on a sample obtained by freeze-drying and pulverizing a slurry containing microfibrous cellulose. The amount of urea groups introduced per unit mass of microfibrous cellulose (mmol / g) can be calculated by dividing the nitrogen content (g / g) per unit mass of microfibrous cellulose obtained in the trace nitrogen analysis by the atomic weight of nitrogen.
[0132] In this embodiment, the fine fibrous cellulose is prepared into a 0.1 mass % aqueous dispersion, and the nanofiber yield is calculated using the following formula. The nanofiber yield is preferably 95 mass % or more, and more preferably 96 mass % or more. It should be noted that the nanofiber yield may be 100 mass %.
[0133] Nanofiber yield [mass %] = C / 0.1×100
[0134] Here, C is the concentration of fine fibrous cellulose contained in the supernatant obtained when an aqueous dispersion having a fine fibrous cellulose concentration of 0.1% by mass is centrifuged under the conditions of 12000 G for 10 minutes.
[0135] In addition, in the present embodiment, when the fine fibrous cellulose is made into an aqueous dispersion with a concentration of 0.2% by mass, the haze of the aqueous dispersion is preferably 5.0% or less, more preferably 4.0% or less, and further preferably 3.0% or less. It should be noted that the haze of the aqueous dispersion can be 0%. If the haze of the aqueous dispersion with a concentration of 0.2% by mass is within the above range, it can be determined that the dispersion is transparent. Here, the haze of the aqueous dispersion is a value measured using a haze meter and a liquid glass cuvette with an optical path length of 1 cm in accordance with JIS K 7136:2000. It should be noted that the zero point determination is performed using the ion exchange water contained in the glass cuvette. In addition, the dispersion to be measured is left to stand for 24 hours at 23°C and a relative humidity of 50% before the measurement, and the liquid temperature of the dispersion is set to 23°C.
[0136] (Method for producing microfibrous cellulose)
[0137] The present invention relates to a method for producing fine fibrous cellulose. The method for producing fine fibrous cellulose of the present invention comprises: a step (A) of removing at least a part of substituents from fine fibrous cellulose having substituents and having a fiber width of 1000 nm or less; and a step (B) of uniformly dispersing the cellulose after the step (A). Here, the substituent possessed by the fine fibrous cellulose supplied to the step (A) is preferably an anionic group, more preferably a phosphorus oxyacid group or a substituent derived from a phosphorus oxyacid group. Furthermore, the fine fibrous cellulose supplied to the step (A) preferably has a urea group.
[0138] (Process (A))
[0139] Step (A) is a step of removing at least a portion of substituents from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less. First, a method for producing fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less (fine fibrous cellulose provided for step (A)) is described below.
[0140] <Fiber Raw Materials>
[0141] The fine fibrous cellulose provided in step (A) is produced from a fiber raw material containing cellulose. The fiber raw material containing cellulose is not particularly limited, and pulp is preferably used from the viewpoint of easy availability and low cost. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. The wood pulp is not particularly limited, and examples include chemical pulps such as broadleaf kraft pulp (LBKP), conifer kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), alkaline pulp (AP), unbleached kraft pulp (UKP), and oxygen bleached kraft pulp (OKP); semi-chemical pulps such as semi-chemical pulp (SCP) and chemical groundwood pulp (CGP); mechanical pulps such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP), etc. The non-wood pulp is not particularly limited, and examples include cotton pulps such as cotton lint and lint; and non-wood pulps such as hemp, straw, and bagasse. There are no particular limitations on deinked pulp, and examples thereof include deinked pulp made from waste paper as a raw material. The pulp of the present embodiment may be one of the above-mentioned pulps alone, or two or more of the above-mentioned pulps may be mixed and used. Among the above-mentioned pulps, from the viewpoint of easy availability, for example, wood pulp and deinked pulp are preferred. In addition, among wood pulps, from the viewpoint of a large cellulose ratio, a high yield of fine fibrous cellulose during defibration treatment, and the viewpoint of being able to obtain fine fibrous cellulose of long fibers with little decomposition of cellulose in the pulp and a large axial ratio, for example, chemical pulp is more preferred, and kraft pulp, sulfite pulp, and dissolving pulp are further preferred. It should be noted that if fine fibrous cellulose of long fibers with a large axial ratio is used, there is a tendency for the viscosity to increase.
[0142] As the fiber raw material containing cellulose, for example, cellulose contained in ascidian and bacterial cellulose produced by acetic acid bacteria can be used. In addition, fibers formed of linear nitrogen-containing polysaccharide polymers such as chitin and deacetylated chitosan can also be used instead of the fiber raw material containing cellulose.
[0143] <Phosphorus oxyacid group introduction step>
[0144] The fine fibrous cellulose supplied to step (A) has a substituent. Therefore, the manufacturing process of the fine fibrous cellulose supplied to step (A) preferably has a substituent introduction process, and more preferably has an anionic group introduction process. As an anionic group introduction process, for example, a phosphorus oxyacid group introduction process can be cited. The phosphorus oxyacid group introduction process is a process in which at least one compound selected from compounds capable of introducing phosphorus oxyacid groups (hereinafter also referred to as "compound A") acts on the fiber raw material containing cellulose by reacting with the hydroxyl group possessed by the fiber raw material containing cellulose. Through this process, fibers introduced with phosphorus oxyacid groups are obtained.
[0145] In the phosphorus oxyacid group introduction step according to the present embodiment, the reaction between the fiber raw material containing cellulose and the compound A is preferably performed in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B").
[0146] As an example of a method for causing compound A to act on a fiber raw material under the condition of coexistence with compound B, there can be cited a method of mixing compound A and compound B for a fiber raw material in a dry state, a wet state or a slurry state. Among these, from the aspect of high reaction uniformity, it is preferred to use a fiber raw material in a dry state or a wet state, and it is particularly preferred to use a fiber raw material in a dry state. The form of the fiber raw material is not particularly limited, and it is preferably, for example, cotton-like or flake-like. There can be cited a method of adding compound A and compound B to the fiber raw material in a powdered state or a solution obtained by dissolving in a solvent or heating to a melting point or above to melt it. Among these, from the aspect of high reaction uniformity, it is preferably added in a solution dissolved in a solvent, especially in a state of an aqueous solution. In addition, compound A and compound B can be added to the fiber raw material at the same time, can be added separately, or can be added in the form of a mixture. As a method for adding compound A and compound B, there is no particular limitation. When compound A and compound B are in a solution state, the fiber raw material can be immersed in the solution, and then taken out after absorbing the liquid, or the solution can be dripped into the fiber raw material. In addition, necessary amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material and then removed by squeezing or filtering.
[0147] As the compound A used in the present embodiment, any compound having a phosphorus atom and capable of forming an ester bond with cellulose may be used, and examples thereof include phosphoric acid or its salts, phosphorous acid or its salts, dehydrated condensed phosphoric acid or its salts, anhydrous phosphoric acid (phosphorus pentoxide), etc., without particular limitation. As phosphoric acid, phosphoric acid of various purities may be used, and for example, 100% phosphoric acid (orthophosphoric acid) and 85% phosphoric acid may be used. As phosphorous acid, 99% phosphorous acid (phosphonic acid) may be listed. Dehydrated condensed phosphoric acid is obtained by condensing more than two molecules of phosphoric acid through a dehydration reaction, and examples thereof include pyrophosphoric acid and polyphosphoric acid. As phosphates, phosphites, and dehydrated condensed phosphates, examples thereof include lithium salts, sodium salts, potassium salts, ammonium salts, etc. of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and they may be set to various degrees of neutralization. Among these, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphate, ammonium salt of phosphate or phosphorous acid, sodium salt of phosphorous acid, potassium salt of phosphorous acid, ammonium salt of phosphorous acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate or phosphorous acid, sodium phosphite are more preferred, from the viewpoint of high efficiency of introduction of phosphate groups, easy to further improve the defibration efficiency in the defibration process described later, low cost and easy industrial application.
[0148] The amount of compound A added to the fiber raw material is not particularly limited. For example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (absolute dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and further preferably 2% by mass or more and 30% by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material to within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to less than the above upper limit, a balance between the effect of improving the yield and the cost can be achieved.
[0149] As described above, the compound B used in the present embodiment is at least one selected from urea and its derivatives. Examples of the compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea.
[0150] From the viewpoint of improving the uniformity of the reaction, the compound B is preferably used as an aqueous solution. From the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both the compound A and the compound B are dissolved.
[0151] The amount of compound B added relative to the fiber raw material (absolute dry mass) is not particularly limited, and is, for example, preferably 1 mass % or more and 500 mass % or less, more preferably 10 mass % or more and 400 mass % or less, and further preferably 100 mass % or more and 350 mass % or less.
[0152] In the reaction of the fiber raw material containing cellulose and compound A, in addition to compound B, amides or amines may be included in the reaction system. Amides include, for example, formamide, dimethylformamide, acetamide, dimethylacetamide, etc. Amines include, for example, methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, hexamethylenediamine, etc. Among these, it is known that triethylamine acts as a good reaction catalyst.
[0153] In the phosphorus oxyacid group introduction step, it is preferred that after adding or mixing compound A and compound B to the fiber raw material, the fiber raw material is subjected to a heat treatment. As the heat treatment temperature, it is preferred to select a temperature that can suppress the thermal decomposition and hydrolysis reaction of the fiber and effectively introduce the phosphorus oxyacid group. The heat treatment temperature is, for example, preferably 50°C or more and 300°C or less, more preferably 100°C or more and 250°C or less, and further preferably 130°C or more and 200°C or less. In addition, the heat treatment can utilize machines having various heat media, such as hot air drying devices, stirring drying devices, rotary drying devices, disc drying devices, roller-type heating devices, plate-type heating devices, fluidized bed drying devices, belt-type drying devices, filter drying devices, vibration fluidized drying devices, airflow drying devices, reduced pressure drying devices, infrared heating devices, far infrared heating devices, microwave heating devices, and high-frequency drying devices.
[0154] In the heat treatment described in the present embodiment, the following methods can be used, for example: a method of adding compound A to a thin sheet of fiber raw material by impregnation or the like, and then heating; a method of heating the fiber raw material and compound A while kneading or stirring the fiber raw material with a kneader or the like. In this way, it is possible to suppress the concentration unevenness of compound A in the fiber raw material, and more uniformly introduce phosphorus oxyacid groups to the surface of the cellulose fiber contained in the fiber raw material. It is believed that the reason for this is that when water molecules move to the surface of the fiber raw material during drying, the dissolved compound A is attracted by the water molecules due to the surface tension, and it is possible to suppress the compound A from similarly moving to the surface of the fiber raw material (i.e., the occurrence of uneven concentration of compound A).
[0155] In addition, the heating device used in the heat treatment is preferably a device that can discharge the moisture retained by the slurry and the moisture generated by the dehydration condensation (phosphorylation) reaction of the hydroxyl groups contained in the cellulose and the like in the fiber raw material to the outside of the device system from time to time. As such a heating device, an oven with a blast mode, for example, can be cited. By discharging the moisture in the device system from time to time, the reverse reaction of the phosphorylation, i.e., the hydrolysis reaction of the phosphate bond, can be suppressed, and on this basis, the acid hydrolysis of the sugar chain in the fiber can also be suppressed. Therefore, a microfibrous cellulose with a high axial ratio can be obtained.
[0156] The time of the heat treatment is preferably, for example, 1 second or more and 300 minutes or less from the time when the water is substantially removed from the fiber raw material, more preferably 1 second or more and 1000 seconds or less, and further preferably 10 seconds or more and 800 seconds or less. In the present embodiment, by setting the heating temperature and the heating time to an appropriate range, the amount of phosphorus oxyacid groups introduced can be set to a preferred range.
[0157] The phosphorus oxyacid group introduction step may be performed at least once, and may be repeated twice or more. By performing the phosphorus oxyacid group introduction step twice or more, a large amount of phosphorus oxyacid groups can be introduced into the fiber raw material.
[0158] The amount of phosphorus oxyacid groups introduced in the phosphorus oxyacid group introduction step is preferably 0.60 mmol / g or more, more preferably 0.70 mmol / g or more, further preferably 0.80 mmol / g or more, further preferably 1.00 mmol / g or more, and particularly preferably 1.20 mmol / g or more relative to 1 g (mass) of the fiber raw material. In addition, the amount of phosphorus oxyacid groups introduced is preferably 5.20 mmol / g or less, more preferably 3.65 mmol / g or less, and further preferably 3.00 mmol / g or less relative to 1 g (mass) of the fiber raw material. It should be noted that the amount of phosphorus oxyacid groups introduced in the phosphorus oxyacid group introduction step within the above range means that the amount of substituents introduced into the fine fibrous cellulose supplied to step (A) is within the above range. By setting the amount of phosphorus oxyacid groups introduced within the above range, the amount of substituents introduced into the fine fibrous cellulose supplied to step (A) can be set within the above range, and as a result, it is easy to produce fine fibrous cellulose with a final fiber width of 10 nm or less. In addition, the transparency of a dispersion or a sheet containing finely fibrous cellulose can be more effectively improved.
[0159] <Sulfonic Group (Sulfur Oxygen Acid Group) Introduction Step>
[0160] The production process of fine fibrous cellulose in step (A) may include a sulfone group introduction step as an anionic group introduction step. The sulfone group introduction step can obtain cellulose fibers having sulfone groups (sulfone group-introduced fibers) by reacting hydroxyl groups of fiber raw materials including cellulose with sulfonic acid.
[0161] In the sulfonic group introduction step, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing a sulfonic group by reacting with a hydroxyl group possessed by a fiber raw material containing cellulose is used instead of compound A in the above-mentioned <phosphorus oxyacid group introduction step>. As compound C, any compound having a sulfur atom and capable of forming an ester bond with cellulose may be used, and examples thereof include sulfuric acid or its salts, sulfurous acid or its salts, and sulfuric acid amide, without particular limitation. As sulfuric acid, sulfuric acid of various purities may be used, and for example, 96% sulfuric acid (concentrated sulfuric acid) may be used. As sulfurous acid, 5% sulfurous acid water may be used. As sulfates or sulfites, lithium salts, sodium salts, potassium salts, ammonium salts, and the like of sulfates or sulfites may be used, and they may be set to various degrees of neutralization. As sulfuric acid amide, aminosulfonic acid and the like may be used. In the sulfonic group introduction step, it is preferred to use compound B in the above-mentioned <phosphorus oxyacid group introduction step> as well.
[0162] In the sulfonic group introduction step, it is preferred that the cellulose raw material is subjected to a heat treatment after mixing an aqueous solution containing sulfonic acid and urea and / or a urea derivative with the cellulose raw material. As the heat treatment temperature, it is preferred to select a temperature that can effectively introduce the sulfonic group while suppressing thermal decomposition and hydrolysis reaction of the fiber. The heat treatment temperature is preferably 100° C. or higher, more preferably 120° C. or higher, and further preferably 150° C. or higher. In addition, the heat treatment temperature is preferably 300° C. or lower, more preferably 250° C. or lower, and further preferably 200° C. or lower.
[0163] In the heat treatment step, it is preferred to heat until there is substantially no water. Therefore, the heat treatment time varies due to the amount of water contained in the cellulose raw material, sulfonic acid, and the amount of the aqueous solution containing urea and / or urea derivatives added, and is preferably set to, for example, more than 10 seconds and less than 10,000 seconds. The heat treatment can utilize machines with various heat media, such as hot air drying devices, stirring drying devices, rotary drying devices, disc drying devices, roller-type heating devices, plate-type heating devices, fluidized bed drying devices, belt-type drying devices, filter drying devices, vibration fluidized drying devices, airflow drying devices, reduced pressure drying devices, infrared heating devices, far infrared heating devices, microwave heating devices, and high-frequency drying devices.
[0164] The amount of sulfonic groups introduced in the sulfonic group introduction step is preferably 0.60 mmol / g or more, more preferably 0.70 mmol / g or more, further preferably 0.80 mmol / g or more, further preferably 1.00 mmol / g or more, and particularly preferably 1.20 mmol / g or more relative to 1 g (mass) of the fiber raw material. In addition, the amount of sulfonic groups introduced is preferably 5.00 mmol / g or less, more preferably 3.00 mmol / g or less relative to 1 g (mass) of the fiber raw material. It should be noted that the amount of sulfonic groups introduced in the sulfonic group introduction step is within the above range, which means that the amount of substituents introduced into the fine fibrous cellulose supplied to the step (A) is within the above range. By setting the amount of sulfonic groups introduced within the above range, the amount of substituents introduced into the fine fibrous cellulose supplied to the step (A) can be set within the above range, and as a result, it is easy to produce fine fibrous cellulose with a fiber width of 10 nm or less. In addition, the transparency of the dispersion and sheet containing the fine fibrous cellulose can be more effectively improved.
[0165] <Xanthate base introduction step>
[0166] The process for producing fine fibrous cellulose in step (A) may include a xanthate group introduction step as an anionic group introduction step. The xanthate group introduction step can obtain cellulose fibers having a xanthate group (xanthate group-introduced fibers) by replacing a hydroxyl group of a fiber raw material containing cellulose with a xanthate group represented by the following formula (2).
[0167] -OCSS - M + ……(2)
[0168] Here, M + It is at least one selected from hydrogen ions, monovalent metal ions, ammonium ions, and aliphatic or aromatic ammonium ions.
[0169] In the xanthate group introduction step, first, an alkali treatment is performed in which the fiber raw material containing cellulose is treated with an alkali solution to obtain alkali cellulose. As the alkali solution, an alkali metal hydroxide aqueous solution, an alkaline earth metal hydroxide aqueous solution, and the like can be cited. Among them, the alkali solution is preferably an alkali metal hydroxide aqueous solution such as sodium hydroxide and potassium hydroxide, and particularly preferably an aqueous sodium hydroxide solution. When the alkali solution is an alkali metal hydroxide aqueous solution, the alkali metal hydroxide concentration in the alkali metal hydroxide aqueous solution is preferably 4% by mass or more, and more preferably 5% by mass or more. In addition, the alkali metal hydroxide concentration in the alkali metal hydroxide aqueous solution is preferably 9% by mass or less. By setting the alkali metal hydroxide concentration to above the above lower limit, the cellulose can be fully mercerized, and the amount of by-products generated during the subsequent xanthate saltization can be reduced, and as a result, the yield of the xanthate group-introduced fiber can be increased. As a result, the defibration treatment described later can be performed more effectively. In addition, by setting the alkali metal hydroxide concentration to below the above upper limit, the cellulose can be mercerized, and the alkali metal hydroxide aqueous solution is inhibited from penetrating into the crystallization region of the cellulose, so that the cellulose I type crystal structure is easily maintained, and the yield of the fine fibrous cellulose can be further increased.
[0170] The time of above-mentioned alkali treatment is preferably more than 30 minutes, more preferably more than 1 hour. In addition, the time of alkali treatment is preferably less than 6 hours, more preferably less than 5 hours. By making the time of alkali treatment within the above-mentioned range, final yield can be improved, productivity can be improved.
[0171] The alkali cellulose obtained by the above-mentioned alkali treatment is preferably subjected to solid-liquid separation to remove the aqueous solution as much as possible in advance. In this way, the water content during the subsequent xanthate treatment can be reduced, and the reaction can be promoted. As a method for solid-liquid separation, general dehydration methods such as centrifugal separation and filtration can be used. It should be noted that the concentration of the alkali metal hydroxide contained in the alkali cellulose after solid-liquid separation is preferably 3% by mass or more and 8% by mass or less relative to the total mass of the alkali cellulose after solid-liquid separation.
[0172] In the xanthate group introduction step, the xanthate treatment step is performed after the alkali treatment. In the xanthate treatment step, carbon disulfide (CS2) is reacted with alkali cellulose to convert (-O - Na + )Based on (-OCSS - Na + ) groups to obtain xanthate group-introduced fibers. It should be noted that in the above, the metal ions introduced into the alkali cellulose are typically represented by Na + , the same reaction will occur with other alkali metal ions.
[0173] In the xanthate treatment, it is preferred to supply carbon disulfide in an amount of 10% by mass or more relative to the absolute dry mass of cellulose in the alkali cellulose. In addition, in the xanthate treatment, the contact time between carbon disulfide and alkali cellulose is preferably 30 minutes or more, more preferably 1 hour or more. By bringing carbon disulfide into contact with the alkali cellulose, xanthate is rapidly carried out, but it takes time for carbon disulfide to penetrate into the interior of the alkali cellulose, so it is preferred to set the reaction time to the above range. On the other hand, as long as the contact time between carbon disulfide and alkali cellulose is 6 hours or less, it can fully penetrate even the agglomerates of the dehydrated alkali cellulose, and the xanthate treatment that can react can be substantially completed.
[0174] The reaction temperature in the xanthate treatment is preferably 46° C. or lower. By setting the reaction temperature within the above range, decomposition of alkali cellulose can be easily suppressed. In addition, by setting the reaction temperature within the above range, the reaction can be easily uniformly performed, thereby suppressing the generation of by-products and further suppressing the removal of the generated xanthate groups.
[0175] The amount of xanthate group introduced in the xanthate group introduction step is preferably 0.60 mmol / g or more, more preferably 0.70 mmol / g or more, further preferably 0.80 mmol / g or more, further preferably 1.00 mmol / g or more, and particularly preferably 1.20 mmol / g or more relative to 1 g (mass) of the fiber raw material. In addition, the amount of xanthate group introduced is preferably 5.00 mmol / g or less, and more preferably 3.00 mmol / g or less relative to 1 g (mass) of the fiber raw material. It should be noted that the amount of xanthate group introduced in the xanthate group introduction step is within the above range, which means that the amount of substituent introduced into the fine fibrous cellulose supplied to the step (A) is within the above range. By setting the amount of xanthate group introduced within the above range, the amount of substituent introduced into the fine fibrous cellulose supplied to the step (A) can be set within the above range, and as a result, it is easy to produce fine fibrous cellulose with a fiber width of 10 nm or less. In addition, the transparency of the dispersion and sheet containing the fine fibrous cellulose can be more effectively improved.
[0176] <Cleaning process>
[0177] In the production process of fine fibrous cellulose provided in step (A), the anionic group-introduced fibers may be subjected to a washing process as needed. The washing process is performed by washing the anionic group-introduced fibers with, for example, water or an organic solvent. In addition, the washing process may be performed after each of the steps described below, and the number of washings performed in each washing process is not particularly limited.
[0178] <Alkali treatment step>
[0179] In the production process of fine fibrous cellulose in step (A), the fiber raw material may be subjected to an alkali treatment between the anionic group introduction step and the fibrillation treatment step described later. The method of the alkali treatment is not particularly limited, and examples thereof include a method of introducing anionic groups into the fibers and immersing them in an alkali solution.
[0180] The alkali compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkali compound or an organic alkali compound. In the present embodiment, from the aspect of high versatility, it is preferred that, for example, sodium hydroxide or potassium hydroxide is used as the alkali compound. In addition, the solvent contained in the alkaline solution may be any one of water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably water or a polar solvent containing a polar organic solvent such as an alcohol as an example, and more preferably an aqueous solvent containing at least water. As the alkaline solution, from the aspect of high versatility, it is preferably, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution.
[0181] The temperature of the alkaline solution in the alkali treatment step is not particularly limited, and is, for example, preferably 5° C. or more and 80° C. or less, and more preferably 10° C. or more and 60° C. or less. The immersion time of the anionic group-introduced fiber in the alkaline solution in the alkali treatment step is not particularly limited, and is, for example, preferably 5 minutes or more and 30 minutes or less, and more preferably 10 minutes or more and 20 minutes or less. The amount of the alkaline solution used in the alkali treatment is not particularly limited, and is, for example, preferably 100% by mass or more and 100,000% by mass or less, and more preferably 1,000% by mass or more and 10,000% by mass or less, relative to the absolute dry mass of the anionic group-introduced fiber.
[0182] In order to reduce the amount of alkaline solution used in the alkali treatment step, the anionic group-introduced fibers may be washed with water or an organic solvent after the anionic group-introducing step and before the alkali treatment step. After the alkali treatment step and before the fiberizing step, it is preferred to wash the anionic group-introduced fibers that have been subjected to alkali treatment with water or an organic solvent from the viewpoint of improving the handling properties.
[0183] <Acid treatment process>
[0184] In the production process of fine fibrous cellulose in step (A), the fiber raw material may be subjected to an acid treatment between the anionic group introduction step and the fibrillation step described below. For example, the anionic group introduction step, acid treatment, alkali treatment, and fibrillation treatment may be performed in this order.
[0185] There is no particular limitation on the method of acid treatment, and examples thereof include a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, and for example, it is preferably 10% by mass or less, and more preferably 5% by mass or less. In addition, the pH of the acidic solution used is not particularly limited, and for example, it is preferably 0 or more and 4 or less, and more preferably 1 or more and 3 or less. As the acid contained in the acidic solution, for example, inorganic acids, sulfonic acids, carboxylic acids, etc. can be used. As inorganic acids, for example, sulfuric acid, nitric acid, hydrochloric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, boric acid, etc. can be listed. As sulfonic acids, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, trifluoromethanesulfonic acid, etc. can be listed. As carboxylic acids, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, tartaric acid, etc. can be listed. Among these, hydrochloric acid or sulfuric acid is particularly preferably used.
[0186] The temperature of the acid solution in the acid treatment is not particularly limited, and is preferably, for example, 5° C. or higher and 100° C. or lower, and more preferably 20° C. or higher and 90° C. or lower. The immersion time in the acid solution in the acid treatment is not particularly limited, and is preferably, for example, 5 minutes or higher and 120 minutes or lower, and more preferably 10 minutes or higher and 60 minutes or lower. The amount of the acid solution used in the acid treatment is not particularly limited, and is preferably, for example, 100% by mass or higher and 100,000% by mass or lower, and more preferably 1,000% by mass or higher and 10,000% by mass or lower, relative to the absolute dry mass of the fiber raw material.
[0187] <Nitrogen Removal Treatment>
[0188] The process for producing fine fibrous cellulose in step (A) may further include a step for reducing the amount of nitrogen introduced into the fibrous cellulose and the amount of nitrogen present in the system (nitrogen removal treatment step). By reducing the amount of nitrogen, fine fibrous cellulose with further suppressed coloration can be obtained. The nitrogen removal treatment step may be provided after the uniform dispersion treatment step in step (B) described later, but is preferably provided before the uniform dispersion treatment step in step (B) described later. In addition, it is preferably provided before the defibration treatment step in step (A) described later.
[0189] In the nitrogen removal treatment step, the pH of the slurry containing the anionic group-introduced fibers is preferably adjusted to 10 or more, and a heat treatment is performed. In the heat treatment, the liquid temperature of the slurry is preferably set to 50° C. or more and 100° C. or less, and the heating time is preferably set to 15 minutes or more and 180 minutes or less. When adjusting the pH of the slurry containing the anionic group-introduced fibers, it is preferred to add an alkali compound that can be used in the above-mentioned alkali treatment step to the slurry.
[0190] After the nitrogen removal treatment step, the anionic group-introduced fiber may be subjected to a washing step as needed. The washing step may be performed by, for example, washing the anionic group-introduced fiber with water or an organic solvent. In addition, the number of washings performed in each washing step is not particularly limited.
[0191] <Fiberization>
[0192] The manufacturing process of the fine fibrous cellulose provided in step (A) includes a fibrillation treatment process. Thus, a fine fibrous cellulose having a substituent and a fiber width of 1000nm or less can be obtained. In the fibrillation treatment process, for example, a fibrillation treatment device can be used. The fibrillation treatment device is not particularly limited, and for example, a high-speed fibrillator, a grinder (stone mill type crusher), a high-pressure homogenizer, an ultra-high pressure homogenizer, a high-pressure impact crusher, a ball mill, a bead mill, a disc refiner, a conical refiner, a twin-screw mixer, a vibration mill, a homogenizer under high-speed rotation, an ultrasonic disperser or a beater, etc. can be used. Among the above-mentioned fibrillation treatment devices, it is more preferable to use a high-speed fibrillator, a high-pressure homogenizer, and an ultra-high pressure homogenizer with less impact of the pulverizing medium and less risk of contamination.
[0193] The processing conditions in the defibration process are not particularly limited. When using, for example, a high-pressure homogenizer, the pressure during processing is preferably above 1 MPa and below 350 MPa, more preferably above 10 MPa and below 300 MPa, and further preferably above 50 MPa and below 250 MPa.
[0194] In the fiber disintegration treatment process, it is preferred that, for example, anionic groups are introduced into the fiber and diluted by using a dispersion medium to form a slurry. As a dispersion medium, one or more organic solvents selected from water and polar organic solvents can be used. As polar organic solvents, there are no particular restrictions, and preferably, for example, alcohols, polyols, ketones, ethers, esters, aprotic polar solvents, etc. are used. As alcohols, for example, methanol, ethanol, isopropanol, n-butanol, isobutanol, etc. can be listed. As polyols, for example, ethylene glycol, propylene glycol, glycerol, etc. can be listed. As ketones, acetone, methyl ethyl ketone (MEK), etc. can be listed. As ethers, for example, diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-butyl ether, propylene glycol monomethyl ether, etc. can be listed. As esters, for example, ethyl acetate, butyl acetate, etc. can be listed. Examples of the aprotic polar solvent include dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidone (NMP).
[0195] The solid content concentration of the fine fibrous cellulose during the fibrillation treatment can be appropriately set. In addition, the slurry obtained by dispersing the anionic group-introduced fibers in the dispersion medium may contain solid components other than the anionic group-introduced fibers, such as urea having hydrogen bonding properties.
[0196] The fiber width of the fine fibrous cellulose after the fibrillation treatment in step (A) is preferably 1 to 50 nm, more preferably 1 to 25 nm, further preferably 1 to 15 nm, particularly preferably 1 to 10 nm.
[0197] In addition, when the fine fibrous cellulose supplied to step (A) is made into an aqueous dispersion with a concentration of 0.1% by mass to calculate the nanofiber yield, the nanofiber yield is preferably 90% by mass or more, more preferably 93% by mass or more, and further preferably 96% by mass or more. It should be noted that the nanofiber yield can be 100% by mass. Here, the nanofiber yield is the following value: using a cooling high-speed centrifuge (KOKUSAN, H-2000B), a fine fibrous cellulose dispersion with a concentration of 0.1% by mass is centrifuged under the conditions of 12000G and 10 minutes, and the cellulose concentration of the obtained supernatant is measured according to the following formula.
[0198] Nanofiber yield (mass %) = cellulose concentration in supernatant (mass %) / 0.1 × 100
[0199] Furthermore, when the fine fibrous cellulose supplied to step (A) is made into an aqueous dispersion with a concentration of 0.2% by mass, the haze of the aqueous dispersion is preferably 10% or less, more preferably 5.0% or less, and further preferably 3.0% or less. It should be noted that the haze of the aqueous dispersion can be 0%. Here, the haze of the aqueous dispersion of fine fibrous cellulose is a value measured using a haze meter (manufactured by Murakami Color Research Institute, HM-150) in accordance with JIS K 7136:2000. During the measurement, a liquid glass cuvette with a light path length of 1 cm (manufactured by Fujiwara Manufacturing Co., Ltd., MG-40, backlight path) is used. It should be noted that the zero point measurement is performed using the ion exchange water contained in the glass cuvette, and the dispersion as the measurement object is left to stand for 24 hours at 23°C and a relative humidity of 50% before the measurement, and the liquid temperature of the dispersion is set to 23°C.
[0200] By setting the fiber width of the fine fibrous cellulose supplied to step (A), the nanofiber yield of the fine fibrous cellulose dispersion, and the haze within the above ranges, the transparency of the fine fibrous cellulose obtained through step (B) when made into a slurry or a sheet can be more effectively improved.
[0201] <Substituent Removal Treatment>
[0202] The method for producing fine fibrous cellulose of the present embodiment includes a step (A) of removing at least a part of substituents from fine fibrous cellulose having substituents and a fiber width of 1000 nm or less. In this specification, the step of removing at least a part of substituents from fine fibrous cellulose is also referred to as a substituent removal treatment step.
[0203] As the substituent removal treatment process, there can be listed: a process of heating the microfibrous cellulose having a substituent and a fiber width of less than 1000nm, a process of performing an enzyme treatment, a process of performing an acid treatment, a process of performing an alkali treatment, etc. They can be performed alone or in combination. Among them, the substituent removal treatment process is preferably a process of performing a heat treatment or a process of performing an enzyme treatment. By undergoing the above-mentioned treatment process, at least a portion of the substituent is removed from the microfibrous cellulose having a substituent and a fiber width of less than 1000nm, a microfibrous cellulose having a substituent introduction amount of less than 0.5mmol / g can be obtained.
[0204] The substituent removal treatment process is preferably carried out in a slurry state. That is, the substituent removal treatment process is preferably a process of heating a slurry containing microfibrous cellulose having a substituent and a fiber width of less than 1000nm, a process of performing an enzyme treatment, a process of performing an acid treatment, a process of performing an alkali treatment, etc. By implementing the substituent removal treatment process in a slurry state, it is possible to prevent the residue of coloring substances, added or generated acids, alkalis, salts, etc. generated by heating during the substituent removal treatment. Thus, it is possible to suppress the coloring when the microfibrous cellulose obtained after step (B) is made into a slurry or a sheet. In addition, when a removal treatment is performed for the salt derived from the substituent removed after the substituent removal treatment, the removal efficiency of the salt can also be improved.
[0205] When a slurry containing microfibrous cellulose having a substituent and a fiber width of 1000 nm or less is subjected to a substituent removal treatment, the concentration of the microfibrous cellulose in the slurry is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and further preferably 0.2% by mass or more. In addition, the concentration of the microfibrous cellulose in the slurry is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less. By setting the concentration of the microfibrous cellulose in the slurry within the above range, the substituent removal treatment can be performed more efficiently. Furthermore, by setting the concentration of the microfibrous cellulose in the slurry within the above range, the residues of coloring substances, added or generated acids, alkalis, salts, etc. generated by heating during the substituent removal treatment can be prevented. Thus, the coloring of the microfibrous cellulose obtained by the step (B) when it is made into a slurry or a sheet can be suppressed. In addition, when the salt removal treatment of the substituent removed after the substituent removal treatment is performed, the removal efficiency of the salt can also be improved.
[0206] When the substituent removal treatment step is a step of heat-treating the fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, the heating temperature in the heat treatment step is preferably 40°C or higher, more preferably 50°C or higher, and even more preferably 60°C or higher. In addition, the heating temperature in the heat treatment step is preferably 250°C or lower, more preferably 230°C or lower, and even more preferably 200°C or lower. Among them, when the substituent possessed by the fine fibrous cellulose subjected to the substituent removal treatment step is a phosphorus oxyacid group or a sulfonic group, the heating temperature in the heat treatment step is preferably 80°C or higher, more preferably 100°C or higher, and even more preferably 120°C or higher.
[0207] When the substituent removal treatment process is a heat treatment process, as a heating device that can be used in the heat treatment process, it is not particularly limited, and hot air heating device, steam heating device, electric heating device, hydrothermal heating device, fire heating device, infrared heating device, far infrared heating device, microwave heating device, high frequency heating device, stirring drying device, rotary drying device, disc drying device, roller type heating device, plate type heating device, fluidized bed drying device, belt type drying device, filter drying device, vibration flow drying device, airflow drying device, reduced pressure drying device can be used. From the viewpoint of preventing evaporation, heating is preferably carried out in a closed system, and then from the viewpoint of improving the heating temperature, it is preferably carried out in a pressure resistance device and a container. Heat treatment can be batch treatment, batch continuous treatment, or continuous treatment.
[0208] When the substituent removal treatment step is a step of enzymatically treating the microfibrous cellulose having a substituent and a fiber width of 1000 nm or less, it is preferred to use phosphohydrolase, sulfohydrolase or the like in accordance with the type of the substituent in the enzymatic treatment step.
[0209] In the enzyme treatment step, it is preferred to add an enzyme so that the enzyme activity relative to 1 g of the fine fibrous cellulose becomes 0.1 nkat or more, more preferably 1.0 nkat or more, and further preferably 10 nkat or more. In addition, it is preferred to add an enzyme so that the enzyme activity relative to 1 g of the fine fibrous cellulose becomes 100,000 nkat or less, more preferably 50,000 nkat or less, and further preferably 10,000 nkat or less. After adding the enzyme to the fine fibrous cellulose dispersion (slurry), it is preferred to perform the treatment at a temperature of 0°C or more and less than 50°C for 1 minute or more and 100 hours or less.
[0210] After the enzyme reaction, a step of deactivating the enzyme may be provided. Examples of methods for deactivating the enzyme include: adding an acid component or an alkali component to the enzyme-treated slurry to deactivate the enzyme; and increasing the temperature of the enzyme-treated slurry to 90° C. or higher to deactivate the enzyme.
[0211] When the substituent removal treatment step is a step of acid-treating the fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, it is preferred that an acid compound that can be used in the above-mentioned acid treatment step is added to the slurry in the acid treatment step.
[0212] When the substituent removal treatment step is a step of subjecting the fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less to an alkali treatment, in the alkali treatment step, an alkali compound that can be used in the above alkali treatment step is preferably added to the slurry.
[0213] In the substituent removal treatment step, the substituent removal reaction is preferably carried out uniformly. In order to carry out the reaction uniformly, for example, the slurry containing fine fibrous cellulose may be stirred, or the specific surface area of the slurry may be increased. As a method of stirring the slurry, mechanical shearing may be applied from the outside, or self-stirring may be promoted by increasing the slurry feeding speed during the reaction.
[0214] In the substituent removal treatment step, spacer molecules can be added. The spacer molecules enter between adjacent microfibrillar celluloses and thus function as spacers for providing micro spaces between the microfibrillar celluloses. By adding such spacer molecules in the substituent removal treatment step, aggregation of the microfibrillar celluloses after the substituent removal treatment can be suppressed. Thereby, the transparency of the dispersion liquid and the sheet containing the microfibrillar celluloses can be improved more effectively.
[0215] The spacer molecules are preferably water-soluble organic compounds. Examples of the water-soluble organic compounds include sugars, water-soluble polymers, urea, etc. Specifically, trehalose, urea, polyethylene glycol (PEG), polyethylene oxide (PEO), carboxymethyl cellulose, polyvinyl alcohol (PVA), etc. can be cited. In addition, as the water-soluble organic compounds, methacrylic acid alkyl ester-acrylic acid copolymer, polyvinylpyrrolidone, sodium polyacrylate, propylene glycol, dipropylene glycol, polypropylene glycol, isopentyl glycol, hexylene glycol, 1,3-butanediol, polyacrylamide, xanthan gum, guar gum, tamarind gum, carrageenan, locust bean gum, quince seed, alginic acid, pullulan, carrageenan, pectin, cationized starch, raw starch, oxidized starch, etherified starch, esterified starch, starch such as amylose, glycerin, diglycerin, polyglycerin, hyaluronic acid, metal salts of hyaluronic acid can also be used.
[0216] In addition, as the spacer molecules, known pigments can be used. Examples include kaolin (including clay), calcium carbonate, titanium oxide, zinc oxide, amorphous silica (including colloidal silica), alumina, zeolite, sepiolite, montmorillonite, synthetic montmorillonite, magnesium silicate, magnesium carbonate, magnesium oxide, diatomaceous earth, styrene-based plastic pigments, hydrotalcite, urea resin-based plastic pigments, benzoguanamine-based plastic pigments, etc.
[0217] <pH adjustment step>
[0218] When the substituent removal treatment step is carried out in a slurry form, a step of adjusting the pH of the slurry containing the microfibrillar celluloses can be provided before the substituent removal treatment step. For example, when an anionic group is introduced into the cellulose fiber and the counter ion of the anionic group is Na + +, the slurry containing the defibrated microfibrillar celluloses shows weak alkalinity. If heated in this state, monosaccharides, which are one of the causes of coloring, may be generated due to the decomposition of cellulose. Therefore, it is preferable to adjust the pH of the slurry to 8 or less, more preferably to 6 or less. In addition, since monosaccharides may also be generated under acidic conditions, it is preferable to adjust the pH of the slurry to 3 or more, more preferably to 4 or more.
[0219] When the fine fibrous cellulose having a substituent is a fine fibrous cellulose having a phosphate group, it is preferred that the phosphorus of the phosphate group is in a state that is susceptible to nucleophilic attack from the viewpoint of improving the removal efficiency of the substituent. The state susceptible to nucleophilic attack is represented by cellulose-OP(=O)(-OH + )(-O-Na + ) is in a state where the degree of neutralization is 1. In order to achieve this state, the pH of the slurry is preferably adjusted to 3 or more and 8 or less, and more preferably the pH is adjusted to 4 or more and 6 or less.
[0220] The means for adjusting pH is not particularly limited. For example, an acid component and an alkali component can be added to the slurry containing fine fibrous cellulose. The acid component can be any one of an inorganic acid and an organic acid. As an inorganic acid, sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, etc. can be listed. As an organic acid, formic acid, acetic acid, citric acid, malic acid, lactic acid, adipic acid, sebacic acid, stearic acid, maleic acid, succinic acid, tartaric acid, fumaric acid, gluconic acid, etc. can be listed. The alkali component can be an inorganic alkali compound or an organic alkali compound. As an inorganic alkali compound, lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, lithium bicarbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, etc. can be listed. Examples of the organic base compound include ammonia, hydrazine, methylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, diaminoethane, diaminopropane, diaminobutane, diaminopentane, diaminohexane, cyclohexylamine, aniline, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, pyridine, and N,N-dimethyl-4-aminopyridine.
[0221] In addition, in the pH adjustment step, an ion exchange treatment may be performed to adjust the pH. When performing the ion exchange treatment, a strongly acidic cation exchange resin or a weakly acidic ion exchange resin may be used. By treating with an appropriate amount of the cation exchange resin for a sufficient time, a slurry containing fine fibrous cellulose at a target pH can be obtained. Furthermore, in the pH adjustment step, the addition of an acid component or an alkali component may be combined with the ion exchange treatment.
[0222] <Salt Removal Treatment>
[0223] It is preferred that a treatment for removing salts derived from the removed substituents is performed after the substituent removal treatment step. By removing salts derived from substituents, it is easy to obtain microfibrous cellulose that can suppress coloring. The means for removing salts derived from substituents is not particularly limited, and examples thereof include washing treatment. The washing treatment is performed by washing the microfibrous cellulose aggregated in the substituent removal treatment with, for example, water or an organic solvent. From the viewpoint of more effectively suppressing yellowing, the washing treatment is preferably performed by filtration dehydration, centrifugal dehydration, or centrifugal separation.
[0224] (Process (B))
[0225] The method for producing microfibrous cellulose of the present embodiment includes: a step (A) of removing at least a part of substituents from microfibrous cellulose having substituents and having a fiber width of 1000 nm or less; and a step (B) of performing a uniform dispersion treatment after step (A). The step (B) of performing a uniform dispersion treatment is a step of uniformly dispersing the microfibrous cellulose obtained after the substituent removal treatment of step (A). In step (A), at least a part of the microfibrous cellulose aggregates by subjecting the microfibrous cellulose to a substituent removal treatment. Step (B) is a step of uniformly dispersing the microfibrous cellulose aggregated in this way. The state in which the microfibrous cellulose is uniformly dispersed in step (B) means that the fiber width of the microfibrous cellulose is 10 nm or less. As described above, although the microfibrous cellulose obtained by the production method of the present embodiment has a low substituent introduction amount of less than 0.5 mmol / g, its fiber width is still 10 nm or less.
[0226] In the step (B) of uniform dispersion treatment, for example, a high-speed fiberizer, a grinder (stone mill type pulverizer), a high-pressure homogenizer, a high-pressure impact type pulverizer, a ball mill, a bead mill, a disc refiner, a cone refiner, a twin-screw mixer, a vibration mill, a homogenizer under high-speed rotation, an ultrasonic disperser or a beater can be used. Among the above-mentioned uniform dispersion treatment devices, a high-speed fiberizer and a high-pressure homogenizer are more preferably used.
[0227] The treatment conditions in the step (B) of uniform dispersion treatment are not particularly limited, and it is preferred to increase the maximum moving speed of the fine fibrous cellulose during treatment and the pressure during treatment. The circumferential speed of the high-speed fibrillator is preferably 20 m / sec or more, more preferably 25 m / sec or more, and further preferably 30 m / sec or more. Since the maximum moving speed of the fine fibrous cellulose during treatment and the pressure during treatment are increased compared to the high-speed fibrillator, a high-pressure homogenizer can be more preferably used. In the high-pressure homogenizer treatment, the pressure during treatment is preferably 1 MPa or more, more preferably 10 MPa or more, further preferably 50 MPa or more, and particularly preferably 100 MPa or more. In addition, in the high-pressure homogenizer treatment, the pressure during treatment is preferably 350 MPa or less, more preferably 300 MPa or less, and further preferably 250 MPa or less.
[0228] It should be noted that the above-mentioned spacer molecules can be newly added in step (B). In the uniform dispersion treatment step of step (B), by adding such spacer molecules, the uniform dispersion of the fine fibrous cellulose can be more smoothly performed. As a result, the transparency of the dispersion liquid and sheet containing the fine fibrous cellulose can be more effectively improved.
[0229] (Dispersion liquid)
[0230] The present invention relates to a dispersion containing the above-mentioned fine fibrous cellulose. That is, the dispersion of the present invention contains fine fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm.
[0231] The amount of substituents introduced into the fine fibrous cellulose contained in the dispersion liquid may be less than 0.5 mmol / g, and is preferably 0.4 mmol / g or less, more preferably 0.3 mmol / g or less, further preferably 0.25 mmol / g or less, and particularly preferably 0.15 mmol / g or less. In addition, the amount of substituents introduced into the fine fibrous cellulose contained in the dispersion liquid may be 0.0 mmol / g, preferably 0.01 mmol / g or more, more preferably 0.04 mmol / g or more, further preferably 0.05 mmol / g or more, and particularly preferably 0.07 mmol / g or more.
[0232] The fiber width of the microfibrillar cellulose contained in the dispersion may be 1 to 10 nm, preferably 1 to 9 nm, more preferably 1 to 8 nm, and further preferably 1 to 7 nm. In addition, the number-average fiber width of the fibrillar cellulose contained in the dispersion is preferably 1 to 10 nm, more preferably 1 to 9 nm, further preferably 1 to 8 nm, and particularly preferably 1 to 7 nm. It should be noted that in this specification, fibrillar cellulose includes microfibrillar cellulose and also includes, for example, thick cellulose fibers with a fiber width greater than 1000 nm. The number-average fiber width of the fibrillar cellulose contained in the dispersion being within the above range means that the dispersion substantially does not contain thick cellulose fibers, and furthermore, the fiber width of 70% or more of the fibrillar cellulose is 10 nm or less. Among all the fibrillar cellulose contained in the dispersion, the proportion of the microfibrillar cellulose with a fiber width of 10 nm or less is preferably 70% or more, more preferably 80% or more, and further preferably 90% or more.
[0233] It should be noted that the proportion of the microfibrillar cellulose with a fiber width of 10 nm or less refers to the value represented by the following formula.
[0234] Proportion of microfibrillar cellulose with a fiber width of 10 nm or less (%) = (Number of microfibrillar cellulose with a fiber width of 10 nm or less / Total number of fibrillar cellulose) × 100
[0235] The dispersion of this embodiment is preferably a dispersion containing the above-mentioned microfibrillar cellulose and a dispersion medium. The dispersion medium is not particularly limited, and preferably contains water, and more preferably a solvent containing water as the main component. That is, the dispersion of this embodiment is preferably an aqueous dispersion containing microfibrillar cellulose. It should be noted that the dispersion medium can be an organic solvent. Examples of the organic solvent include dimethylformamide (DMF), dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), aniline, pyridine, quinoline, dimethylpyridine, acetonitrile, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dioxane, ethanol, isopropanol, etc. In addition, as the dispersion medium, a mixed solvent of these organic solvents and water can also be used.
[0236] The pH of the dispersion with a microfibrillar cellulose concentration of 1% by mass is preferably 3 or more, more preferably 4 or more, and further preferably 5 or more. In addition, the pH of the dispersion with a microfibrillar cellulose concentration of 1% by mass is preferably 10 or less, more preferably 9 or less, and further preferably 8 or less. By setting the pH of the dispersion within the above range, the yellowing of the dispersion and the sheet can be more effectively suppressed. It should be noted that in order to set the pH of the dispersion within the above range, the same method as the above <pH adjustment step> can also be adopted.
[0237] The concentration of the fine fibrous cellulose in the dispersion of the present embodiment is not particularly limited, but is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and even more preferably 2.0% by mass or more. In addition, the dispersion of the present embodiment may be a high-concentration dispersion containing 3.0% by mass or more of the fine fibrous cellulose.
[0238] The haze of the dispersion of the present embodiment is preferably 5% or less, more preferably 4% or less, and further preferably 3% or less. Here, the haze of the dispersion is a value measured using a haze meter and a liquid glass cuvette with an optical path length of 1 cm in accordance with JIS K7136:2000. It should be noted that the zero point measurement is performed using ion exchange water contained in the glass cuvette. In addition, the dispersion to be measured is left to stand for 24 hours at 23°C and a relative humidity of 50% before the measurement, and the liquid temperature of the dispersion is set to 23°C.
[0239] In the dispersion of the present embodiment, when the fine fibrous cellulose is prepared into a dispersion with a concentration of 0.1 mass %, and the nanofiber yield is calculated using the following formula, the nanofiber yield is preferably 95 mass % or more, more preferably 96 mass % or more. It should be noted that the nanofiber yield may be 100 mass %.
[0240] Nanofiber yield [mass %] = C / 0.1×100
[0241] Here, C is the concentration of fine fibrous cellulose contained in the supernatant obtained when a dispersion liquid having a fine fibrous cellulose concentration of 0.1% by mass is centrifuged under the conditions of 12000 G for 10 minutes.
[0242] In the dispersion of the present embodiment, when the fine fibrous cellulose concentration is made into a dispersion of 0.4 mass%, the viscosity of the dispersion at 23°C is preferably 100 mPa·s or more, more preferably 1000 mPa·s or more, and further preferably 2000 mPa·s or more. In addition, the viscosity of the dispersion at 23°C is preferably 200000 mPa·s or less, and more preferably 100000 mPa·s or less. The viscosity of the dispersion having a fine fibrous cellulose concentration of 0.4 mass% can be measured using a B-type viscometer (manufactured by BLOOKFIELD, analog viscometer T-LVT). The measurement conditions are set to 23°C, the rotation speed is set to 3 rpm, and the viscosity is measured 3 minutes after the start of the measurement. In addition, the dispersion to be measured is left to stand for 24 hours under an environment of 23°C and a relative humidity of 50% before the measurement, and the liquid temperature of the dispersion is set to 23°C.
[0243] The amount of free nitrogen in the dispersion is preferably less. The amount of free nitrogen in the dispersion can be determined by measuring the nitrogen concentration in the filtrate when filtering the microfibrous cellulose dispersion. For example, the free nitrogen concentration in the dispersion having a microfibrous cellulose concentration of 0.2% by mass is preferably 100 ppm or less, more preferably 80 ppm or less, further preferably 70 ppm or less, further preferably 60 ppm or less, further preferably 50 ppm or less, further preferably 40 ppm or less, and particularly preferably 30 ppm or less. It should be noted that the nitrogen concentration in the dispersion having a microfibrous cellulose concentration of 0.2% by mass can be 0 ppm. The free nitrogen present in the dispersion can cause coloration, so by setting the nitrogen concentration in the filtrate to within the above range, the yellowing of the dispersion and sheet containing microfibrous cellulose can be more effectively suppressed. Here, the method for determining the nitrogen concentration in the filtrate is as follows. First, distilled water is added in such a way that the microfibrous cellulose concentration becomes 0.2% by mass, and after stirring for 24 hours, the filtrate is filtered using a filter material with a pore size of 0.45 μm to obtain a filtrate. Furthermore, the nitrogen concentration (ppm) in the filtrate was measured by micro nitrogen analysis.
[0244] <Optional Ingredients>
[0245] The dispersion may contain optional components on the basis of the microfibrous cellulose and dispersion medium as described above. As optional components, for example, the above-mentioned spacer molecules, hydrophilic polymers, organic ions, etc. can be listed. The hydrophilic polymer is preferably a hydrophilic oxygen-containing organic compound (which does not include the above-mentioned cellulose fibers). The oxygen-containing organic compound is preferably non-fibrous, and this non-fibrous oxygen-containing organic compound does not contain microfibrous cellulose and thermoplastic resin fibers. In addition, as optional components, for example, defoamers, lubricants, ultraviolet absorbers, dyes, pigments, stabilizers, surfactants, preservatives (such as phenoxyethanol), etc. can be listed.
[0246] The oxygen-containing organic compound is preferably a hydrophilic organic compound. The hydrophilic oxygen-containing organic compound can improve the strength, density and chemical resistance of the sheet. The hydrophilic oxygen-containing organic compound preferably has an SP value of 9.0 or more. In addition, with respect to the hydrophilic oxygen-containing organic compound, it is preferred that 1 g or more of the oxygen-containing organic compound be dissolved in, for example, 100 ml of ion exchange water.
[0247] Examples of oxygen-containing organic compounds include hydrophilic polymers such as polyethylene glycol, polyethylene oxide, casein, dextrin, starch, modified starch, polyvinyl alcohol, modified polyvinyl alcohol (acetoacetylated polyvinyl alcohol, etc.), polyethylene oxide, polyvinyl pyrrolidone, polyvinyl methyl ether, polyacrylates, polyacrylamide, alkyl acrylate copolymers, urethane copolymers, and cellulose derivatives (hydroxyethyl cellulose, carboxyethyl cellulose, carboxymethyl cellulose, etc.); and hydrophilic low molecular weights such as glycerol, sorbitol, and ethylene glycol. Among these, polyethylene glycol, polyethylene oxide, polyvinyl alcohol, glycerol, and sorbitol are preferred from the viewpoint of improving the strength, density, and chemical resistance of the sheet, more preferably at least one selected from polyethylene glycol and polyethylene oxide, and even more preferably at least one selected from polyethylene oxide, polyvinyl alcohol, and polyethylene glycol.
[0248] The oxygen-containing organic compound is preferably an organic compound macromolecular weight of 50,000 to 8,000,000. The oxygen-containing organic compound also preferably has a molecular weight of 100,000 to 5,000,000, and may be a low molecular weight of less than 1,000, for example.
[0249] As organic ions, tetraalkylammonium ions and tetraalkylphosphonium ions can be listed. As tetraalkylammonium ions, for example, tetramethylammonium ions, tetraethylammonium ions, tetrapropylammonium ions, tetrabutylammonium ions, tetrapentylammonium ions, tetrahexylammonium ions, tetraheptylammonium ions, tributylmethylammonium ions, lauryltrimethylammonium ions, cetyltrimethylammonium ions, stearyltrimethylammonium ions, octyldimethylethylammonium ions, lauryldimethylethylammonium ions, didecyldimethylammonium ions, lauryldimethylbenzylammonium ions, and tributylbenzylammonium ions can be listed. As tetraalkylphosphonium ions, for example, tetramethylphosphonium ions, tetraethylphosphonium ions, tetrapropylphosphonium ions, tetrabutylphosphonium ions, and lauryltrimethylphosphonium ions can be listed. In addition, as tetrapropyl onium ions and tetrabutyl onium ions, tetra-n-propyl onium ions and tetra-n-butyl onium ions can also be listed respectively.
[0250] (piece)
[0251] The present invention relates to a sheet comprising the above-mentioned fine fibrous cellulose. That is, the sheet of the present invention comprises fine fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm.
[0252] In addition, the present invention relates to a sheet comprising a substituent introduction amount of less than 0.5 mmol / g and a fine fibrous cellulose with a fiber width of 1 to 10 nm, wherein the sheet has a YI value of 1.5 or less when the thickness is 50 μm. The YI value when the sheet thickness is 50 μm is preferably 1.3 or less, and more preferably 1.2 or less. It should be noted that the lower limit of the YI value when the sheet thickness is 50 μm is not particularly limited and may be 0.0. Here, the YI value when the sheet thickness is 50 μm is a yellowness index measured in accordance with JIS K 7373:2006. As a measuring device for the YI value, for example, Colour Cute i (manufactured by Suga Test Instruments) can be used. It should be noted that the above-mentioned YI value is the YI value measured before the sheet is heated as described later, and therefore, it is sometimes also referred to as the initial YI value.
[0253] The YI value when the thickness is 50 μm can be calculated using the following formula.
[0254] YI value when the thickness is 50 μm = YI value of the sheet (measured value) × [50 / thickness of the sheet (μm)]
[0255] It should be noted that the thickness of the sheet can be measured by a stylus constant pressure thickness gauge (MILLITRON 1202DPG-02 manufactured by MAHR TECLOCK CORPORATION). Specifically, a sheet cut into a size of 50 mm square or more is humidified at 23° C. and a relative humidity of 50% for 24 hours, and the thickness at four random points is measured, and the average value is taken as the thickness of the sheet.
[0256] The YI increase rate of the sheet of the present embodiment is preferably 1500% or less, more preferably 1200% or less, further preferably 1000% or less, further preferably 800% or less, and particularly preferably 750% or less. It should be noted that the lower limit of the YI increase rate of the sheet is not particularly limited and may be 0%. Here, the YI increase rate of the sheet refers to the increase rate of the YI value of the sheet before and after the sheet is heated at 160°C for 6 hours. Specifically, the YI increase rate is a value calculated using the following formula.
[0257] YI increase rate (%) = (yellowness index of the sheet after heating - yellowness index of the sheet before heating) / yellowness index of the sheet before heating × 100
[0258] It should be noted that, in the above formula, the yellowness index of the sheet is a yellowness index measured in accordance with JIS K 7373:2006.
[0259] Furthermore, in the present embodiment, when the initial YI value is 1.5 or less and the YI increase rate is within the above range, it can be determined that the coloring (yellowing) of the sheet is suppressed.
[0260] The haze of the sheet of the present embodiment is preferably 5.0% or less, more preferably less than 3.5%, further preferably 3.0% or less, further preferably 2.5% or less, and particularly preferably 2.0% or less. If the haze of the sheet is within the above range, it can be determined that a highly transparent sheet is formed by using the fine fibrous cellulose of the present embodiment. It should be noted that the haze of the sheet is a value measured using a haze meter in accordance with JIS K 7136:2000.
[0261] The total light transmittance of the sheet of the present embodiment is preferably 90.0% or more, more preferably 90.5% or more, and further preferably 91.0% or more. The haze of the sheet is a value measured using a haze meter in accordance with JIS K 7361-1:1997.
[0262] The surface roughness of at least one surface of the sheet of the present embodiment is preferably less than 50nm, more preferably less than 30nm, and further preferably less than 10nm. It should be noted that it is also particularly preferred that the surface roughness of both sides of the sheet is within the above range. By setting the surface roughness to within the above range, the transparency of the sheet can be further improved. Specifically, the haze of the sheet can be further reduced. Here, the surface roughness (arithmetic mean) of the sheet is the arithmetic mean roughness of at least one surface of the sheet. The surface roughness (arithmetic mean) is a value obtained by measuring the arithmetic mean roughness of a 3μm square using an atomic force microscope (Veeco, NanoScope IIIa).
[0263] The surface pH of the sheet of the present embodiment is preferably 3 or more, more preferably 4 or more, and further preferably 5 or more. In addition, the surface pH of the sheet is preferably 10 or less, further preferably 9 or less, and more preferably 8 or less. By setting the surface pH of the sheet to the above range, the effect of suppressing yellowing can be easily obtained. In order to set the surface pH of the sheet to the above range, it is ideal to set the pH of the dispersion (a dispersion having a concentration of 1% by mass of fine fibrous cellulose) to the aforementioned preferred range. It should be noted that when measuring the surface pH of the sheet, 10 μL of ion exchange water is dripped into a 1 cm square range on the surface of the sheet using a micropipette, and the pH of this portion is measured using a flat pH composite electrode (6261-10C; manufactured by HORIBA).
[0264] The sheet of the present embodiment is manufactured from the above dispersion. Specifically, the manufacturing process of the sheet preferably includes: a coating process of coating the above dispersion on a substrate or a papermaking process of making paper from the above dispersion. It should be noted that the dispersion may contain the above additives as required.
[0265] In the coating process, the dispersion (coating solution) containing the above-mentioned fine fibrous cellulose can be applied to the substrate and dried, and the sheet thus formed can be peeled off from the substrate to obtain a sheet. By using a coating device and a long substrate, it is possible to continuously produce sheets. In addition, the papermaking process is carried out by using a papermaking machine to make paper from the slurry. The papermaking machine used in the papermaking process is not particularly limited, and examples thereof include continuous papermaking machines such as long net type, round net type, inclined type, or multi-layer papermaking machines obtained by combining them. In the papermaking process, known papermaking methods such as manual papermaking can be used.
[0266] The sheet of the present embodiment may further include a resin layer and an inorganic layer. The present embodiment may also relate to a laminate having the above-mentioned sheet and having a resin layer and / or an inorganic layer.
[0267] <Optional Ingredients>
[0268] The sheet of the present embodiment may contain optional components that may be contained in the dispersion. Among them, the sheet preferably contains the above-mentioned hydrophilic polymer, and the hydrophilic polymer is preferably a hydrophilic oxygen-containing organic compound. The content of the oxygen-containing organic compound contained in the sheet is preferably 1 mass part or more, more preferably 10 mass parts or more, and further preferably 15 mass parts or more relative to 100 mass parts of fine fibrous cellulose contained in the sheet. In addition, the content of the oxygen-containing organic compound contained in the sheet is preferably 1000 mass parts or less, more preferably 500 mass parts or less, further preferably 100 mass parts or less, and particularly preferably 50 mass parts or less relative to 100 mass parts of fine fibrous cellulose contained in the sheet. By setting the content of the oxygen-containing organic compound within the above range, a laminated sheet with high transparency and strength can be formed.
[0269] (Laminated Sheet)
[0270] The present invention relates to a laminated sheet having a fiber layer and a resin layer disposed on at least one surface of the fiber layer. Here, the fiber layer contains fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm. The fiber layer constituting the laminated sheet is a layer formed by the above sheet.
[0271] Figure 2 2 is a cross-sectional view illustrating the structure of the laminated sheet of this embodiment. Figure 2As shown in the figure, the laminated sheet 10 of the present embodiment has a resin layer 2 and a fiber layer 6. The resin layer 2 is directly laminated on the fiber layer 6, and the resin layer 2 and the fiber layer 6 are in contact with each other on either side. The laminated sheet 10 of the present embodiment only needs to have at least one layer of each resin layer 2 and fiber layer 6, and may have more than two layers of resin layers 2, or may have more than two layers of fiber layers 6. For example, the laminated sheet may be a structure in which a fiber layer, a resin layer, and a fiber layer are laminated in sequence, or may be a structure in which a resin layer, a fiber layer, and a resin layer are laminated in sequence.
[0272] In the past, in order to obtain a sheet with high transparency, it has been studied to increase the amount of substituents introduced into microfibrous cellulose, thereby obtaining microfibrous cellulose with a small fiber width. However, when microfibrous cellulose with a high amount of substituents is mixed into the sheet in this way, there is a tendency for the sheet to be colored due to heating in the manufacturing process of the sheet and the use environment. On the other hand, when the substituent introduction process is controlled and the amount of substituents introduced is suppressed to a low level, the fibrillation of the microfibrous cellulose becomes insufficient, and it is difficult to obtain a highly transparent sheet. Therefore, the inventors of the present invention have repeatedly studied the manufacturing process of microfibrous cellulose, and have successfully miniaturized the fiber width to a level of 1 to 10 nm despite the low amount of substituents introduced, which is less than 0.5 mmol / g. And it was found that the sheet of fibrous cellulose with a low amount of substituents and a fiber width of 1 to 10 nm is highly transparent and coloring is suppressed. When such a sheet containing microfibrous cellulose is laminated on a resin layer, the transparency of the resin layer can be maintained without being damaged.
[0273] The total light transmittance of the laminated sheet is preferably 88% or more, more preferably 90% or more, further preferably 91% or more, and particularly preferably 91.5% or more. By setting the total light transmittance of the laminated sheet to the above range, the laminated sheet of this embodiment can also be used in the application of transparent glass in the past. Here, the total light transmittance is a value measured in accordance with JIS K7361-1:1997 and using a haze meter (Murakami Color Technology Research Institute, HM-150).
[0274] The haze of the laminated sheet is preferably 2.0% or less, preferably 1.5% or less, and more preferably 1.0% or less. It should be noted that the lower limit of the haze of the laminated sheet is not particularly limited and may be 0%. Here, the haze is a value measured in accordance with JIS K7136:2000 using a haze meter (Murakami Color Technology Research Institute, HM-150).
[0275] The laminated sheet of the present embodiment also has excellent interlayer adhesion between the fiber layer and the resin layer. Specifically, according to JIS K 5400, 100 1 mm2 scratches were made on the surface of the fiber layer side of the laminated sheet. 2The number of grids at which the fiber layer is peeled off from the resin layer is less than 5 after a transparent tape (manufactured by NICHIBAN) is attached and pressed on the grids. In this case, it can be determined that the interlayer adhesion between the fiber layer and the resin layer is good. The number of grids peeled off is more preferably 3 or less, further preferably 1 or less, and particularly preferably 0.
[0276] The laminated sheet of the present embodiment has a fiber layer and a resin layer, and the fiber layer can also function as a layer for strengthening the resin layer. Therefore, the strength of the laminated sheet itself can be improved. In addition, when the laminated sheet is attached to an adherend such as other resin films or resin plates, the fiber layer functions as a layer for strengthening the adherend. For example, by using a resin plate such as a polycarbonate plate as an adherend, the laminated sheet is attached to the resin plate, thereby strengthening the mechanical strength of the resin plate. Like this, the laminated sheet with the fiber layer also has the effect of strengthening the adherend.
[0277] The strengthening effect when laminating the laminated sheet on the adherend can be evaluated as follows: for example, when the bending elastic modulus after laminating the laminated sheet on the adherend becomes more than 1.5 times compared with the bending elastic modulus of the adherend, it can be evaluated as exerting an excellent strengthening effect. The bending elastic modulus after laminating the laminated sheet on the adherend is particularly preferably more than 2.0 times compared with the bending elastic modulus of the adherend. It should be noted that when the adherend is laminated, the laminated sheet is made by heat pressing to the glass transition temperature of the adherend after the adherend and the laminated sheet overlap.
[0278] The laminated sheet of the present embodiment itself has excellent mechanical strength. For example, the tensile elastic modulus of the laminated sheet at 23°C and a relative humidity of 50% is preferably 2.5 GPa or more, more preferably 5.0 GPa or more, and further preferably 10 GPa or more. In addition, the tensile elastic modulus of the laminated sheet at 23°C and a relative humidity of 50% is preferably 30 GPa or less, more preferably 25 GPa or less, and further preferably 20 GPa or less. The tensile elastic modulus of the laminated sheet is a value measured in accordance with JIS P 8113.
[0279] The overall thickness of the laminate is not particularly limited, but is preferably 30 μm or more, more preferably 40 μm or more, further preferably 50 μm or more, further preferably 60 μm or more, and particularly preferably 70 μm or more. In addition, the overall thickness of the laminate is preferably 1000 μm or less. The thickness of the laminate can be appropriately adjusted according to the purpose. From the perspective of exerting the effect of strengthening the adherend, the overall thickness of the laminate is preferably 50 μm or more.
[0280] The thickness of the fiber layer of the laminate is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more. In addition, the thickness of the fiber layer is preferably 500 μm or less, more preferably 200 μm or less, and further preferably 100 μm or less. Here, the thickness of the fiber layer constituting the laminate is a value measured by cutting out a cross section of the laminate using a slicer UC-7 (manufactured by JEOL) and observing the cross section using an electron microscope, a magnifying glass or visually. In the case where a plurality of fiber layers are included in the laminate, the total thickness of the fiber layer is preferably within the above range.
[0281] In addition, the thickness of the resin layer of the laminate is preferably 0.5 μm or more, more preferably 1 μm or more, further preferably 2 μm or more, and particularly preferably 3 μm or more. In addition, the thickness of the resin layer is preferably 15000 μm or less, more preferably 5000 μm or less, and further preferably 500 μm or less. Here, the thickness of the resin layer constituting the laminate is a value measured by cutting out a cross section of the laminate using a slicer UC-7 (manufactured by JEOL) and observing the cross section using an electron microscope, a magnifying glass or visually. In the case where a plurality of resin layers are included in the laminate, the total thickness of the resin layer is preferably within the above range.
[0282] The ratio of the thickness of the resin layer to the thickness of the fiber layer (the thickness of the resin layer / the thickness of the fiber layer) is preferably 10 or less, more preferably 5 or less, and further preferably 1 or less. In addition, for example, when the resin layer is a coating layer formed by coating, the ratio of the thickness of the resin layer to the thickness of the fiber layer (the thickness of the resin layer / the thickness of the fiber layer) may be 0.5 or less, 0.2 or less, 0.15 or less, or 0.1 or less. It should be noted that when there are multiple fiber layers in the laminated sheet, the thickness of the fiber layer is the total thickness of the fiber layers, and when there are multiple resin layers, the thickness of the resin layer is the total thickness of the resin layers.
[0283] In the present embodiment, the YI value of the laminate is preferably less than 2.0, more preferably less than 1.5. It should be noted that the lower limit of the YI value of the laminate is not particularly limited, preferably more than 0.1. Here, the YI value of the laminate is the YI value measured in accordance with JIS K7373:2006. As a measuring device for the YI value, for example, Color Cute i (Suga Test Instruments company system) can be used. It should be noted that the above-mentioned YI value is the YI value measured before the laminate is heated as described later, therefore, it is sometimes referred to as the initial YI value.
[0284] In this embodiment, the YI value after heating the laminated sheet at 160° C. for 6 hours is preferably 20 or less, more preferably 15 or less, and further preferably 10 or less. It should be noted that the lower limit of the YI value of the laminated sheet after heating at 160° C. for 6 hours is not particularly limited, but is preferably 0.1 or more. It should be noted that the YI value after heating at 160° C. for 6 hours is sometimes referred to as the YI value after heating.
[0285] The YI increase rate in the laminated sheet of the present embodiment is preferably 1500% or less, more preferably 1250% or less, further preferably 1000% or less, further preferably 800% or less, and particularly preferably 600% or less. It should be noted that the lower limit of the YI increase rate in the laminated sheet is not particularly limited, and is preferably 0.1% or more. Here, the YI increase rate of the laminated sheet refers to the increase rate of the YI value of the laminated sheet before and after the laminated sheet is heated at 160°C for 6 hours. Specifically, the YI increase rate is a value calculated using the following formula.
[0286] YI increase rate (%) = (YI value of the laminated sheet after heating - YI value of the laminated sheet before heating) / YI value of the laminated sheet before heating × 100
[0287] In addition, in the above formula, the YI value of the laminated sheet is a YI value measured according to JIS K 7373:2006.
[0288] (Resin layer)
[0289] The laminate sheet has at least one resin layer. Here, the resin layer is directly laminated on the fiber layer, and the resin layer and the fiber layer are in contact with each other on either side. It should be noted that the resin layer is preferably a resin layer formed by coating (coating resin layer).
[0290] The resin layer is a layer with natural resin or synthetic resin as the main component. Here, the main component refers to a component whose content is 50% by mass or more relative to the total mass of the resin layer. The content of the resin is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more relative to the total mass of the resin layer. It should be noted that the content of the resin can also be set to 100% by mass, or can be 95% by mass or less.
[0291] Examples of the natural resin include rosin-based resins such as rosin, rosin ester, and hydrogenated rosin ester.
[0292] As the synthetic resin, it is preferred that at least one selected from polycarbonate resin, polyethylene terephthalate resin, polyethylene naphthalate resin, polyethylene resin, polypropylene resin, cyclic olefin resin, polyimide resin, polystyrene resin and acrylic resin. Among them, the synthetic resin is preferably at least one selected from polycarbonate resin and acrylic resin, more preferably polycarbonate resin. It should be noted that the acrylic resin is preferably at least one selected from polyacrylonitrile and poly (meth) acrylate.
[0293] Examples of the polycarbonate resin constituting the resin layer include aromatic polycarbonate resins and aliphatic polycarbonate resins. These specific polycarbonate resins are well known, and examples thereof include polycarbonate resins described in Japanese Patent Application Laid-Open No. 2010-023275.
[0294] In the laminated sheet of the present embodiment, the resin layer preferably contains a close-fitting aid. As the close-fitting aid, for example, a compound containing at least one selected from an isocyanate group, a carbodiimide group, an epoxy group, an oxazoline group, an amino group, a silanol group, and an alkoxysilyl group; an organosilicon compound. Among them, the close-fitting aid is preferably at least one selected from a compound containing an isocyanate group (isocyanate compound) and an organosilicon compound. As the organosilicon compound, for example, a silane coupling agent condensate and a silane coupling agent can be listed.
[0295] As the isocyanate compound, a polyisocyanate compound or a polyfunctional isocyanate can be cited. As the polyisocyanate compound, specifically, an aromatic polyisocyanate having a carbon number of 6 or more and 20 or less, an aliphatic polyisocyanate having a carbon number of 2 or more and 18 or less, an alicyclic polyisocyanate having a carbon number of 6 or more and 15 or less, an aralkyl type polyisocyanate having a carbon number of 8 or more and 15 or less, a modified product of these polyisocyanates, and a mixture of two or more thereof can be cited. Among them, an alicyclic polyisocyanate having a carbon number of 6 or more and 15 or less, i.e., isocyanurate, is preferably used.
[0296] Specific examples of the alicyclic polyisocyanate include isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4′-diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, and 2,6-norbornane diisocyanate.
[0297] As the organosilicon compound, compounds having a siloxane structure or compounds forming a siloxane structure by condensation can be listed. For example, as the organosilicon compound, a silane coupling agent or a condensate of a silane coupling agent can be listed. As the silane coupling agent, it may have a functional group other than an alkoxysilyl group, or it may not have a functional group other than this. As the functional group other than the alkoxysilyl group, vinyl, epoxy, styryl, methacryloxy, acryloxy, amino, ureide, mercapto, thioether, isocyanate, etc. can be listed. The silane coupling agent used in the present embodiment is preferably a silane coupling agent containing a methacryloxy group.
[0298] Specific examples of silane coupling agents having a methacryloxy group in the molecule include methacryloxypropylmethyldimethoxysilane, methacryloxypropyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropyltriethoxysilane, 1,3-bis(3-methacryloxypropyl)tetramethyldisiloxane, etc. Among them, at least one selected from methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane and 1,3-bis(3-methacryloxypropyl)tetramethyldisiloxane is preferably used. The silane coupling agent preferably contains three or more alkoxysilyl groups.
[0299] As the silane coupling agent, a silane coupling agent having an alkoxysilyl group can be used, and a silane coupling agent that generates a silanol group after hydrolysis can be used. In this case, it is preferred that at least a portion of the alkoxysilyl group and the silanol group still exist after laminating the fiber layer. The silanol group is a hydrophilic group, and therefore, by increasing the hydrophilicity of the surface of the fiber layer side of the resin layer, the adhesion between the resin layer and the fiber layer can also be more effectively improved.
[0300] The adhesion promoter may be contained in a state uniformly dispersed in the resin layer. Here, the state in which the adhesion promoter is uniformly dispersed in the resin layer means that when the concentrations of the following three regions ((a) to (c)) are measured, there is no difference of more than 2 times even when the concentrations of any two regions are compared.
[0301] (a) an area from the surface of the resin layer on the fiber layer side to 10% of the total thickness of the resin layer;
[0302] (b) a region from the surface of the resin layer opposite to the fiber layer to 10% of the total thickness of the resin layer;
[0303] (c) A region from the center plane in the thickness direction of the resin layer to ±5% (10% in total) of the entire thickness.
[0304] The adhesion promoter may be present more preferentially in the region on the fiber layer side of the resin layer. For example, when an organosilicon compound is used as the adhesion promoter, the organosilicon compound may be present more preferentially in the region on the fiber layer side of the resin layer.
[0305] Here, the state where the concentration is concentrated in the region on the fiber layer side of the resin layer means that the concentrations in both the following regions ((d) and (e)) are measured and the concentrations differ by 2 times or more.
[0306] (d) a region from the surface of the resin layer on the fiber layer side to 10% of the total thickness of the resin layer;
[0307] (e) A region from the center plane in the thickness direction of the resin layer to ±5% (10% in total) of the entire thickness.
[0308] Here, the concentration of the adhesion promoter is a value measured by an X-ray electron spectrometer or an infrared spectrophotometer, and is a value obtained by cutting out a cross section of a predetermined region of the laminated sheet using a microtome UC-7 (manufactured by JEOL) and measuring the cross section using the device.
[0309] The layer containing the organosilicon compound may be provided on the fiber layer side of the resin layer, and this state is also included in the state where the organosilicon compound is concentrated in the fiber layer side region of the resin layer. The layer containing the organosilicon compound may be a coating layer formed by coating a coating liquid containing the organosilicon compound.
[0310] It should be noted that when a layer containing an organosilicon compound is provided on the surface of the fiber layer side of the resin layer, in the above-mentioned area (d), "the surface of the fiber layer side of the resin layer" is understood as "the exposed surface of the layer containing an organosilicon compound", and "the overall thickness of the resin layer" is understood as "the total thickness of the resin layer and the layer containing an organosilicon compound".
[0311] The content of the adhesion aid is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the resin contained in the resin layer. In addition, the content of the adhesion aid is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, relative to 100 parts by mass of the resin contained in the resin layer.
[0312] When the adhesion aid is an isocyanate compound, the content of the isocyanate compound is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and further preferably 18 parts by mass or more relative to 100 parts by mass of the resin contained in the resin layer. In addition, the content of the isocyanate compound is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and further preferably 30 parts by mass or less relative to 100 parts by mass of the resin contained in the resin layer.
[0313] When the adhesion aid is an organosilicon compound, the content of the organosilicon compound is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the resin contained in the resin layer. In addition, the content of the organosilicon compound is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the resin contained in the resin layer.
[0314] By setting the content of the adhesion aid in the above range, the adhesion between the fiber layer and the resin layer can be more effectively improved.
[0315] When the adhesion aid is an isocyanate compound, the content of the isocyanate group contained in the resin layer is preferably 0.5 mmol / g or more, more preferably 0.6 mmol / g or more, further preferably 0.8 mmol / g or more, and particularly preferably 0.9 mmol / g or more. In addition, the content of the isocyanate group contained in the resin layer is preferably 3.0 mmol / g or less, more preferably 2.5 mmol / g or less, further preferably 2.0 mmol / g or less, and particularly preferably 1.5 mmol / g or less.
[0316] The surface of the fiber layer side of the resin layer may be subjected to a surface treatment. Examples of the surface treatment method include corona treatment, plasma discharge treatment, UV irradiation treatment, electron beam irradiation treatment, and flame treatment. Among them, the surface treatment is preferably at least one selected from the group consisting of corona treatment and plasma discharge treatment. It should be noted that the plasma discharge treatment is preferably a vacuum plasma discharge treatment.
[0317] The surface of the fiber layer side of the resin layer can be formed with a fine concavo-convex structure. By making the surface of the fiber layer side of the resin layer have a fine concavo-convex structure, the adhesion of the fiber layer and the resin layer can be more effectively improved. When the surface of the fiber layer side of the resin layer has a fine concavo-convex structure, this structure is preferably formed by treatment processes such as shot peening, embossing, etching, corona treatment, plasma discharge treatment, etc. It should be noted that in this specification, the fine concavo-convex structure refers to a structure in which the number of concave portions existing on a straight line of 1 mm drawn at any position is more than 10. When measuring the number of concave portions, the laminate is immersed in ion exchange water for 24 hours, and the fiber layer is peeled off from the resin layer. Thereafter, it can be measured by scanning the surface of the fiber layer side of the resin layer using a stylus surface roughness meter (manufactured by Kosaka Institute, SURFCORDER series). When the pitch of the concavities and convexities is extremely small, such as a pitch of the order of submicrometer or nanometer, the number of the concavities and convexities can be measured from an image observed with a scanning probe microscope (AFM5000II and AFM5100N manufactured by Hitachi High-Technologies Corporation).
[0318] The resin layer may contain an optional component other than the synthetic resin. Examples of the optional component include known components used in the field of resin films, such as fillers, pigments, dyes, and ultraviolet absorbers.
[0319] (Fiber layer)
[0320] The fiber layer contains fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm. In general, fibrous cellulose having a fiber width of 1000 nm or less is also referred to as microfibrous cellulose or CNF. Among them, the fibrous cellulose contained in the fiber layer of the present embodiment is a microfibrous cellulose having a smaller fiber width. As the microfibrous cellulose contained in the fiber layer, the above-mentioned microfibrous cellulose can be preferably exemplified. In addition, the microfibrous cellulose contained in the fiber layer is preferably manufactured using the above-mentioned manufacturing method.
[0321] The number average fiber width of the fibrous cellulose contained in the fiber layer is preferably 1 to 10 nm, more preferably 1 to 9 nm, further preferably 1 to 8 nm, and particularly preferably 1 to 7 nm. It should be noted that the number average fiber width of the fibrous cellulose contained in the fiber layer being within the above range means that the fiber layer does not substantially contain coarse cellulose fibers, and further, more than 70% of the fibrous cellulose has a fiber width of 10 nm or less. Among all the fibrous cellulose contained in the fiber layer, the proportion of fine fibrous cellulose having a fiber width of 10 nm or less is preferably 70% or more, more preferably 80% or more, and further preferably 90% or more.
[0322] Here, the ratio of fine fibrous cellulose having a fiber width of 10 nm or less refers to a value represented by the following formula.
[0323] Ratio of fine fibrous cellulose having a fiber width of 10 nm or less (%) = (number of fine fibrous cellulose having a fiber width of 10 nm or less / number of all fibrous cellulose) × 100
[0324] The fiber width of the fine fibrous cellulose in the laminated sheet is measured by, for example, atomic force microscopy observation as follows. First, the fiber layer of the laminated sheet is observed using an atomic force microscope (manufactured by Veeco, NanoScope IIIa). At this time, the image is set to a 500nm field of view. For the obtained image, two random axes in the vertical and horizontal directions are drawn for each image, and more than 20 fibers that intersect the axes are randomly selected, and the fiber width is read visually. In this way, three non-repetitive observation images are taken, and the value of the fiber width of the fibers that intersect with each of the two axes is read (more than 20 × 2 × 3 = more than 120).
[0325] (1) Draw a straight line X at any position in the observation image, and randomly select 20 or more fibers that intersect the straight line X.
[0326] (2) Draw a straight line Y perpendicular to the straight line in the same image, and randomly select 20 or more fibers that intersect the straight line Y.
[0327] In addition, when the fiber layer is not exposed in the laminated sheet, the laminated sheet is cut using a microtome or the like, and the cross section of the fiber layer is cut out and observed by the above method.
[0328] In this embodiment, the density of the fiber layer is preferably 1.0 g / cm 3 More preferably, 1.2 g / cm 3 More preferably, 1.4 g / cm 3 In addition, the density of the fiber layer is preferably 1.7 g / cm 3 Below, more preferably 1.65g / cm 3 Below, more preferably 1.6 g / cm 3 When the laminated sheet includes two or more fiber layers, the density of each fiber layer is preferably within the above range.
[0329] The density of the fiber layer is calculated based on the basis weight and thickness of the fiber layer in accordance with JIS P 8118: 2014. The basis weight of the fiber layer can be calculated by cutting the fiber layer using a slicer UC-7 (manufactured by JEOL) so that only the fiber layer of the laminated sheet remains, and calculating it in accordance with JIS P 8124: 2011. It should be noted that when the fiber layer contains an optional component other than the microfibrous cellulose, the density of the fiber layer is the density including the optional component other than the microfibrous cellulose.
[0330] In this embodiment, the fiber layer is preferably a non-porous layer. Here, the fiber layer is non-porous means that the density of the fiber layer as a whole is 1.0 g / cm 3 If the density of the fiber layer as a whole is 1.0 g / cm 3 The above means that the porosity contained in the fiber layer is suppressed to below the specified value, which is distinguished from porous sheets and layers. In addition, the fiber layer is non-porous and can also be characterized by a porosity of less than 15 volume %. The porosity of the fiber layer mentioned here is simply calculated by the following formula (a).
[0331] Formula (a): Void ratio (volume %) = {1-B / (M×A×t)}×100
[0332] Here, A is the area of the fiber layer (cm 2), t is the thickness of the fiber layer (cm), B is the mass of the fiber layer (g), and M is the density of cellulose.
[0333] In the present embodiment, the surface roughness of at least one side of the fiber layer is preferably less than 50 nm, more preferably less than 30 nm, and further preferably less than 10 nm. It should be noted that it is also particularly preferred that the surface roughness of both sides of the fiber layer is within the above range. By making the surface roughness within the above range, the transparency of the fiber layer can be further improved, and as a result, the transparency of the laminate can also be improved. Specifically, the haze of the fiber layer and the laminate can be further reduced. Here, the surface roughness (arithmetic mean) of the fiber layer is the arithmetic mean roughness of at least one surface of the fiber layer. The surface roughness (arithmetic mean) is a value obtained by measuring the arithmetic mean roughness of a 3 μm square using an atomic force microscope (manufactured by Veeco, NanoScope IIIa).
[0334] In the present embodiment, the surface pH of the fiber layer is preferably 3 or more, more preferably 4 or more, and further preferably 5 or more. In addition, the surface pH of the fiber layer is preferably 10 or less, more preferably 9 or less, and further preferably 8 or less. By setting the surface pH of the fiber layer to the above range, the effect of suppressing yellowing is easily obtained. In order to set the surface pH of the fiber layer to the above range, it is preferred to appropriately adjust the pH of the fine fibrous cellulose dispersion obtained by the manufacturing process described later. It should be noted that when measuring the surface pH of the fiber layer, 10 μL of ion exchange water is dripped into a 1 cm square range on the surface of the fiber layer using a micropipette, and the pH of this part is measured using a flat pH composite electrode (6261-10C; manufactured by HORIBA).
[0335] <Optional Ingredients>
[0336] The fiber layer may contain an optional component other than the fine fibrous cellulose. Examples of the optional component include the optional components that can be contained in the dispersion and the fiber layer.
[0337] The fiber layer preferably contains the above-mentioned hydrophilic polymer, and the hydrophilic polymer is preferably a hydrophilic oxygen-containing organic compound. The content of the oxygen-containing organic compound contained in the fiber layer is preferably 1 mass part or more, more preferably 10 mass parts or more, and further preferably 15 mass parts or more relative to 100 mass parts of fine fibrous cellulose contained in the fiber layer. In addition, the content of the oxygen-containing organic compound contained in the fiber layer is preferably 1000 mass parts or less, more preferably 500 mass parts or less, further preferably 100 mass parts or less, and particularly preferably 50 mass parts or less relative to 100 mass parts of fine fibrous cellulose contained in the fiber layer. By setting the content of the oxygen-containing organic compound within the above range, a laminated sheet with high transparency and strength can be formed.
[0338] (Method for producing laminated sheet)
[0339] The method for manufacturing the laminated sheet of the present embodiment preferably includes the following steps: forming a fiber layer containing fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm; and applying a resin composition on the fiber layer. In addition, the method for manufacturing the laminated sheet of the present embodiment may include applying a fine fibrous cellulose dispersion containing fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm on the resin layer.
[0340] In the step of coating the resin composition on the fiber layer to form the resin layer, it is preferred to provide a drying step after coating the resin composition containing the resin to form a coating film.
[0341] As a method for manufacturing a laminated sheet, in addition to the above method, a method of placing a resin layer on a fiber layer and performing heat pressing can also be cited. In addition, a method of arranging a fiber layer in an injection molding mold, injecting heated and molten resin into the mold, and thereby bonding the resin layer to the fiber layer can also be cited.
[0342] The step of forming a fiber layer containing fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm preferably includes a step of applying the dispersion containing fine fibrous cellulose (slurry containing fine fibrous cellulose) on a substrate or a step of making paper from the fine fibrous cellulose dispersion. In addition, when applying a fine fibrous cellulose dispersion containing fibrous cellulose having a fiber width of 1000 nm or less on a resin layer, the substrate may be replaced with a resin layer and the coating method described below may be adopted.
[0343] It should be noted that the microfibrous cellulose dispersion (slurry containing microfibrous cellulose) may contain optional components contained in the fiber layer, and the nanofiber yield, haze, pH, viscosity, free nitrogen content, etc. of the microfibrous cellulose dispersion are preferably within the numerical range recorded in the above-mentioned item <Microfibrous cellulose>.
[0344] <Coating process>
[0345] The step of applying a microfibrous cellulose dispersion (a slurry containing microfibrous cellulose) on a substrate (hereinafter also referred to as a coating step) is a step of applying the microfibrous cellulose dispersion on a substrate and drying it, and peeling off the sheet containing microfibrous cellulose thus formed from the substrate to obtain a sheet. By using a coating device and a long substrate, it is possible to continuously produce sheets. The concentration of the applied microfibrous cellulose dispersion is not particularly limited, but is preferably 0.05% by mass or more and 5% by mass or less.
[0346] The material of the substrate used in the coating process is not particularly limited. When the wettability to the fine fibrous cellulose dispersion is high, the shrinkage of the sheet during drying can be suppressed, and it is preferred to select a substrate that can be easily peeled off the sheet formed after drying. Among them, resin plates or metal plates are preferred, but not particularly limited. For example, resin plates such as acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, and polyvinylidene chloride plates; metal plates such as aluminum plates, zinc plates, copper plates, and iron plates; and substrates obtained by oxidizing their surfaces, stainless steel plates, brass plates, etc. can be used.
[0347] In the coating process, when the viscosity of the fine fibrous cellulose dispersion is low and it spreads on the substrate, in order to obtain a sheet containing fine fibrous cellulose of a specified thickness and a specified basis weight, a blocking frame can be fixed on the substrate for use. The material of the blocking frame is not particularly limited, and it is preferred to select a frame that can be easily peeled off at the end of the attached sheet after drying. Among them, a frame formed by molding a resin plate or a metal plate is preferred, but it is not particularly limited. For example, resin plates such as acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, polyvinylidene chloride plates, aluminum plates, zinc plates, copper plates, iron plates, and metal plates, and plates obtained by oxidizing their surfaces, stainless steel plates, brass plates, etc. can be used.
[0348] As a coater for applying the fine fibrous cellulose dispersion, for example, a bar coater, roll coater, gravure coater, die coater, curtain coater, air blade coater, etc. are used. From the viewpoint of making the thickness more uniform, a bar coater, die coater, curtain coater, or spray coater is preferred.
[0349] The coating temperature is not particularly limited, but is preferably 20° C. to 45° C. If the coating temperature is at least the lower limit, the fine fibrous cellulose dispersion can be easily coated, while if it is at most the upper limit, volatilization of the dispersion medium during coating can be suppressed.
[0350] In the coating process, it is preferred that the final basis weight of the sheet be 10 g / m 2 Above and 100g / m 2The fine fibrous cellulose dispersion is applied as follows: By applying the dispersion so that the basis weight is within the above range, a fiber layer having excellent strength can be obtained.
[0351] The production process of the sheet containing fine fibrous cellulose preferably includes a step of drying the fine fibrous cellulose dispersion applied to the substrate. The drying method is not particularly limited and may be a non-contact drying method or a method of drying while restraining the sheet, or a combination of these methods.
[0352] As a non-contact drying method, there is no particular limitation, and a method of drying by heating with hot air, infrared, far infrared or near infrared (heat drying method); a method of drying by making a vacuum (vacuum drying method) can be applied. The heating drying method and the vacuum drying method can be combined, and the heating drying method is usually applied. Drying based on infrared, far infrared or near infrared can be carried out using an infrared device, a far infrared device or a near infrared device, without particular limitation. The heating temperature in the heating drying method is not particularly limited, and is preferably set to be above 20°C and below 150°C, and more preferably set to be above 25°C and below 105°C. If the heating temperature is set to be above the above lower limit, the dispersion medium can be volatilized quickly. If it is below the above upper limit, the cost required for heating can be suppressed and the discoloration of the fine fibrous cellulose due to heat can be suppressed.
[0353] After drying, the obtained microfibrous cellulose-containing sheet is peeled off from the substrate. If the substrate is a sheet, the microfibrous cellulose-containing sheet and the substrate may be rolled up in a stacked state, and the microfibrous cellulose-containing sheet may be peeled off from the process substrate just before the microfibrous cellulose-containing sheet is used. In this way, a microfibrous cellulose-containing sheet serving as a fiber layer can be obtained.
[0354] In the step of applying the resin composition on the fiber layer, the resin composition is preferably applied on the surface of the sheet containing fine fibrous cellulose that is peeled off from the substrate, thereby further improving the interlayer adhesion between the fiber layer and the resin layer.
[0355] <Papermaking process>
[0356] The production process of the sheet containing fine fibrous cellulose to be the fiber layer may include a process of papermaking the fine fibrous cellulose dispersion. In the papermaking process, examples of papermaking machines include continuous papermaking machines such as Fourdrinier, cylinder, and inclined papermaking machines, and multilayer papermaking machines obtained by combining these. In the papermaking process, known papermaking methods such as manual papermaking can be performed.
[0357] In the papermaking process, a sheet in a wet paper state is obtained by filtering and dehydrating a microfibrous cellulose dispersion on a wire, and then pressurizing and drying to obtain a sheet. The concentration of the microfibrous cellulose dispersion is not particularly limited, and is preferably 0.05% by mass or more and 5% by mass or less. When filtering and dehydrating the microfibrous cellulose dispersion, the filter cloth used for filtration is not particularly limited, and the important thing is that the microfibrous cellulose does not pass through and the filtration speed is not too slow. Such a filter cloth is not particularly limited, and is preferably a sheet, a fabric, or a porous membrane formed by an organic polymer. The organic polymer is not particularly limited, and is preferably a non-cellulose organic polymer such as polyethylene terephthalate, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), etc. Specifically, examples include porous films of polytetrafluoroethylene having a pore size of 0.1 μm to 20 μm, for example, 1 μm; and fabrics of polyethylene terephthalate and polyethylene having a pore size of 0.1 μm to 20 μm, for example, 1 μm, without particular limitation.
[0358] The method for producing a sheet from a fine fibrous cellulose dispersion is not particularly limited, and examples thereof include a method using a production apparatus described in WO2011 / 013567. The production apparatus includes a squeezer section, the squeezer section spraying a fine fibrous cellulose dispersion onto the upper surface of an endless belt, squeezing out a dispersion medium from the sprayed fine fibrous cellulose dispersion to produce a web, and a drying section drying the web to produce a fiber sheet. An endless belt is provided from the squeezer section to the drying section, and the web produced in the squeezer section is conveyed to the drying section while being placed on the endless belt.
[0359] The dehydration method that can be used in this embodiment is not particularly limited, and examples thereof include dehydration methods commonly used in paper production, preferably a method of dehydrating by roller pressure after dehydration using a Fourdrinier wire, a cylinder wire, an inclined wire mesh, etc. In addition, the drying method is not particularly limited, and examples thereof include methods used in paper production, preferably methods such as a cylinder dryer, a Yankee dryer, hot air drying, a near infrared heater, and an infrared heater.
[0360] (Laminated body)
[0361] The present invention may relate to a laminate formed by laminating the above-mentioned laminate and an adherend. It should be noted that when the adherend is configured on the resin layer side of the laminate, the resin layer in the laminate can function as an adhesive layer. As adherend, for example, an organic film (hereinafter referred to as an organic layer) and an inorganic film (hereinafter referred to as an inorganic layer) can be listed. Wherein, the laminate of the present embodiment is preferably a laminate formed by laminating the above-mentioned laminate and an adherend with an organic film. It should be noted that as an organic film, for example, a resin film, a resin plate, a resin molded body, etc. can be listed.
[0362] Resin film, resin plate and resin molded body (hereinafter also referred to as resin film) are layers with natural resin or synthetic resin as main components. Here, main component refers to a component containing 50% by mass or more relative to the total mass of the resin film. The content of the resin component is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more relative to the total mass of the resin film. It should be noted that the content of the resin component can be 100% by mass relative to the total mass of the resin film.
[0363] Examples of the natural resin include rosin-based resins such as rosin, rosin ester, and hydrogenated rosin ester.
[0364] Examples of the synthetic resin include polyolefin resins, cyclic olefin resins, polycarbonate resins, polyethylene terephthalate resins, polyethylene naphthalate resins, polyimide resins, polystyrene resins, acrylic resins, etc. Among them, the synthetic resin is preferably a polyolefin resin, preferably at least one selected from polyethylene resins and polypropylene resins.
[0365] The formation method of the organic layer is not particularly limited, and examples thereof include coating method, injection molding method, heating and pressing method, etc. In the coating method, the resin composition forming the organic layer is preferably coated on the resin layer of the laminate, and thermally cured or photocured. In addition, in the heating and pressing method, it is preferred to heat and pressurize the resin film in a state where the resin film is overlapped on the resin layer of the laminate. The heat and pressurization conditions at this time can be appropriately selected with reference to the glass transition temperature of the resin film, etc.
[0366] The material constituting the inorganic layer is not particularly limited, and examples thereof include aluminum, silicon, magnesium, zinc, tin, nickel, and titanium; their oxides, carbides, nitrides, carbon oxides, nitride oxides, or carbonitride oxides; or mixtures thereof. From the viewpoint of being able to stably maintain high moisture resistance, silicon oxide, silicon nitride, silicon oxycarbide, silicon oxynitride, silicon oxycarbonitride, aluminum oxide, aluminum nitride, aluminum oxycarbide, aluminum oxynitride, or mixtures thereof are preferred.
[0367] The method for forming the inorganic layer is not particularly limited, and examples thereof include chemical vapor deposition (CVD) and physical vapor deposition (PVD). As the CVD method, specifically, plasma CVD using plasma, catalytic chemical vapor deposition (Cat-CVD) using a heated catalyst to catalyze thermal cracking of a material gas, etc., can be cited. As the PVD method, specifically, vacuum evaporation, ion plating, sputtering, etc. can be cited. In addition, as a method for forming the inorganic layer, an atomic layer deposition (ALD) method can also be used. The ALD method is a method for forming a thin film in atomic layer units by alternately supplying raw material gases of the elements constituting the film to be formed to the surface of the forming layer.
[0368] (use)
[0369] The use of the fine fibrous cellulose of the present embodiment is not particularly limited, and examples thereof include concrete pump pipe lubricants (concrete pressure-feeding pump pipe lubricants), lubricants, casting compositions, dental materials, abrasives, stripping agents, papermaking additives, metal surface treatment agents, resin surface treatment agents, oil drilling, adhesives, cleaning agents, battery / capacitor electrodes / separators, antifreeze agents, pipe friction resistance reducing agents, filters, fragrances / deodorants, asphalt, absorbents, hydrolyzable sheets, antibacterial agents, insecticides / insect repellents, pesticides, etc. Among them, the fine fibrous cellulose of the present embodiment is preferably used in concrete pump pipe lubricants (concrete pressure-feeding pump pipe lubricants), lubricants, casting compositions, dental materials, abrasives, stripping agents, and papermaking additives.
[0370] In addition, the present embodiment may be a concrete pump pipe lubricant (concrete pressure-feeding pump pipe lubricant), a lubricant, a molding composition, a dental material, an abrasive, a release agent, or a papermaking additive comprising the fine fibrous cellulose.
[0371] Furthermore, the laminated sheet of the present embodiment is transparent, has high mechanical strength, and is suppressed in coloring. From the viewpoint of utilizing such excellent optical properties, it is suitable for use in optical components. It can be used for purposes of light-transmitting substrates such as various display devices and various solar cells. In addition, the laminated sheet of the present embodiment is also suitable for purposes such as substrates of electronic devices, components of household appliances, various vehicles, window materials of buildings, interior materials, exterior materials, and packaging materials.
[0372] Example
[0373] Below, enumerate embodiment and comparative example, and more specifically illustrate the feature of the present invention.The material, dosage, ratio, processing content, processing step etc. shown in the following embodiment can be appropriately changed within the scope not exceeding the gist of the present invention.Therefore, the scope of the present invention should not be subject to the restrictive interpretation of the specific example shown below.
[0374] <Production Example 1>
[0375] [Phosphorylation]
[0376] As the raw material pulp, broadleaf dissolving pulp (dried sheet) manufactured by Oji Paper Co., Ltd. was used. The raw material pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (absolute dry mass) of the raw material pulp, and the mixture was adjusted so that the ammonium dihydrogen phosphate was 45 parts by mass, the urea was 120 parts by mass, and the water was 150 parts by mass to obtain chemical solution impregnated pulp. Next, the obtained chemical solution impregnated pulp was heated in a hot air dryer at 165° C. for 250 seconds to introduce phosphoric acid groups into the cellulose in the pulp, thereby obtaining phosphorylated pulp.
[0377] [Cleaning treatment]
[0378] Next, the obtained phosphorylated pulp was subjected to a washing treatment. The washing treatment was performed by adding 10 L of ion exchange water to 100 g (absolute dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp uniformly, and then filtering and dehydrating the pulp, and repeating this operation. The point when the conductivity of the filtrate reached 100 μS / cm or less was regarded as the end point of the washing.
[0379] [Neutralization treatment]
[0380] Next, the washed phosphorylated pulp was neutralized as follows. First, the washed phosphorylated pulp was diluted with 10 L of ion exchange water, and then a 1N sodium hydroxide aqueous solution was added little by little while stirring, thereby obtaining a phosphorylated pulp slurry having a pH of 12 or more and 13 or less. Next, the phosphorylated pulp slurry was dehydrated to obtain a phosphorylated pulp subjected to a neutralization treatment. Next, the neutralized phosphorylated pulp was subjected to the above-mentioned washing treatment.
[0381] The infrared absorption spectrum of the phosphorus-containing oxygen-acidified pulp thus obtained was measured using FT-IR. -1Absorption of P=O based on phosphate groups was observed near the pulp, confirming that phosphate groups were added to the pulp. In addition, the obtained phosphorylated pulp was subjected to a test, and as a result of analysis using an X-ray diffraction device, characteristic peaks were confirmed at two locations near 2θ=14° to 17° and near 2θ=22° to 23°, confirming that it contained cellulose I type crystals.
[0382] [Fiberization]
[0383] Ion exchange water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content concentration of 2% by mass. The slurry was treated 6 times at a pressure of 200 MPa using a high-pressure homogenizer (manufactured by SUGINO MACHINE, STARBURST) to obtain a microfibrous cellulose dispersion containing microfibrous cellulose. X-ray diffraction confirmed that the microfibrous cellulose maintained cellulose type I crystals. It should be noted that the amount of phosphate groups (the first dissociated acid amount) measured using the measurement method described in the determination of [phosphorus oxyacid group amount] described later was 1.45 mmol / g. It should be noted that the total dissociated acid amount was 2.45 mmol / g.
[0384] <Production Example 2>
[0385] Phosphorylated pulp and a fine fibrous cellulose dispersion containing fine fibrous cellulose were obtained in the same manner as in Production Example 1 except that the following nitrogen removal treatment was performed after the washing treatment and neutralization treatment of the phosphorylated pulp.
[0386] [Nitrogen removal treatment]
[0387] Ion exchange water was added to the phosphorylated pulp to prepare a slurry with a solid content concentration of 4% by mass. A 48% by mass sodium hydroxide aqueous solution was added to the slurry to adjust the pH to 13.4, and the slurry was heated at a liquid temperature of 85°C for 1 hour. Thereafter, the pulp slurry was dehydrated, 10 L of ion exchange water was added to 100 g (absolute dry weight) of the phosphorylated pulp, and the obtained pulp dispersion was stirred in a manner that the pulp was uniformly dispersed, filtered and dehydrated, and this operation was repeated to remove excess sodium hydroxide. The time when the conductivity of the filtrate reached 100 μS / cm or less was regarded as the end point of the removal.
[0388] The infrared absorption spectrum of the phosphorus-containing oxygen-acidified pulp thus obtained was measured using FT-IR. -1Absorption of P=O based on phosphate groups was observed nearby, confirming that phosphate groups were added to the pulp. In addition, X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. It should be noted that the amount of phosphate groups (first dissociated acid amount) measured by the measurement method described in [Measurement of the amount of phosphorus oxyacid groups] described later was 1.35 mmol / g. It should be noted that the total dissociated acid amount was 2.30 mmol / g.
[0389] <Production Example 3>
[0390] [Phosphitylation treatment]
[0391] Phosphorylated pulp and a fine fibrous cellulose dispersion containing fine fibrous cellulose were obtained in the same manner as in Production Example 1 except that 33 parts by mass of phosphorous acid (phosphonic acid) was used instead of ammonium dihydrogen phosphate in the phosphorylation treatment.
[0392] The infrared absorption spectrum of the phosphorylated pulp thus obtained was measured using FT-IR. -1 Absorption of P=O based on the tautomer of the phosphite group, i.e., the phosphonate group, was observed nearby, confirming that the (phosphite) group (phosphonate group) was added to the pulp. In addition, the obtained fine fibrous cellulose was confirmed to maintain cellulose I type crystals by X-ray diffraction. It should be noted that the (phosphite) group amount (first dissociated acid amount) measured by the measurement method described in [Measurement of the amount of phosphorus oxyacid groups] described later was 1.51 mmol / g, and the total dissociated acid amount was 1.54 mmol / g.
[0393] <Production Example 4>
[0394] [Sulfate treatment]
[0395] Sulfated pulp and a microfibrous cellulose dispersion containing microfibrous cellulose were obtained in the same manner as in Production Example 1 except that 38 parts by mass of amidosulfuric acid (aminosulfonic acid) was used instead of diammonium phosphate in the phosphorylation treatment and the heating time was extended to 19 minutes.
[0396] The thus obtained sulfated pulp was subjected to infrared absorption spectrum measurement using FT-IR. -1 Absorption based on sulfate groups (sulfon groups) was observed nearby, confirming that sulfate groups (sulfon groups) were added to the pulp. In addition, X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose I type crystals. It should be noted that the amount of sulfon groups measured by the measurement method described in [Measurement of the amount of sulfon groups] described later was 1.12 mmol / g.
[0397] <Production Example 5>
[0398] Xanthated pulp and a fine fibrous cellulose dispersion containing fine fibrous cellulose were obtained in the same manner as in Production Example 1 except that the following xanthated treatment was performed instead of the phosphorylation treatment.
[0399] [Xanthate treatment]
[0400] 2500 parts by mass of an 8.5% by mass sodium hydroxide aqueous solution was added to 100 parts by mass (absolute dry weight) of raw material pulp (broadleaf dissolving pulp (dried flakes) manufactured by Oji Paper Co., Ltd.), and the mixture was stirred at room temperature for 3 hours to perform an alkali treatment. The alkali-treated pulp was subjected to solid-liquid separation by centrifugation (filter cloth 400 mesh, 3000 rpm, and 5 minutes) to obtain a dehydrated product of alkali cellulose. 3.5 parts by mass of carbon disulfide was added to 10 parts by mass (absolute dry weight) of the obtained alkali cellulose, and a sulfidation reaction was performed at room temperature for 4.5 hours to perform a xanthate treatment.
[0401] X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. The xanthate group content measured by the measurement method described in [Measurement of xanthate group content] described later was 1.73 mmol / g.
[0402] <Production Example 6>
[0403] Ion exchange water was added to raw material pulp (broadleaf dissolving pulp (dried flakes) manufactured by Oji Paper Co., Ltd.) to prepare a slurry having a solid content concentration of 2 mass %. The slurry was treated 30 times with a high pressure homogenizer (STARBURST manufactured by SUGINO MACHINE CO., LTD.) at a pressure of 200 MPa to obtain a cellulose dispersion containing coarse fibrous cellulose having a fiber width of more than 1000 nm.
[0404] [Table 1]
[0405]
[0406] <Example 1>
[0407] [Substituent removal treatment (high temperature heat treatment)]
[0408] A 20% by mass aqueous solution of citric acid was added to the fine fibrous cellulose dispersion obtained in Production Example 1 to adjust the pH of the dispersion to 5.5. The obtained slurry was placed in a pressure vessel and heated at a liquid temperature of 160° C. for 15 minutes until the amount of phosphate groups reached 0.08 mmol / g. This operation confirmed the formation of fine fibrous cellulose aggregates.
[0409] [Washing treatment of slurry after removal of substituent]
[0410] Add an equal amount of ion exchange water to the heated slurry to prepare a slurry with a solid content concentration of about 1% by mass. After stirring the slurry, filter and dehydrate it, and repeat this operation to wash the slurry. When the conductivity of the filtrate reaches 10μS / cm or less, add ion exchange water again to prepare a slurry of about 1% by mass, and let it stand for 24 hours. Thereafter, the operation of filtering and dehydrating is further repeated, and the moment when the conductivity of the filtrate reaches 10μS / cm or less again is taken as the end point of washing. Add ion exchange water to the obtained fine fibrous cellulose aggregate to obtain a slurry after removing the substituent. The solid content concentration of the slurry is 1.7% by mass.
[0411] [Uniform dispersion of slurry after removal of substituents]
[0412] Ion exchange water was added to the obtained slurry after the substituent was removed to prepare a slurry with a solid content concentration of 1.0% by mass. The pH of the slurry was 5.5. A high-pressure homogenizer (manufactured by SUGINO MACHINE, STARBURST) was used to treat the slurry three times at a pressure of 200 MPa to obtain a dispersion of microfibrous cellulose after the substituent was removed, which contained microfibrous cellulose after the substituent was removed. The number average fiber width of the microfibrous cellulose after the substituent was removed, measured by the [Determination of Fiber Width] described later, was 4 nm, and the proportion of microfibrous cellulose with a fiber width of less than 10 nm among all the fibrous cellulose contained in the dispersion was 98%.
[0413] [Film production 1]
[0414] Acetoacetyl-modified polyvinyl alcohol (GOHSENX Z-200 manufactured by Mitsubishi Chemical Corporation) was added to ion-exchanged water to give 12% by mass, and the mixture was stirred at 95° C. for 1 hour to dissolve the mixture. A polyvinyl alcohol aqueous solution was obtained through the above steps.
[0415] The fine fibrous cellulose dispersion after the substituents were removed and the polyvinyl alcohol aqueous solution were diluted with ion exchange water so that the solid content concentration was 0.6 mass %. Then, the diluted polyvinyl alcohol aqueous solution was mixed with 70 mass parts of the diluted fine fibrous cellulose dispersion after the substituents were removed so that 30 mass parts were obtained to obtain a mixed solution. Furthermore, the final basis weight of the sheet was 35 g / m 2The mixed solution was measured in a manner and spread on a commercially available acrylic plate. It should be noted that a blocking frame (internal dimensions of 250 mm×250 mm and a height of 5 cm) was arranged on the acrylic plate in a manner to achieve a predetermined basis weight. Thereafter, it was dried in a dryer at 70°C for 24 hours and peeled off from the acrylic plate to obtain a sheet containing fine fibrous cellulose after the substituents were removed. The thickness of the sheet was 25 μm.
[0416] <Example 2>
[0417] The same operation as in Example 1 was carried out except that the substituent removal treatment was carried out at a liquid temperature of 85° C. for 5 days to obtain a fine fibrous cellulose dispersion after the substituent was removed and a sheet containing the fine fibrous cellulose after the substituent was removed.
[0418] <Example 3>
[0419] The fine fibrous cellulose dispersion obtained in Production Example 1 was diluted to 0.7% by mass and subjected to a substituent removal treatment. After the washing treatment step after the substituent removal, ion exchange water was added to the obtained fine fibrous cellulose aggregate to prepare a slurry with a solid content concentration of 1.0% by mass. Except for this, the same operation as in Example 1 was performed to obtain a fine fibrous cellulose dispersion after the substituent removal and a sheet containing the fine fibrous cellulose after the substituent removal.
[0420] <Example 4>
[0421] The same operation as in Example 1 was performed except that the substituent removal treatment was carried out at a liquid temperature of 160°C for 40 minutes until the phosphate group amount reached 0.05 mmol / g, thereby obtaining a fine fibrous cellulose dispersion after the substituent removal and a sheet containing the fine fibrous cellulose after the substituent removal.
[0422] <Example 5>
[0423] The same operation as in Example 1 was performed except that the substituent removal treatment was carried out at a liquid temperature of 150°C for 15 minutes until the phosphate group amount reached about 0.21 mmol / g, thereby obtaining a fine fibrous cellulose dispersion after the substituent removal and a sheet containing the fine fibrous cellulose after the substituent removal.
[0424] <Example 6>
[0425] The same operation as in Example 1 was performed except that the substituent removal treatment was carried out at a liquid temperature of 140°C for 20 minutes until the phosphate group amount reached about 0.40 mmol / g, thereby obtaining a fine fibrous cellulose dispersion after the substituent removal and a sheet containing the fine fibrous cellulose after the substituent removal.
[0426] <Example 7>
[0427] A microfibrous cellulose dispersion after substituent removal and a sheet containing microfibrous cellulose after substituent removal were obtained in the same manner as in Example 1 except that the pH of the microfibrous cellulose dispersion subjected to the substituent removal treatment was adjusted to 2.4 and the pH of the slurry after substituent removal was adjusted to 5.5 after the washing treatment. The amount of phosphate groups after substituent removal was 0.22 mmol / g.
[0428] <Example 8>
[0429] A microfibrous cellulose dispersion after substituent removal and a sheet containing microfibrous cellulose after substituent removal were obtained in the same manner as in Example 1 except that the pH of the microfibrous cellulose dispersion subjected to the substituent removal treatment was not adjusted but the heat treatment was performed, and the pH was adjusted to 5.5 after the washing treatment of the slurry after substituent removal. The amount of phosphate groups after substituent removal was 0.29 mmol / g.
[0430] <Example 9>
[0431] The same procedures as in Example 1 were carried out except that a high-speed defibrator (CLEARMIX-11S, manufactured by M TECHNIQUE) was used to uniformly disperse the slurry after the substituent was removed and a microfibrous cellulose dispersion after the substituent was removed and a sheet containing the microfibrous cellulose after the substituent was removed were obtained.
[0432] <Example 10>
[0433] The substituent removal treatment was carried out by the following enzyme treatment without heat treatment, and the slurry after the substituent removal was washed by the following method. The same operation as in Example 1 was carried out to obtain a fine fibrous cellulose dispersion after the substituent removal and a sheet containing the fine fibrous cellulose after the substituent removal.
[0434] [Substituent removal treatment (enzyme treatment)]
[0435] A 20% by mass aqueous solution of citric acid was added to the obtained fine fibrous cellulose dispersion to adjust the pH of the slurry to 5.5. Acid phosphatase (AMYTIM PM manufactured by Shin Nippon Chemical Industries, Ltd.) was added to the obtained slurry in an amount of 3 parts by mass relative to 100 parts by mass of the fine fibrous cellulose, and the enzyme treatment was performed in a hot water bath at 37° C. for 2.5 hours. The generation of fine fibrous cellulose aggregates was confirmed by this operation.
[0436] [Washing treatment of slurry after removal of substituents by enzyme treatment]
[0437] To the obtained slurry after the removal of the substituent, 1 / 5 by volume of a strongly basic ion exchange resin (AMBERJET 4400; ORGANO Co., Ltd., adjusted) and a weakly acidic ion exchange resin (AMBERLITE IRC76; ORGANO Co., Ltd., adjusted) were added, and after shaking for 1 hour, the mixture was poured onto a sieve with a mesh of 90 μm to separate the resin and the slurry, thereby washing the slurry.
[0438] <Example 11>
[0439] A substituent-removed fine fibrous cellulose dispersion and a sheet containing substituent-removed fine fibrous cellulose were obtained in the same manner as in Example 1 except that the substituent-removed fine fibrous cellulose dispersion obtained in Production Example 2 was used instead of the substituent-removed fine fibrous cellulose dispersion obtained in Production Example 1.
[0440] <Example 12>
[0441] A substituent-removed fine fibrous cellulose dispersion and a sheet containing substituent-removed fine fibrous cellulose were obtained in the same manner as in Example 1 except that the substituent-removed fine fibrous cellulose dispersion obtained in Production Example 3 was used instead of the substituent-removed fine fibrous cellulose dispersion obtained in Production Example 1.
[0442] <Example 13>
[0443] A substituent-removed fine fibrous cellulose dispersion and a sheet containing substituent-removed fine fibrous cellulose were obtained in the same manner as in Example 1 except that the substituent-removed fine fibrous cellulose dispersion obtained in Production Example 4 was used instead of the substituent-removed fine fibrous cellulose dispersion obtained in Production Example 1.
[0444] <Example 14>
[0445] The fine fibrous cellulose dispersion obtained in Production Example 5 was used instead of the fine fibrous cellulose dispersion obtained in Production Example 1. Furthermore, the substituent removal treatment (low-temperature heat treatment) described later was performed instead of the substituent removal treatment (high-temperature heat treatment). Except for this, the same operation as in Example 1 was performed to obtain a fine fibrous cellulose dispersion after the substituent was removed and a sheet containing the fine fibrous cellulose after the substituent was removed.
[0446] [Substituent removal (low temperature heat treatment)]
[0447] The obtained fine fibrous cellulose dispersion was heated at a liquid temperature of 40° C. for 45 minutes until the amount of xanthate groups reached 0.08 mmol / g.
[0448] <Comparative Example 1>
[0449] A sheet containing fine fibrous cellulose was obtained by performing the same operation as in [Sheet Preparation 1] except that the fine fibrous cellulose dispersion obtained in Production Example 1 was used instead of the fine fibrous cellulose dispersion after the substituent was removed.
[0450] <Comparative Example 2>
[0451] A sheet containing fine fibrous cellulose was obtained in the same manner as in Comparative Example 1 except that the fine fibrous cellulose dispersion obtained in Production Example 3 was used.
[0452] <Comparative Example 3>
[0453] A sheet containing fine fibrous cellulose was obtained in the same manner as in Comparative Example 1 except that the fine fibrous cellulose dispersion obtained in Production Example 4 was used.
[0454] <Comparative Example 4>
[0455] A sheet containing fine fibrous cellulose was obtained in the same manner as in Comparative Example 1 except that the fine fibrous cellulose dispersion obtained in Production Example 5 was used.
[0456] <Comparative Example 5>
[0457] The same operation as in Example 1 was performed except that the substituent removal treatment was carried out at a liquid temperature of 140°C for 10 minutes until the phosphate group amount reached about 0.74 mmol / g, thereby obtaining a fine fibrous cellulose dispersion after the substituent removal and a sheet containing the fine fibrous cellulose after the substituent removal.
[0458] <Comparative Example 6>
[0459] A sheet containing coarse fibrous cellulose was obtained in the same manner as in Comparative Example 1 except that the cellulose dispersion containing coarse fibrous cellulose obtained in Production Example 6 was used.
[0460] <Comparative Example 7>
[0461] A dispersion of substituent-removed fine fibrous cellulose and a sheet containing substituent-removed fine fibrous cellulose were obtained in the same manner as in Example 1 except that uniform dispersion of the substituent-removed slurry was not performed.
[0462] <Comparative Example 8>
[0463] A dispersion of substituent-removed fine fibrous cellulose and a sheet containing substituent-removed fine fibrous cellulose were obtained in the same manner as in Example 12 except that uniform dispersion of the substituent-removed slurry was not performed.
[0464] <Comparative Example 9>
[0465] A dispersion of substituent-removed fine fibrous cellulose and a sheet containing substituent-removed fine fibrous cellulose were obtained in the same manner as in Example 13 except that uniform dispersion of the substituent-removed slurry was not performed.
[0466] <Comparative Example 10>
[0467] A dispersion of substituent-removed fine fibrous cellulose and a sheet containing substituent-removed fine fibrous cellulose were obtained in the same manner as in Example 14 except that uniform dispersion of the substituent-removed slurry was not performed.
[0468] <Comparative Example 11>
[0469] A dispersion of desubstituted microfibrous cellulose and a sheet containing desubstituted microfibrous cellulose were obtained in the same manner as in Example 1 except that the desubstituted slurry was stirred at 2000 rpm for 10 minutes without performing uniform dispersion.
[0470] <Comparative Example 12>
[0471] As described below, the substituents are removed in a sheet form instead of a slurry form to obtain a sheet containing fine fibrous cellulose after the substituents are removed.
[0472] [Filmmaking 2]
[0473] To the fine fibrous cellulose dispersion obtained in Production Example 1 before the removal of the substituent, glycerol was added in an amount of 15 parts by mass relative to 100 parts by mass of the fine fibrous cellulose. The concentration was adjusted so that the solid content concentration was 0.5% by mass. The final basis weight of the sheet was 37.5 g / m 2 The amount of slurry was measured in a manner and spread on a commercially available acrylic plate and dried in an oven at 50°C. It should be noted that a barrier plate was arranged on the acrylic plate in a manner to achieve a predetermined basis weight so that the resulting sheet was a quadrilateral. Through the above steps, a sheet containing fine fibrous cellulose was obtained. The thickness of the resulting sheet was 25 μm and the density was 1.49 g / cm 3 .
[0474] [Substituent Removal Treatment]
[0475] An object obtained by opening a 100 mmφ hole in a heat-resistant rubber sheet (manufactured by Shin-Etsu Chemical Co., Ltd., X-30-4084-U) is placed on a stainless steel plate, and 11 mL of ethylene glycol is filled into the hole. A sheet containing fine fibrous cellulose cut into 5 cm squares is immersed therein, and a stainless steel plate is overlapped thereon, and the sheet is set in a heat press machine heated to 180°C (manufactured by Imoto Seisakusho: manual hydraulic vacuum heating and pressing). As a substituent removal treatment, the sheet is treated at 180°C for 15 minutes, and then immersed in 30 mL of methanol for washing. The washing is repeated three times, and the sheet is pasted on glass, heated and dried at 100°C for 5 minutes to obtain a sheet containing fine fibrous cellulose after the substituent is removed. It should be noted that the amount of phosphate groups measured by the measurement method described in [Determination of the amount of phosphate groups in the sheet] described later is less than 0.1 mmol / g.
[0476] <Comparative Example 13>
[0477] A dispersion of desubstituted microfibrous cellulose and a sheet containing desubstituted microfibrous cellulose were obtained in the same manner as in Example 1 except that the following [ion exchange resin treatment of desubstituted slurry] was performed instead of [washing treatment of desubstituted slurry].
[0478] [Ion exchange resin treatment of slurry after removal of substituents]
[0479] Ion exchange water was added to the heated slurry obtained in [Substituent Removal Treatment (High-Temperature Heat Treatment)] to prepare a slurry having a solid content concentration of about 1.1 mass %, and then a 1 / 10 volume ratio of a strongly acidic ion exchange resin (AMBERJET 1024; ORGANO Co., Ltd., adjusted) and a 1 / 10 volume ratio of a strongly basic ion exchange resin (AMBERJET 4400; ORGANO Co., Ltd., adjusted) were added, and after shaking for 1 hour, the mixture was poured onto a sieve with a mesh size of 90 μm to separate the resin from the slurry. The pH of the obtained slurry was 3.1.
[0480] <Comparative Example 14>
[0481] A microfibrous cellulose dispersion after the substituents were removed and a sheet containing the microfibrous cellulose after the substituents were removed was obtained in the same manner as in Comparative Example 13, except that 1 / 10 of the amount of urea based on the microfibrous cellulose dispersion was added instead of citric acid in the [substituent removal treatment (high-temperature heat treatment)].
[0482] [evaluate]
[0483] The dispersions and sheets obtained in Examples and Comparative Examples were evaluated by the following methods.
[0484] [Measurement of fiber width]
[0485] The fiber width of fibrous cellulose is measured by the following method. Each fibrous cellulose dispersion is diluted with water in a manner that the concentration of cellulose is 0.01% by mass or more and 0.1% by mass or less, and cast on a hydrophilized carbon film-covered grid. After drying, it is stained with uranyl acetate and observed using a transmission electron microscope (TEM, manufactured by JEOL, JEOL-2000EX). At this time, an axis of arbitrary image width is assumed in the obtained image, and the magnification is adjusted in a manner that more than 20 fibers intersect the axis. After obtaining an observation image that meets this condition, two random axes in the vertical and horizontal directions are drawn for each image, and the fiber width of the fibers intersecting the axis is read visually. For each dispersion, three non-repetitive observation images are taken, and the fiber width values of the fibers intersecting the respective two axes are read (more than 20 × 2 × 3 = more than 120). It should be noted that the number average fiber width is calculated based on the fiber width obtained by such operation. However, only in Production Example 6, the obtained dispersion was diluted with water so that the cellulose concentration became 0.01 mass % or more and 0.1 mass % or less, and cast on glass, and observed with a scanning electron microscope (SEM).
[0486] In addition, the ratio of fine fibrous cellulose having a fiber width of 10 nm or less was determined according to the following formula.
[0487] Ratio of fine fibrous cellulose having a fiber width of 10 nm or less (%) = (number of fine fibrous cellulose having a fiber width of 10 nm or less / number of all fibrous cellulose) × 100
[0488] [Determination of phosphorus oxyacid group content]
[0489] In the measurement of the phosphorus oxyacid group content (phosphoric acid group or phosphorous acid group content), ion exchange water is first added to the microfibrous cellulose of interest to prepare a slurry having a solid content concentration of 0.2% by mass, and the obtained slurry is treated with an ion exchange resin and then titrated with an alkali to perform the measurement.
[0490] The treatment with ion exchange resin was performed as follows: 1 / 10 by volume of a strongly acidic ion exchange resin (AMBERJET 1024; manufactured by ORGANO Co., Ltd.) was added to the slurry containing fine fibrous cellulose, and after shaking for 1 hour, the mixture was poured onto a sieve with a mesh size of 90 μm to separate the resin from the slurry.
[0491] In addition, the titration using alkali is performed as follows: to the slurry containing fine fibrous cellulose treated with an ion exchange resin, 10 μL of a 0.1N sodium hydroxide aqueous solution is added every 5 seconds, and the change in the pH value shown by the slurry is measured. It should be noted that nitrogen gas is blown into the slurry from 15 minutes before the start of the titration, and the titration is performed. In this neutralization titration, in the curve obtained by plotting the measured pH against the amount of alkali added, two points where the increment (the differential value of pH with respect to the amount of alkali added) reaches a maximum are observed. The maximum point of the increment obtained first by adding alkali among them is called the first endpoint, and the maximum point of the increment obtained subsequently is called the second endpoint ( Figure 1 ). The amount of alkali required from the start of titration to the first endpoint is equal to the amount of the first dissociated acid in the slurry used for titration. In addition, the amount of alkali required from the start of titration to the second endpoint is equal to the total amount of dissociated acid in the slurry used for titration. It should be noted that the value obtained by dividing the amount of alkali required from the start of titration to the first endpoint (mmol) by the solid content (g) in the titration object slurry is the phosphorus oxyacid group amount (mmol / g).
[0492] It should be noted that when measuring the amount of phosphorus oxyacid groups in pulp, ion exchange water was added to phosphorus oxyacidified pulp to prepare a slurry with a solid content concentration of 2% by mass, and the slurry was treated 6 times at a pressure of 200 MPa using a high-pressure homogenizer (Starburst, manufactured by Sugino Machine Co., Ltd.), and the resulting dispersion was titrated with an alkali in the same manner as the above method.
[0493] [Determination of Sulfon Group Amount]
[0494] The sulfonate amount is measured as follows. After freezing the fine fibrous cellulose in a cold storage, dry it in a freeze dryer (FreeZone manufactured by LABCONCO) for 3 days. Using a manual stirrer (manufactured by Osaka Chemical Co., Ltd., LABMILSER PLUS), the resulting freeze-dried product is crushed at a speed of 20,000 rpm for 60 seconds to make it into a powder. In a closed container, nitric acid is used to pressurize and heat the sample after freeze drying and crushing. Thereafter, it is appropriately diluted and the sulfur content is determined by ICP-OES. The value calculated by dividing the absolute dry mass of the fine fibrous cellulose used for the test is used as the sulfate ester group amount (unit: mmol / g).
[0495] [Determination of xanthate base content]
[0496] The amount of xanthate base is measured by Bredee method. Specifically, 40 mL of saturated ammonium chloride solution is added to 1.5 parts by mass (absolute dry mass) of fibrous cellulose, and the sample is crushed with a glass rod while being fully mixed. After being placed for about 15 minutes, it is filtered with GFP filter paper (GS-25 made by ADVANTEC) and fully washed with saturated ammonium chloride solution. The sample is placed in a 500 mL high volume cup together with the GFP filter paper, and 50 mL of 0.5 M sodium hydroxide solution (5 ° C) is added and stirred. After being placed for 15 minutes, phenolphthalein solution is added until the solution turns pink, and 1.5 M acetic acid is added, and the point where the solution changes from pink to colorless is used as the neutralization point. After neutralization, 250 mL of distilled water is added and fully stirred, and 10 mL of 1.5 M acetic acid and 10 mL of 0.05 mol / L iodine solution are added using a full-capacity pipette. The solution is titrated with 0.05 mol / L sodium thiosulfate solution. The xanthate base amount was calculated by the following formula based on the titration amount of sodium thiosulfate and the absolute dry mass of fibrous cellulose.
[0497] Xanthate base amount (mmol / g) = (0.05×10×2-0.05×sodium thiosulfate titration (mL)) / 1000 / absolute dry mass of fibrous cellulose (g)
[0498] [Determination of the amount of phosphate groups in the tablet]
[0499] The concentration of phosphorus atoms in the sheet is measured by fluorescent X-ray analysis. Specifically, the intensity of characteristic X-rays of phosphorus atoms released when outer shell electrons transition to holes generated by excitation of inner shell electrons of phosphorus atoms when the sheet is irradiated with X-rays is measured, and the concentration of phosphorus atoms is calculated based on a standard curve prepared by the following method. The standard curve is prepared as follows: a sheet is prepared from a microfibrous cellulose dispersion liquid with a known amount of phosphate groups, and after fluorescent X-ray analysis is performed, the intensity of characteristic X-rays of phosphorus atoms and the amount of phosphate groups are plotted.
[0500] [Measurement of haze of dispersion liquid]
[0501] In the determination of the haze of the dispersion, the fibrous cellulose dispersion was diluted with ion exchange water to 0.2 mass %, and then measured using a haze meter (Murakami Color Technology Research Institute, HM-150) and a liquid glass cuvette (Fujiwara Manufacturing, MG-40, backlight path) with a light path length of 1 cm in accordance with JIS K 7136:2000. It should be noted that the zero point determination was performed using the ion exchange water contained in the glass cuvette. In addition, the dispersion to be measured was left to stand for 24 hours at 23° C. and a relative humidity of 50% before the measurement. The liquid temperature of the dispersion during the measurement was 23° C.
[0502] [Determination of Nanofiber Yield]
[0503] The nanofiber yield after centrifugal separation of the fibrous cellulose dispersion is determined by the following method. The nanofiber yield becomes an indicator of the yield of fine fibrous cellulose. The higher the nanofiber yield, the higher the yield of fine fibrous cellulose. The cellulose concentration of each dispersion is adjusted to 0.1% by mass, and centrifuged at 12000G for 10 minutes using a cooling high-speed centrifuge (KOKUSAN, H-2000B). The obtained supernatant is recovered and the cellulose concentration of the supernatant is determined. The yield of fine fibrous cellulose is calculated according to the following formula.
[0504] Nanofiber yield (mass %) = cellulose concentration in supernatant (mass %) / 0.1 × 100
[0505] [Determination of nitrogen content]
[0506] The total amount of nitrogen contained in the fine fibrous cellulose and free nitrogen contained in the fine fibrous cellulose dispersion was measured by the following method. The solid content concentration of each dispersion was adjusted to 1% by mass, and decomposition was performed by the Kjeldahl method (JIS K0102:2016 44.1). After decomposition, the amount of ammonium ions (mmol) was measured by cation chromatography, and the nitrogen content (mmol / g) was calculated by dividing it by the amount of cellulose (g) used in the measurement.
[0507] [Determination of urea group]
[0508] The amount of urea groups is determined by freeze-drying a slurry containing fibrous cellulose (fine fibrous cellulose and coarse fibrous cellulose) and then pulverizing the sample obtained by micro nitrogen analysis. The amount of urea groups introduced per unit mass of fine fibrous cellulose (mmol / g) is calculated by dividing the nitrogen content per unit mass of fine fibrous cellulose (g / g) obtained in the micro nitrogen analysis by the atomic weight of nitrogen.
[0509] [Measurement of total light transmittance of sheet]
[0510] The total light transmittance of the sheet was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory) in accordance with JIS K 7361-1:1997.
[0511] [Measurement of haze of sheet]
[0512] The haze of the sheet was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory) in accordance with JIS K 7136:2000.
[0513] [Yellowness index measurement of sheets before and after heating]
[0514] According to JIS K 7373:2006, the yellowness index of the sheet before and after heating was measured using Color Cute i (manufactured by Suga Test Instruments). It should be noted that the yellowness index after heating is the yellowness index of the sheet after heating at 160°C for 6 hours. The measured yellowness index was converted into a YI value when the thickness was 50 μm using the following formula.
[0515] YI value when the thickness is 50 μm = YI value of the sheet (measured value) × [50 / thickness of the sheet (μm)]
[0516] Here, the thickness of the sheet is measured using a stylus constant pressure thickness gauge (MILLITRON 1202DPG-02 manufactured by MAHR Corporation, TECLOCK CORPORATION) according to the following method. After a sheet having a size of 50 mm or more is cut into a square and humidified at 23° C. and a relative humidity of 50% for 24 hours, the thickness at four random points is measured, and the average value is taken as the thickness of the sheet.
[0517] In addition, the YI increase rate was calculated by the following method based on the yellowness index of the sheet before and after heating.
[0518] YI increase rate (%) = (yellowness index of the sheet after heating - yellowness index of the sheet before heating) / yellowness index of the sheet before heating × 100 [Table 2]
[0519]
[0520] [Table 3]
[0521]
[0522] [Table 4]
[0523]
[0524] The dispersion obtained in the examples contained microfibrous cellulose having a low amount of substituents and was highly transparent. In addition, the sheet obtained from the dispersion was highly transparent and had a small YI increase rate before and after heating.
[0525] On the other hand, when the substituent removal treatment is not performed or the removal treatment is insufficient, the YI increase rate of the obtained sheet before and after heating is large (Comparative Examples 1 to 5). In addition, when unmodified coarse fibrous cellulose is used, the obtained sheet is opaque (Comparative Example 6). Furthermore, when uniform dispersion is not performed after the substituent is removed, the transparency of the obtained slurry is low, and a tendency for low transparency of the obtained sheet is observed (Comparative Examples 7 to 11). It should be noted that when the substituent removal treatment is performed in a sheet form, the haze of the sheet is high and the YI value before heating is high (Comparative Example 12). In addition, when a uniform dispersion treatment is performed under conditions of a pH of less than 4, the haze of the sheet is high and the YI value after heating is high (Comparative Example 13).
[0526] [Measurement of sheet surface roughness]
[0527] Furthermore, the surface roughness of the sheets containing the substituent-free fine fibrous cellulose obtained in Examples 1, 3, 10 and 11 was measured. The surface roughness of the sheet was measured using an atomic force microscope (NanoScope IIIa manufactured by Veeco), and the arithmetic mean roughness of a 3 μm square on the sheet surface was taken as the surface roughness of the sheet.
[0528] [Table 5]
[0529]
[0530] As shown in the above table, the surface roughness of the sheet was low in all Examples.
[0531] [Measurement of pH of dispersion and surface pH of sheet]
[0532] Furthermore, the pH of the dispersion containing the substituent-removed fine fibrous cellulose obtained in Example 1 and Comparative Example 13 and the pH on the sheet surface were measured. When measuring the pH on the sheet surface, 10 μL of ion exchange water was dropped into a 1 cm square area on the sheet surface using a micropipette, and the pH of this area was measured using a flat pH composite electrode (6261-10C; manufactured by HORIBA).
[0533] [Viscosity measurement]
[0534] Furthermore, the viscosity of the dispersion containing the substituent-removed fine fibrous cellulose obtained in Example 1 and Comparative Example 13 was measured. The viscosity was measured as follows: the fine fibrous cellulose concentration was set to 0.4% by mass, and after being left to stand for 24 hours under an environment of 23° C. and a relative humidity of 50% before measurement, the viscosity was measured 3 minutes after the start of measurement using a B-type viscometer (manufactured by BLOOKFIELD, analog viscometer T-LVT) at 23° C. and a rotation speed of 3 rpm.
[0535] [Table 6]
[0536]
[0537] As shown in the results of the above table, the pH of the dispersion obtained in Comparative Example 13 and the pH of the sheet surface were less than 4. Therefore, yellowing was observed after heating. In addition, the viscosity of the dispersion obtained in Comparative Example 13 was lower than that of the dispersion obtained in Example 1, and in Comparative Example 13, the fine fibrous cellulose was short-fibered.
[0538] [Measurement of free nitrogen concentration in dispersion]
[0539] Furthermore, the free nitrogen content in the dispersion containing the substituent-removed fine fibrous cellulose obtained in Example 1, Comparative Examples 13, and Comparative Examples 14 was measured. Distilled water was added to the fine fibrous cellulose dispersion so that the fine fibrous cellulose concentration became 0.2% by mass, and the mixture was stirred for 24 hours. After stirring, a filtrate was obtained using a filter material having a pore size of 0.45 μm.
[0540] [Table 7]
[0541]
[0542] <Example 101>
[0543] [Substituent removal treatment (high temperature heat treatment)]
[0544] A 20% by mass aqueous solution of citric acid was added to the fine fibrous cellulose dispersion obtained in Production Example 1 to adjust the pH of the dispersion to 5.5. The obtained slurry was placed in a pressure vessel and heated at a liquid temperature of 160° C. for 15 minutes until the amount of phosphate groups reached 0.08 mmol / g. This operation confirmed the formation of fine fibrous cellulose aggregates.
[0545] [Washing treatment of slurry after removal of substituent]
[0546] Add an equal amount of ion exchange water to the heated slurry to prepare a slurry with a solid content concentration of about 1% by mass. After stirring the slurry, filter and dehydrate it, and repeat this operation to wash the slurry. When the conductivity of the filtrate reaches 10μS / cm or less, add ion exchange water again to prepare a slurry of about 1% by mass, and let it stand for 24 hours. Thereafter, the operation of filtering and dehydrating is further repeated, and the moment when the conductivity of the filtrate reaches 10μS / cm or less again is taken as the end point of washing. Add ion exchange water to the obtained fine fibrous cellulose aggregate to obtain a slurry after removing the substituent. The solid content concentration of the slurry is 1.7% by mass.
[0547] [Uniform dispersion of slurry after removal of substituents]
[0548] Ion exchange water was added to the obtained slurry after the substituent was removed to prepare a slurry with a solid content concentration of 1.0% by mass. The pH of the slurry was 5.5. A high-pressure homogenizer (manufactured by SUGINO MACHINE, STARBURST) was used to treat the slurry three times at a pressure of 200 MPa to obtain a dispersion of microfibrous cellulose after the substituent was removed, which contained microfibrous cellulose after the substituent was removed. The number average fiber width of the microfibrous cellulose after the substituent was removed, measured by the [Determination of Fiber Width] described later, was 4 nm, and the proportion of fiber widths below 10 nm was 98%.
[0549] [Film production 1]
[0550] Acetoacetyl-modified polyvinyl alcohol (GOHSENX Z-200 manufactured by Mitsubishi Chemical Corporation) was added to ion-exchanged water to give 12% by mass, and the mixture was stirred at 95° C. for 1 hour to dissolve the mixture. A polyvinyl alcohol aqueous solution was obtained through the above steps.
[0551] The fine fibrous cellulose dispersion after the substituents were removed and the polyvinyl alcohol aqueous solution were diluted with ion exchange water so that the solid content concentration was 0.6 mass %. Then, the diluted polyvinyl alcohol aqueous solution was mixed with 70 mass parts of the diluted fine fibrous cellulose dispersion after the substituents were removed so that 30 mass parts were obtained to obtain a mixed solution. Furthermore, the final basis weight of the sheet was 37.5 g / m 2 The mixed liquid is measured in a manner and spread on a commercially available acrylic plate. It should be noted that a blocking frame (internal dimensions of 250 mm×250 mm and a height of 5 cm) is arranged on the acrylic plate in a manner to obtain a predetermined basis weight. Thereafter, it is dried in a dryer at 70°C for 24 hours and peeled off from the acrylic plate to obtain a sheet containing fine fibrous cellulose after the substituents have been removed. The thickness of the sheet is 25 μm. It should be noted that the surface pH of the sheet containing fine fibrous cellulose after the substituents have been removed before the resin layer is laminated is 4.8.
[0552] [Formation of resin layer]
[0553] 100 parts by mass of an acrylic resin (AKURIT 8KX-012C manufactured by Daisei Fine Chemicals Co., Ltd., with a solid content concentration of 39% by mass) obtained by graft polymerization of an acrylic acid group having a hydroxyl group, 38 parts by mass of a polyisocyanate compound (TPA-100 manufactured by Asahi Kasei Chemicals Co., Ltd.) and 100 parts by mass of methyl ethyl ketone are mixed to obtain a resin composition. Next, the resin composition is applied to one surface of a sheet containing microfibrous cellulose after the substituent is removed by means of a rod coater, and then heated at 100°C for 1 hour to cure it, thereby laminating a resin layer. Furthermore, according to the same procedure, a resin layer is also laminated on the other surface of the sheet containing microfibrous cellulose after the substituent is removed. The thickness of the resin layer on each single side is 5 μm. According to the above steps, a laminated sheet having resin layers laminated on both surfaces of a sheet containing microfibrous cellulose after the substituent is removed is obtained.
[0554] <Example 102>
[0555] A laminated sheet was obtained in the same manner as in Example 101 except that the substituent removal treatment was performed at a liquid temperature of 85° C. for 5 days. The surface pH of the sheet containing the fine fibrous cellulose after the substituent was removed before lamination of the resin layer was 4.7.
[0556] <Example 103>
[0557] The fine fibrous cellulose dispersion obtained in Production Example 1 was diluted to 0.7% by mass, subjected to a substituent removal treatment, and after the washing treatment step after the substituent removal, ion exchange water was added to the obtained fine fibrous cellulose aggregate to prepare a slurry with a solid content concentration of 1.0% by mass. A laminated sheet was obtained in the same manner as in Example 101. The surface pH of the sheet containing the fine fibrous cellulose after the substituent removal before lamination of the resin layer was 4.8.
[0558] <Example 104>
[0559] A laminated sheet was obtained in the same manner as in Example 101 except that the substituent removal treatment was performed at a liquid temperature of 160°C for 40 minutes until the phosphate group content reached 0.05 mmol / g. The surface pH of the sheet containing the microfibrous cellulose after substituent removal before lamination of the resin layer was 4.8.
[0560] <Example 105>
[0561] A laminated sheet was obtained in the same manner as in Example 101 except that the substituent removal treatment was performed at a liquid temperature of 150°C for 15 minutes until the phosphate group content reached about 0.21 mmol / g. The surface pH of the sheet containing the microfibrous cellulose after substituent removal before lamination of the resin layer was 4.9.
[0562] <Example 106>
[0563] A laminated sheet was obtained in the same manner as in Example 101 except that the substituent removal treatment was performed at a liquid temperature of 140°C for 20 minutes until the phosphate group content reached about 0.40 mmol / g. The surface pH of the sheet containing the microfibrous cellulose after substituent removal before lamination of the resin layer was 4.7.
[0564] <Example 107>
[0565] A laminated sheet was obtained in the same manner as in Example 101 except that the pH of the fine fibrous cellulose dispersion subjected to the substituent removal treatment was adjusted to 2.4 and the pH of the slurry after the substituent removal was adjusted to 5.5 after the washing treatment. The amount of phosphate groups after the substituent removal was 0.22 mmol / g. It should be noted that the surface pH of the sheet containing the fine fibrous cellulose after the substituent removal before lamination of the resin layer was 4.7.
[0566] <Example 108>
[0567] A laminated sheet was obtained in the same manner as in Example 101 except that the pH of the fine fibrous cellulose dispersion subjected to the substituent removal treatment was not adjusted but a heat treatment was performed, and the pH of the slurry after the substituent removal was adjusted to 5.5 after the washing treatment. The amount of phosphate groups after the substituent removal was 0.29 mmol / g. It should be noted that the surface pH of the sheet containing the fine fibrous cellulose after the substituent removal before lamination of the resin layer was 4.9.
[0568] <Example 109>
[0569] A laminated sheet was obtained in the same manner as in Example 101 except that a high-speed defibrator (M TECHNIQUE, CLEARMIX-11S) was used for 180 minutes at a peripheral speed of 34 m / sec to uniformly disperse the slurry after the substituent was removed. The surface pH of the sheet containing the microfibrous cellulose after the substituent was removed before lamination of the resin layer was 4.8.
[0570] <Example 110>
[0571] The substituent removal treatment was performed by the following enzyme treatment without heat treatment, and the slurry after the substituent removal was washed by the following method. A laminated sheet was obtained in the same manner as in Example 101. The surface pH of the sheet containing the microfibrous cellulose after the substituent removal before lamination of the resin layer was 4.8.
[0572] [Substituent removal treatment (enzyme treatment)]
[0573] A 20% by mass aqueous solution of citric acid was added to the obtained fine fibrous cellulose dispersion to adjust the pH of the slurry to 5.5. Acid phosphatase (AMYTIM PM manufactured by Shin Nippon Chemical Industries, Ltd.) was added to the obtained slurry in an amount of 3 parts by mass relative to 100 parts by mass of the fine fibrous cellulose, and the enzyme treatment was performed in a hot water bath at 37° C. for 2.5 hours. The generation of fine fibrous cellulose aggregates was confirmed by this operation.
[0574] [Washing treatment of slurry after removal of substituents by enzyme treatment]
[0575] To the obtained slurry after the removal of the substituent, 1 / 5 by volume of a strongly basic ion exchange resin (AMBERJET 4400; ORGANO Co., Ltd., adjusted) and a weakly acidic ion exchange resin (AMBERLITE IRC76; ORGANO Co., Ltd., adjusted) were added, and after shaking for 1 hour, the mixture was poured onto a sieve with a mesh of 90 μm to separate the resin and the slurry, thereby washing the slurry.
[0576] <Example 111>
[0577] A laminated sheet was obtained in the same manner as in Example 101 except that the fine fibrous cellulose dispersion obtained in Production Example 2 was used instead of the fine fibrous cellulose dispersion obtained in Production Example 1. The surface pH of the sheet containing the fine fibrous cellulose after the substituent was removed before lamination of the resin layer was 4.7.
[0578] <Example 112>
[0579] A laminated sheet was obtained in the same manner as in Example 101 except that the fine fibrous cellulose dispersion obtained in Production Example 3 was used instead of the fine fibrous cellulose dispersion obtained in Production Example 1. The surface pH of the sheet containing the fine fibrous cellulose after the substituent was removed before lamination of the resin layer was 4.7.
[0580] <Example 113>
[0581] A laminated sheet was obtained in the same manner as in Example 101 except that the fine fibrous cellulose dispersion obtained in Production Example 4 was used instead of the fine fibrous cellulose dispersion obtained in Production Example 1. The surface pH of the sheet containing the fine fibrous cellulose after the substituent was removed before lamination of the resin layer was 4.8.
[0582] <Example 114>
[0583] The fine fibrous cellulose dispersion obtained in Production Example 5 was used instead of the fine fibrous cellulose dispersion obtained in Production Example 1. Furthermore, the substituent removal treatment (low temperature heat treatment) described later was performed instead of the substituent removal treatment (high temperature heat treatment). Except for this, the same operation as in Example 101 was performed to obtain a laminated sheet. It should be noted that the surface pH of the sheet containing the fine fibrous cellulose after the substituent was removed before laminating the resin layer was 6.9.
[0584] [Substituent removal (low temperature heat treatment)]
[0585] The obtained fine fibrous cellulose dispersion was heated at a liquid temperature of 40° C. for 45 minutes until the amount of xanthate groups became less than 0.08 mmol / g.
[0586] <Example 115>
[0587] A laminated sheet was obtained in the same manner as in Example 101 except that the resin layer was formed only on one surface of the sheet containing fine fibrous cellulose after desubstituents were removed in [Formation of Resin Layer]. The surface pH of the sheet containing fine fibrous cellulose after desubstituents were 4.8 before lamination of the resin layer.
[0588] <Example 116>
[0589] In [Preparation of Sheet 1], polyethylene oxide (PEO-18 manufactured by Sumitomo Seika Chemicals Co., Ltd.; viscosity average molecular weight of 4.3 million to 4.8 million) diluted to a solid content concentration of 0.6% was used instead of a polyvinyl alcohol aqueous solution having a solid content concentration of 0.6% by mass. Otherwise, the same operation as in Example 101 was performed to obtain a laminated sheet. It should be noted that the surface pH of the sheet containing the microfibrous cellulose after the substituent was removed before laminating the resin layer was 4.8.
[0590] <Example 117>
[0591] The step of [forming the resin layer] is changed as follows. Otherwise, the same operation as in Example 101 is performed to obtain a laminated sheet. 15 parts by mass of a modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Co., Ltd., IUPIZETA FPC-2136), 57 parts by mass of toluene, and 28 parts by mass of methyl ethyl ketone are mixed to obtain a resin coating liquid. Next, 2.25 parts by mass of an isocyanate compound (manufactured by Asahi Kasei Chemicals Co., Ltd., DURANATE TPA-100) as a bonding aid is added to the above-mentioned resin coating liquid, and mixed to obtain a resin composition. Next, the above-mentioned resin composition is applied to one side of a sheet containing fine fibrous cellulose after the substituent is removed by a rod coater, and then heated at 100°C for 1 hour to cure it, thereby laminating a resin layer. Furthermore, according to the same procedure, a resin layer is also laminated on the other side of the sheet containing fine fibrous cellulose after the substituent is removed. The thickness of the resin layer on each single side is 5 μm. The surface pH of the sheet containing fine fibrous cellulose from which the substituents were removed before lamination of the resin layer was 4.8.
[0592] <Example 118>
[0593] In [Preparation of Sheet 1], 60 parts by mass of the diluted polyvinyl alcohol aqueous solution were mixed with 40 parts by mass of the diluted fine fibrous cellulose dispersion after the substituent was removed to obtain a mixed solution. The final basis weight of the sheet was 35.0 g / m 2 The mixed solution was measured in a manner and spread on a commercially available acrylic plate. Except for this, the same operation as in Example 117 was performed to obtain a laminated sheet. It should be noted that the thickness of the sheet containing the microfibrous cellulose after the substituent was removed was 25 μm. It should be noted that the surface pH of the sheet containing the microfibrous cellulose after the substituent was removed before the resin layer was laminated was 3.2.
[0594] <Example 119>
[0595] In [Preparation of Sheet 1], 90 parts by weight of the diluted polyvinyl alcohol aqueous solution was mixed with 10 parts by weight of the diluted fine fibrous cellulose dispersion after substituent removal to obtain a mixed solution. The final basis weight of the sheet was 31.0 g / m 2 The mixed solution was measured in a manner and spread on a commercially available acrylic plate. Except for this, the same operation as in Example 117 was performed to obtain a laminated sheet. It should be noted that the thickness of the sheet containing the microfibrous cellulose after the substituent was removed was 25 μm. It should be noted that the surface pH of the sheet containing the microfibrous cellulose after the substituent was removed before the resin layer was laminated was 3.0.
[0596] <Example 120>
[0597] In [Preparation of Sheet 1], the final basis weight of the sheet was 105.0 g / m 2 The mixed solution was measured in a manner of , and developed on a commercially available acrylic plate. The same operation as in Example 117 was performed to obtain a laminated sheet. It should be noted that the thickness of the sheet containing the microfibrous cellulose after the substituent was removed was 70 μm. It should be noted that the surface pH of the sheet containing the microfibrous cellulose after the substituent was removed before the resin layer was laminated was 4.8.
[0598] <Example 121>
[0599] The step of [Formation of Resin Layer] is changed as follows, and the same operation as in Example 120 is performed to obtain a laminated sheet. 15 parts by mass of a modified polycarbonate resin (Mitsubishi Gas Chemical Co., Ltd., IUPIZETA FPC-2136), 57 parts by mass of toluene, and 28 parts by mass of methyl ethyl ketone are mixed to obtain a resin coating liquid. Next, 0.75 parts by mass of methacryloxypropyltrimethoxysilane (Momentive Performance Materials Japan, SILQUEST A-174SILANE), which is a silicone compound (silane coupling agent) and serves as a close-fitting aid, is added to the above-mentioned resin coating liquid, and mixed to obtain a resin composition. Next, the above-mentioned resin composition is applied to one surface of a sheet containing fine fibrous cellulose after the substituent is removed by a rod coater, and then heated at 100°C for 1 hour to cure it, thereby laminating a resin layer. Furthermore, according to the same procedure, a resin layer is also laminated on the other surface of the sheet containing fine fibrous cellulose after the substituent is removed. The thickness of the resin layer per one side was 5 μm. The surface pH of the sheet containing the fine fibrous cellulose after the substituent was removed before lamination of the resin layer was 4.8.
[0600] <Comparative Example 101>
[0601] A sheet containing fine fibrous cellulose was obtained by performing the same operation as in [Sheet Preparation 1] except that the fine fibrous cellulose dispersion obtained in Preparation Example 1 was used instead of the fine fibrous cellulose dispersion after the substituent was removed. The surface pH of the fine fibrous cellulose-containing sheet before lamination of the resin layer was 7.3.
[0602] <Comparative Example 102>
[0603] A fine fibrous cellulose-containing sheet was obtained in the same manner as in Comparative Example 101 except that the fine fibrous cellulose dispersion obtained in Production Example 3 was used. The surface pH of the fine fibrous cellulose-containing sheet before lamination of the resin layer was 7.2.
[0604] <Comparative Example 103>
[0605] A fine fibrous cellulose-containing sheet was obtained in the same manner as in Comparative Example 101 except that the fine fibrous cellulose dispersion obtained in Production Example 4 was used. The surface pH of the fine fibrous cellulose-containing sheet before lamination of the resin layer was 6.9.
[0606] <Comparative Example 104>
[0607] A fine fibrous cellulose-containing sheet was obtained in the same manner as in Comparative Example 101 except that the fine fibrous cellulose dispersion obtained in Production Example 5 was used. The surface pH of the fine fibrous cellulose-containing sheet before lamination of the resin layer was 6.3.
[0608] <Comparative Example 105>
[0609] A laminated sheet was obtained in the same manner as in Example 101 except that the substituent removal treatment was performed at a liquid temperature of 140°C for 10 minutes until the phosphate group content reached about 0.74 mmol / g. The surface pH of the sheet containing the microfibrous cellulose after substituent removal before lamination of the resin layer was 4.9.
[0610] <Comparative Example 106>
[0611] A laminated sheet was obtained in the same manner as in Comparative Example 101 except that the cellulose dispersion containing coarse fibrous cellulose obtained in Production Example 6 was used. The surface pH of the coarse fibrous cellulose-containing sheet before lamination of the resin layer was 5.8.
[0612] <Comparative Example 107>
[0613] A laminated sheet was obtained in the same manner as in Example 101 except that uniform dispersion of the slurry after removal of the substituent was not performed. The surface pH of the sheet containing the fibrous cellulose after removal of the substituent before lamination of the resin layer was 4.8.
[0614] <Comparative Example 108>
[0615] A laminated sheet was obtained in the same manner as in Example 112 except that uniform dispersion of the slurry after removal of the substituent was not performed. The surface pH of the sheet containing the fibrous cellulose after removal of the substituent before lamination of the resin layer was 4.6.
[0616] <Comparative Example 109>
[0617] A laminated sheet was obtained in the same manner as in Example 113 except that uniform dispersion of the slurry after removal of the substituent was not performed. The surface pH of the sheet containing the fibrous cellulose after removal of the substituent before lamination of the resin layer was 4.5.
[0618] <Comparative Example 110>
[0619] A laminated sheet was obtained in the same manner as in Example 114 except that uniform dispersion of the slurry after removal of the substituent was not performed. The surface pH of the sheet containing the fibrous cellulose after removal of the substituent before lamination of the resin layer was 6.8.
[0620] <Comparative Example 111>
[0621] A laminated sheet was obtained in the same manner as in Example 115 except that the microfibrous cellulose dispersion obtained in Production Example 1 was used instead of the microfibrous cellulose dispersion after the substituent was removed in [Sheet Preparation 1]. The surface pH of the microfibrous cellulose-containing sheet before lamination of the resin layer was 7.3.
[0622] <Comparative Example 112>
[0623] A laminated sheet was obtained in the same manner as in Example 116 except that the microfibrous cellulose dispersion obtained in Production Example 1 was used instead of the microfibrous cellulose dispersion after substituent removal in [Sheet Preparation 1]. The surface pH of the microfibrous cellulose-containing sheet before lamination of the resin layer was 7.2.
[0624] <Comparative Example 113>
[0625] A laminated sheet was obtained in the same manner as in Example 117 except that the microfibrous cellulose dispersion obtained in Production Example 1 was used instead of the microfibrous cellulose dispersion after substituent removal in [Sheet Preparation 1]. The surface pH of the microfibrous cellulose-containing sheet before lamination of the resin layer was 7.3.
[0626] <Comparative Example 114>
[0627] A laminated sheet was obtained in the same manner as in Example 118 except that the microfibrous cellulose dispersion obtained in Production Example 1 was used instead of the microfibrous cellulose dispersion after substituent removal in [Sheet Preparation 1]. The surface pH of the microfibrous cellulose-containing sheet before lamination of the resin layer was 6.9.
[0628] <Comparative Example 115>
[0629] A laminated sheet was obtained in the same manner as in Example 120 except that the microfibrous cellulose dispersion obtained in Production Example 1 was used instead of the microfibrous cellulose dispersion after the substituent was removed in [Sheet Preparation 1]. The surface pH of the microfibrous cellulose-containing sheet before lamination of the resin layer was 7.2.
[0630] <Comparative Example 116>
[0631] A laminated sheet was obtained in the same manner as in Example 121 except that the microfibrous cellulose dispersion obtained in Production Example 1 was used instead of the microfibrous cellulose dispersion after the substituent was removed in [Sheet Preparation 1]. The surface pH of the microfibrous cellulose-containing sheet before lamination of the resin layer was 7.2.
[0632] <Comparative Example 117>
[0633] A laminated sheet was obtained in the same manner as in Example 101 except that the following [ion exchange resin treatment of the slurry after desubstituent removal] was performed instead of [washing treatment of the slurry after desubstituent removal]. The surface pH of the sheet containing the microfibrous cellulose after desubstituent removal before lamination of the resin layer was 2.4.
[0634] [Ion exchange resin treatment of slurry after removal of substituents]
[0635] Ion exchange water was added to the heated slurry obtained in [Substituent Removal Treatment (High-Temperature Heat Treatment)] to prepare a slurry having a solid content concentration of about 1.1 mass %, and then a 1 / 10 volume ratio of a strongly acidic ion exchange resin (AMBERJET 1024; ORGANO Co., Ltd., adjusted) and a 1 / 10 volume ratio of a strongly basic ion exchange resin (AMBERJET 4400; ORGANO Co., Ltd., adjusted) were added, and after shaking for 1 hour, the mixture was poured onto a sieve with a mesh size of 90 μm to separate the resin from the slurry. The pH of the obtained slurry was 3.1.
[0636] <Comparative Example 118>
[0637] A laminated sheet was obtained in the same manner as in Comparative Example 117 except that 1 / 10 the amount of urea based on the microfibrous cellulose dispersion was added instead of citric acid in [Substituent Removal Treatment (High-Temperature Heat Treatment)]. The surface pH of the sheet containing the microfibrous cellulose after the substituent was removed before lamination of the resin layer was 2.4.
[0638] [evaluate]
[0639] The laminated sheets obtained in Examples and Comparative Examples were evaluated by the following methods.
[0640] [Measurement of fiber width]
[0641] The fiber width of fibrous cellulose is measured by the following method. Each fibrous cellulose dispersion is diluted with water in a manner that the concentration of cellulose is 0.01% by mass or more and 0.1% by mass or less, and cast on a hydrophilized carbon film-covered grid. After drying, it is stained with uranyl acetate and observed using a transmission electron microscope (TEM, manufactured by JEOL, JEOL-2000EX). At this time, an axis of arbitrary image width is assumed in the obtained image, and the magnification is adjusted in a manner that more than 20 fibers intersect the axis. After obtaining an observation image that meets this condition, two random axes in the vertical and horizontal directions are drawn for each image, and the fiber width of the fibers intersecting the axis is read visually. For each dispersion, three non-repetitive observation images are taken, and the fiber width values of the fibers intersecting the respective two axes are read (more than 20 × 2 × 3 = more than 120). It should be noted that the number average fiber width is calculated based on the fiber width obtained by such operation. Of these, for Examples 101 to 121 and Comparative Examples 105, 107 to 110, the measurement was performed using a fine fibrous cellulose dispersion after the substituent was removed, and for Comparative Examples 101 to 104, 111 to 116, the measurement was performed using a fine fibrous cellulose dispersion. In addition, only for the coarse fibrous cellulose used in Comparative Example 106, the dispersion was diluted with water so that the cellulose concentration was 0.01 mass % or more and 0.1 mass % or less, and the dispersion was cast on glass and observed using a scanning electron microscope (SEM).
[0642] In addition, the ratio of fine fibrous cellulose having a fiber width of 10 nm or less was determined according to the following formula.
[0643] Ratio of fine fibrous cellulose having a fiber width of 10 nm or less (%) = (number of fine fibrous cellulose having a fiber width of 10 nm or less / number of all fibrous cellulose) × 100
[0644] [Determination of the amount of phosphorus oxyacid groups / Determination of the amount of sulfonate groups / Determination of the amount of xanthate groups]
[0645] The amount of phosphorus oxyacid groups (phosphoric acid groups or phosphite groups), the amount of sulfonic groups, and the amount of xanthate groups were measured by the same methods as described above.
[0646] [Measurement of total light transmittance of laminated sheet]
[0647] The total light transmittance of the laminated sheet was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory) in accordance with JIS K 7361-1:1997.
[0648] [Measurement of haze of laminated sheet]
[0649] The haze of the laminated sheet was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory) in accordance with JIS K 7136:2000.
[0650] [Yellowness index measurement of laminated sheets before and after heating]
[0651] According to JIS K 7373:2006, the yellowness index (YI value) of the laminated sheet before and after heating was measured using Color Cute i (manufactured by Suga Test Instruments). It should be noted that the YI value after heating is the YI value of the laminated sheet after heating at 160° C. for 6 hours. In addition, the YI increase rate was measured using the following method.
[0652] YI increase rate (%) = (YI value of the sheet after heating - YI value of the sheet before heating) / YI value of the sheet before heating × 100
[0653] [Measurement of Surface pH of Sheet (CNF Sheet) Before Lamination of Resin Layer]
[0654] 10 μL of ion exchange water was dropped into a 1 cm square area on the sheet surface using a micropipette, and the pH of this area was measured using a flat pH composite electrode (6261-10C; manufactured by HORIBA Corporation).
[0655] [Table 8]
[0656]
[0657] [Table 9]
[0658]
[0659] [Table 10]
[0660]
[0661] [Table 11]
[0662]
[0663] AC: Acrylic
[0664] PIC: Polyisocyanate
[0665] PC: Polycarbonate
[0666] OSi: Organosilane
[0667] The laminated sheets obtained in the examples are highly transparent, and not only the YI before heating is low, but also the YI after heating is low (Examples 101 to 121). On the other hand, when the substituent removal treatment is not performed or the removal treatment is insufficient, the YI of the obtained laminated sheets after heating is high (Comparative Examples 101 to 105, 111 to 116). When unmodified coarse fibrous cellulose is used, the obtained laminated sheets are opaque (Comparative Example 106). When uniform dispersion after the substituent removal is not performed, the transparency of the laminated sheets is low (Comparative Examples 107 to 110).
[0668] <Example 501>
[0669] Prepare two samples obtained by trimming the laminated sheets obtained in Example 120 into 100 mm square. Use these two laminated sheets to clamp a polycarbonate plate with a size of 100 mm square and a thickness of 2 mm, and then clamp them with two stainless steel plates with a size of 200 mm square. Thereafter, insert it into a micro-test press (MP-WCH manufactured by Toyo Seiki Industries Co., Ltd.) set to room temperature, and heat it to 160°C in 3 minutes under a pressurization pressure of 0.2 MPa. After maintaining this state for 30 seconds, it takes 3 minutes to cool to 30°C. According to the above steps, a laminated body with the polycarbonate plate is obtained.
[0670] <Example 502>
[0671] A laminate of the laminate and a polycarbonate plate was obtained in the same manner as in Example 501 except that the laminate sheet obtained in Example 121 was used.
[0672] <Comparative Example 501>
[0673] A laminate of the laminated sheet obtained in Comparative Example 115 and a polycarbonate plate was obtained in the same manner as in Example 501, except that the laminated sheet obtained in Comparative Example 115 was used.
[0674] <Comparative Example 502>
[0675] A laminate of the laminated sheet obtained in Comparative Example 116 and a polycarbonate plate was obtained in the same manner as in Example 501, except that the laminated sheet obtained in Comparative Example 116 was used.
[0676] <Comparative Example 503>
[0677] In Example 501, the polycarbonate plate was not sandwiched between two laminate sheets and was processed using a micro-test press. This plate was used for evaluation.
[0678] [evaluate]
[0679] The laminates and plates obtained in Examples and Comparative Examples were evaluated by the following methods.
[0680] [Measurement of flexural elastic modulus]
[0681] Test pieces having a size of 80 mm×10 mm were cut out from the laminate and the plate, and a bending test was performed in accordance with JIS K 7171:2016 to measure the bending modulus.
[0682] [Appearance]
[0683] The YI values of the laminate and the plate were measured using Color Cute i (manufactured by Suga Test Instruments) in accordance with JIS K 7373: 2006. The appearance was evaluated based on the measurement results according to the following criteria.
[0684] A: YI is less than 10
[0685] B: YI is 10 or above
[0686] [Appearance]
[0687] The laminate and the plate were heated at 90° C. for 720 hours. Then, the YI values of the laminate and the plate were measured using ColourCute i (manufactured by Suga Test Instruments) in accordance with JIS K 7373:2006. The appearance was evaluated based on the measurement results according to the following criteria.
[0688] A: YI is less than 15
[0689] B: YI is 15 or above
[0690] [Table 12]
[0691]
[0692] The laminated sheets obtained in the examples have low YI before and after heating and good appearance. Furthermore, when made into a laminate, the bending elastic modulus also becomes higher, and the reinforcing effect of the resin material is also excellent (Examples 501 and 502). The bending elastic modulus of the laminated sheets that have not undergone a process including the removal of the substituents is slightly lowered, and the appearance when made into a laminate is also poor (Comparative Examples 501 and 502).
[0693] [Concrete pump pipe lubricant (concrete pressure pump pipe lubricant)]
[0694] <Example 615>
[0695] 100 parts by mass of porous calcium carbonate and 200 parts by mass of water are mixed, and the fine fibrous cellulose dispersion obtained in Example 1 after removing the substituent is added thereto in a manner that the solid component becomes 0.015 parts by mass, and fully mixed to make a concrete pump pipe lubricant (concrete pressure-feeding pump pipe lubricant). The resulting concrete pump pipe lubricant (concrete pressure-feeding pump pipe lubricant) shows good dispersion stability, and the viscosity of the composition is sufficiently low, and is a range without problems in terms of operability during actual use. Therefore, the above-mentioned composition is good as a concrete pump pipe lubricant (concrete pressure-feeding pump pipe lubricant).
[0696] [Lubricant]
[0697] <Example 616>
[0698] The fine fibrous cellulose dispersion obtained in Example 1 after removing the substituents, which is 0.2 parts by mass in terms of solid content, 12.5 parts by mass of polyalkylene glycol, 45.0 parts by mass of propylene glycol, 1.0 parts by mass of morpholine, 1.5 parts by mass of lauric acid, and 0.001 parts by mass of a metal inertizing agent (methylbenzotriazole alkanolamine salt) are prepared / stirred in such a manner that the total amount is 100 parts by mass and the balance is water to prepare a lubricant. The obtained lubricant exhibits good lubricity and storage stability. Therefore, the above composition is good as a lubricant used in the friction part of a machine.
[0699] [Molding composition]
[0700] <Example 617>
[0701] The fine fibrous cellulose dispersion obtained in Example 1 after removing the substituents, which is calculated as 0.25 parts by mass of solid content, 100 parts by mass of alumina (Al2O3) (Al-160SG-4, manufactured by Showa Denko Co., Ltd.) as an inorganic material, 0.2 parts by mass of A-6114 (ammonium salt of carboxylic acid copolymer, manufactured by Toagosei Co., Ltd.) as a dispersant, and 40 parts by mass of water are mixed, and then mixed for 24 hours using a ball mill to prepare a composition for casting. The obtained composition for casting shows good dispersion stability and castability. In addition, the obtained composition for casting is injected into a gypsum mold, left to stand at room temperature for 24 hours, and dried to obtain a wet molded body. The obtained wet molded body is fired in an electric furnace to produce a casting molded body. The obtained casting molded body can be easily demolded from the mold, and the ceramic has a high density. Therefore, the above-mentioned composition is good as a casting molded composition for improving the manufacturing efficiency of casting molded bodies such as ceramic products.
[0702] [Dental Materials]
[0703] <Example 618>
[0704] 4 parts by mass of dihydrate gypsum, 9 parts by mass of anhydrous gypsum, 3.2 parts by mass of magnesium oxide, 6 parts by mass of liquid paraffin, 1 part by mass of surfactant (trioleyl decaglycerol), 0.3 parts by mass of trisodium phosphate, and 3 parts by mass of diatomaceous earth were mixed to prepare a curing material paste. Furthermore, 3.5 parts by mass of potassium alginate, 60 parts by mass of water, and 10 parts by mass of diatomaceous earth were mixed to prepare a base material paste. Furthermore, 200 parts by mass of isopropanol were added to 100 parts by mass of the microfibrous cellulose dispersion after the removal of the substituent obtained in Example 1 to precipitate the microfibrous cellulose. The precipitate was recovered by filtration, and the recovered microfibrous cellulose was heated in an oven at 70°C for 3 hours. The solid content concentration of the heated microfibrous cellulose was 15% by mass. Mixing / kneading was performed in a manner that the microfibrous cellulose, which was 1 part by mass in terms of solid content, the curing material paste was 26.2 parts by mass, and the base material paste was 72.8 parts by mass to obtain a dental material composition. The obtained dental material composition exhibits good crushing resistance and heat resistance. Therefore, the composition is excellent as a dental material for use in the oral cavity for restoration of cast crowns and repair of defects.
[0705] <Comparative Example 615>
[0706] A dental material composition was obtained in the same manner as in Example 618 except that the fine fibrous cellulose dispersion obtained in Comparative Example 1 was used.
[0707] [YI increase rate of the dental material composition before and after heating]
[0708] The YI increase rates of the dental material compositions obtained in Example 618 and Comparative Example 615 before and after heating were measured by a reflectance measurement method using Color Cute (manufactured by Suga Test Instruments) in accordance with JIS K 7373:2006. The yellowness index after heating was set to the yellowness index of the composition after heating at 160° C. for 6 hours, and the YI increase rate was measured by the following method.
[0709] YI increase rate (%) = (yellowness index of the composition after heating - yellowness index of the composition before heating) / yellowness index of the composition before heating × 100
[0710] The YI increase rate of Example 618 was 850%, whereas the YI increase rate of Comparative Example 615 was 2130%. When the fine fibrous cellulose obtained in Example 618 and the substituents were removed was used, the yellowing was improved.
[0711] [Abrasive]
[0712] <Example 619>
[0713] The fine fibrous cellulose dispersion obtained in Example 1 after removing the substituents was prepared and stirred in a solid content of 0.2 parts by mass, 30 parts by mass of cerium oxide, and the balance of water to obtain an abrasive. The obtained abrasive exhibited good sprayability and anti-drip properties. Therefore, the above composition is good as an abrasive used for grinding and cleaning metal products, glass products, stone products, resin products, etc.
[0714] [Removal agent]
[0715] <Example 620>
[0716] The fine fibrous cellulose dispersion obtained in Example 1 after removing the substituents, which is 0.4 parts by mass in terms of solid content, 35 parts by mass of benzyl alcohol, and 2 parts by mass of hydrogen peroxide (H2O2) are prepared / stirred in such a manner that the total is 100 parts by mass and the balance is water to prepare a stripping agent. The result of the coating film stripping test of the obtained stripping agent is good, and no liquid dripping after adding the stripping auxiliary agent is observed. Therefore, the above composition is a good stripping agent used when stripping a coating film from a substrate such as an outer wall or a structure.
[0717] [Additives for papermaking]
[0718] <Example 621>
[0719] Waste paper (newspaper waste paper, cardboard waste paper, high-quality waste paper, discarded confidential documents, etc.) is dissolved by a pulper to obtain a recycled waste paper pulp slurry (water filtration: 220 ml, calcium content: 60 ppm, sodium content: 35 ppm). Thereafter, foreign matter such as dirt is removed from the recycled waste paper pulp slurry using a foreign matter removal device. Next, the fine fibrous cellulose dispersion after removal of substituents obtained in Example 1 is added to the recycled waste paper pulp slurry in such a manner that the solid content becomes 30 parts by mass relative to 100 parts by mass of the solid content of the recycled waste paper pulp. The obtained recycled waste paper pulp slurry is put into the container of a molding machine, and a conventional molding mold for pulp molding is used to form a mold with a thickness of 2.5±0.3 mm and a basis weight of 420±50 g / m 2 The pulp mold obtained shows good demoulding property and tensile strength. Therefore, the composition is good as an additive for papermaking.
[0720] <Example 622>
[0721] A pulp mold was obtained in the same manner as in Example 621 except that hardwood dissolving pulp manufactured by Oji Paper Industries, Ltd. was used instead of recycled waste paper pulp.
[0722] <Comparative Example 616>
[0723] A pulp mold was obtained in the same manner as in Example 622 except that the fine fibrous cellulose dispersion obtained in Comparative Example 1 was used.
[0724] [YI increase rate of pulp mold before and after heating]
[0725] The YI increase rate of the pulp molds obtained in Example 622 and Comparative Example 616 before and after heating was measured by a reflectance measurement method using Color Cute (manufactured by Suga Test Instruments) in accordance with JIS K 7373:2006. The yellowness index after heating was set to the yellowness index of the composition after heating at 160° C. for 6 hours, and the YI increase rate was measured by the following method.
[0726] YI increase rate (%) = (yellowness index of the composition after heating - yellowness index of the composition before heating) / yellowness index of the composition before heating × 100
[0727] The YI increase rate of Example 622 was 820%, whereas the YI increase rate of Comparative Example 616 was 2060%. When the fine fibrous cellulose obtained in Example 622 and the substituents were removed was used, the yellowing was improved.
Claims
1. A dispersion comprising fine fibrous cellulose, wherein the amount of substituents introduced into the fine fibrous cellulose is less than 0.5 mmol / g, the fiber width is 1 to 10 nm, and the fine fibrous cellulose has 0.001 mmol / g to 0.04 mmol / g or 0.09 mmol / g of urea groups.
2. The dispersion according to claim 1, wherein The substituent is an anionic group.
3. A sheet comprising fine fibrous cellulose having a substituent introduction amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm, When the sheet is heated at 160° C. for 6 hours, the YI increase rate calculated by the following formula is 1500% or less. YI increase rate (%) = (yellowness index of the sheet after heating - yellowness index of the sheet before heating) / yellowness index of the sheet before heating × 100 In the above formula, the yellowness index of the sheet is a yellowness index measured in accordance with JIS K 7373:2006. The sheet according to claim 3 , which has a haze of 5.0% or less.
5. A laminated sheet comprising a fiber layer and a resin layer, The fiber layer is the sheet according to claim 3.
6. The laminated sheet according to claim 5, wherein: The density of the fiber layer is 1.0 g / cm 3 above.
7. The laminated sheet according to claim 5 or 6, wherein: The resin layer includes at least one selected from the group consisting of polycarbonate resin, polyethylene terephthalate resin, and acrylic resin.
8. The laminated sheet according to claim 5 or 6, wherein: The resin layer further includes a adhesion aid. 9 . A laminate comprising the laminate sheet according to claim 5 or 6 and an adherend.
10. A method for producing microfibrous cellulose, comprising: A step (A) of removing at least a part of the substituent from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less; as well as After the step (A), a step (B) of performing a uniform dispersion treatment is performed.
11. The method for producing fine fibrous cellulose according to claim 10, wherein The amount of substituents introduced into the fine fibrous cellulose subjected to the step (A) is 0.60 mmol / g or more.
12. The method for producing fine fibrous cellulose according to claim 10 or 11, wherein The substituent is an anionic group.
13. The method for producing fine fibrous cellulose according to claim 10 or 11, wherein The fine fibrous cellulose subjected to the step (A) has a urea group. 14 . The method for producing fine fibrous cellulose according to claim 10 or 11 , further comprising a step of reducing the amount of nitrogen.
15. The method for producing fine fibrous cellulose according to claim 10 or 11, wherein The step (A) is performed in a slurry state.
16. The method for producing fibrous cellulose according to claim 15, wherein Prior to the step (A), the method further includes adjusting the pH of the slurry containing fine fibrous cellulose to 3 to 8.
Citation Information
Patent Citations
Polycarbonate resin / cellulose fiber laminate and method for producing the same
JP2010023275A
Laminate and method for producing the same
JP2014079938A
Production method of de-esterified compound
JP2015098526A
Laminate
JP2017056715A
Sheet containing derivative functional group-detached cellulose fine fibers
JP2019007101A